Thermal plasma pyro-gasification of bio-oil for H2/CO-Rich syngas production - Tamer M. Ismail; Xiaoxiao Meng; Rui Sun; M.Abd El-Salam; Lu Ding (Fuel, 2027)

Titanium dioxide and gold nanoparticles toxicity in albino rats: Biochemical, anatomical, histopathological, and immunohistochemical studies - Yasmine A. Mansour; Alaa H. Elsayed; Fady Sayed Youssef; Sameh H. Ismail; Gehad Genidy Mohamed; Meray N. Ramsis; Samar Kamel; Basma A. Elkhadrawey; Mujtaba Farooq Rana; Heba H. Mahboub; Aya M. Mekkawy (Tissue and Cell, 2027)

Advanced and functionalized biomass-derived carbon materials for energy conversion, storage, and smart systems: Synthesis strategies, structure–property relationships, and AI integration - Basiru O. Yusuf; Mansur Aliyu; Ijaz Hussain; Mustapha Umar; Aliyu M. Alhassan; Yahuza Nantomah Abdulai; Jamilu Nura Musa; Esraa Kotob; Omer A. Taialla; Ismail Abdulazeez; Saheed A. Ganiyu (Biomass and Bioenergy, 2027)

Antifungal activity of phycocyanin and phycocyanin-loaded chitosan nanoparticles against postharvest black rot (Alternaria citri) of citrus fruit - Ahmed M. Khairy; Soha Sabry; Hossam S. El-Beltagi; Mohamed M. El-Mogy; Eman Ibrahem; Amged El-Harariy; Doaa.S. Mahmoud; Sameh H. Ismail; Ali Osman (Postharvest Biology and Technology, 2026)

Ensuring authenticity in coffee: A systematic review of coffee adulteration and mislabeling practices, advanced detection methods and quality assurance - Mohammad Mehdizadeh; Mariam Ayad Abd; Esraa H. Mahdi; Aseel Smerat; Leena J. Patel; Vipasha Sharma; Sayed M. Ismail; Mahzuna Turdialiyeva (Food and Humanity, 2026)

Correction: Molecular characterization and cuticular stomatal anatomy of Punica Granatum L. cultivars study in Dohuk governorate - Dalal Y. Kh. Sinjare; Shamiran S. Abdulrahman; Nizek S. Khalid; Rizgar Y. Ismail; Muhammad Yasir Naeem; Zeliha Selamoglu; Gani Issayev; Aveen M. N. Ahmed (Molecular Biology Reports, 2026)

Suppression of miR426 enhances photoprotection and chlorophyll stability via upregulation of ELIP2 in Arabidopsis thaliana - Arif Faisal Mustaffa; Syed Muhammad Iqbal Syed Othman; Nur Irdina Izzatie Mohd Zahid; M. Hafiz Che-Othman; Hoe-Han Goh; Muhammad Sajad; Ismanizan Ismail (Molecular Biology Reports, 2026)

Mitigating indoor air quality risks from Cladosporium sphaerospermum-induced biodeterioration of oil-based paints using silver and zinc oxide nanoparticles - Ismail R. Abdel-Rahim; Nivien A. Nafady; Magdy M. K. Bagy; Ahmad M. Abd-Alkader; Mohamed Hemida Abd-Alla (Aerobiologia, 2026)
Indoor air quality is significantly compromised by the biodeterioration of building materials, such as oil-based paints, which facilitates the release of fungal bioaerosols posing health risks to occupants. This study examines the role of Cladosporium sphaerospermum as a key airborne contaminant in paint degradation and evaluates metal nanoparticles as antimicrobial additives to mitigate associated bioaerosol emissions. Cladosporium sphaerospermum was isolated from deteriorated oil-based paint samples and identified via phenotypic and genotypic analyses. Microscopic evaluations, including stereomicroscopy, light microscopy, and scanning electron microscopy (SEM), confirmed its primary involvement in paint degradation through surface invasion and colonization. The fungus displayed robust lipase and urease activities, with specific activities of 43.2 and 824 units per milligram protein, respectively, indicating enzymatic breakdown of paint components. Indoor air quality assessments identified C. sphaerospermum as the predominant bioaerosol in environments with degraded paint, accounting for 69.8% of the total fungal count (128 CFU/m 3 ), followed by Aspergillus niger at 11.7%. Incorporation of silver nanoparticles (Ag-NPs; 3–60 nm particle size) and zinc oxide nanoparticles (ZnO-NPs; 18.2 nm particle size) into oil-based paints markedly improved resistance to fungal deterioration in vivo, relative to controls. These results underscore Ag-NPs and ZnO-NPs as effective additives for enhancing paint longevity and reducing fungal bioaerosol contamination in indoor settings, particularly from C. sphaerospermum and related dematiaceous fungi.

Boosting plant immunity via intercropping: Changes in the microbiome, induced resistance, and defense signaling networks - Mohamed M. El-Mogy; Sameh A. Hussein; Fatmah Ahmed Safhi; Mohamed Abdel-Haleem; Hossam S. El-Beltagi; Ahmed M. Ismail; Wael Elmenofy; Amira A. Ibrahim (Physiological and Molecular Plant Pathology, 2026)

Synergistic impact of toxic cyanobacterial blooms and bacterial pathogens on European seabass (Dicentrarchus labrax) mortality in the Eastern Mediterranean - Ghada E. Hegazy; Hussein Oraby; Amr Fadel; Mohamed A. Aly-Eldeen; Hassan A.H. Ibrahim; Mona M. Ismail (Continental Shelf Research, 2026)

Green-synthesized pure and Cr-doped Co3O4 nanoparticles for catalytic dye removal from wastewater: Kinetic and mechanistic insights - Fatima A.S. Al-Yusufy; Basheer M. Al-Maswari; Zulfa M. Abaker; Tasneem I. Hussein; Fatima A. Al- Qadri; Bakheit Mustafa; Mukhtar Ismail; Noon G. Al-Harbi (Journal of Environmental Chemical Engineering, 2026)

A novel hybrid cooling strategy for residential buildings integrating PV-powered AC and PCM thermal energy storage with intermittent operation - Zeyad Amin Al-Absi; Muhammad Asif; Ismail M. Budaiwi; Mohammed Alhaji Mohammed; Nedhal Al-Tamimi (Energy and Buildings, 2026)

Effects of dietary supplementation with chitosan nanogel on biochemical, antioxidant traits, and resistance to Aeromonas sobria infection, in Cyprinus carpio fingerlings - Hanan M. Alharbi; Heba H. Mahboub; Yasmine A. Mansour; Rasha M. M. Ezz-Eldin; Sherif M. Shawky; Sahar H. Orabi; Sameh H. Ismail; Tarek Khamis; Shaimaa A. A. Ahmed (Veterinary Research Communications, 2026)

Post-thaw quality, apoptosis, oxidative stress, microbiota, and in vivo fertility of buffalo bull semen in response to quercetin nano-emulsion or hesperidin-loaded chitosan nanoparticles supplementation - Wael A. Khalil; Aya A. Ismail; Mahmoud A.E. Hassan; Mohamed M. Hegazy; Mostafa A. El-Harairy; Sameh A. Abdelnour; Mahmoud Moussa (Animal Reproduction Science, 2026)

Aloe vera powder bio-filled jute fiber epoxy composites with enhanced thermal stability and modified water absorption behavior - Md Mahadi Hassan Parvez; Md. Arafat Islam; Md. Ismail Hossain; Mamun Hasan; Md. Shariat Ulla Shuvo; Md. Shoyeb; A. S. M. Tauabur Rahman Mondal; M. Ahasan Habib (Next Research, 2026)

Perspectives: Effect of global change drivers on carbon fluxes and resilience of European forests - Mana Gharun; Charlotte Angove; Mirco Migliavacca; Yu Zhou; Kate Buckeridge; Cristina Branquinho; Alessio Collalti; Line Nybakken; Miglena Zhiyanski; Murat Sarginci; Ismail Koc; Abdullah Huseyin Donmez; et al. (Forest Ecology and Management, 2026)

Innovative nanotechnology approach using salicylic acid loaded chitosan nanoparticles to improve post-thaw sperm function, reduce apoptosis, and preserve ultrastructure in rams - Wael A. Khalil; Azza S. El-Demerdash; Mahmoud A. E. Hassan; Khaled Fathy; Sherif M. Dessouki; Mostafa A. El-Harairy; Aya A. Ismail; Ali A. El-Raghi (Tropical Animal Health and Production, 2026)

Advancing energy efficiency in smart transportation through intelligent technologies and policy innovation - F. B. Ismail; S. T. Yousif; I. M. Albayati; R. H. Al-Hadeethi; S. M. AL Shurafa; M. A. AlMubaidin (International Journal of Energy and Water Resources, 2026)
The transportation sector remains one of the largest contributors to global energy consumption and carbon emissions, particularly in rapidly urbanizing and emerging economies. This study presents an integrative review of intelligent technologies, system optimization approaches, and policy frameworks aimed at improving transportation energy efficiency, with a focused assessment of the Association of Southeast Asian Nations (ASEAN) member states. By synthesizing evidence from peer-reviewed literature, international energy databases, and official policy documents, the study evaluates the roles of transport electrification, intelligent transport systems, artificial intelligence–based energy management, and regulatory support mechanisms. The analysis reveals that electrification alone delivers limited efficiency gains unless integrated with artificial intelligence–driven optimization tools such as predictive analytics, real-time traffic management, and coordinated energy–transport system control. Evidence from Malaysia, Thailand, and Indonesia demonstrates notable progress in electric vehicle incentives, manufacturing strategies, and battery supply chain development, while highlighting persistent barriers including inadequate charging infrastructure, fragmented regulations, data limitations, and supply chain instability. The findings further emphasize that alternative fuels and system-level operational strategies remain essential complementary solutions. Unlike previous reviews that examine transport electrification, intelligent transport systems, artificial intelligence applications, or policy measures separately, this study develops an integrated analytical perspective that evaluates their combined influence on transportation energy efficiency. The principal contribution of the review is the development of a unified AI-enabled conceptual framework that positions artificial intelligence as the central coordinating layer linking vehicle technologies, transport operations, energy management systems, and policy instruments. By focusing on ASEAN economies while maintaining broader applicability to emerging regions, the framework provides strategic guidance for accelerating the transition toward intelligent, energy-efficient, and climate-resilient transportation systems.

Biological effects of statins in systemic sclerosis: a systematic review and meta-analysis of 323 patients - Mostafa A. Khalifa; Hamzah M. Alghzawi; Shehabeldin S. Anan; Ahmad Al Rifai; Ayah A. Anwar; Hayder Ali Raheem Al-Saedi; Eman Awady; Islam Masood; Mohamed Elsayed Badr; Mohamed Ismail; Obada Muayaid; Omar M. Ahmed; et al. (DARU Journal of Pharmaceutical Sciences, 2026)

Molecular docking and experimental validation for the protective effect of betanin against capecitabine-induced myocardial injury: Binding to TLR4 and downregulation of MyD88/NFκB signaling - Tahani A. Saeedi; Fady T. Hakem; Mohamed A. Helal; Marwa Hussein Mohamed; Heba W.Z. Khella; Mohamed H. Elbassiouny; Hussein M. Ismail; Asma M. Alshahrani; Abir S. Mohamed; Asmaa Saleh; Noura Moustafa Mohamed; Sawsan A. Zaitone (Tissue and Cell, 2026)

Alteration of Triassic Magmatic Rocks in Northwestern Tunisia: Mineralogical and Geochemical Constraints from the Djebel Debadib and Regional Geodynamic Implications - Randa Ben Abdallah; Mansour M. Abdelmalak; Suhail S. Alhejji; Abdullah Alohali; Abdullah I. Nabhan; Saleh Ismail Qaysi (Journal of African Earth Sciences, 2026)

Volatile oils as natural approach during pandemics: therapeutic contributions to respiratory health and mechanisms of action as antiviral, antimicrobial, immunomodulatory, and anti-inflammatory agents - Hamdoon A. Mohammed; Hebatallah M. Saad; Salman A. A. Mohammed; Riaz A. Khan; Ghassan M. Sulaiman; Suliman A. Almahmoud; Ali Z. Al-Saffar; Mohd Masih Uzzaman Khan; Ahmed Ismail (Phytochemistry Reviews, 2026)

Enhancement of the Anti-Inflammatory Effect of Zingerone Using the Galactosylated Chitosan Nano Formula Against CCl4-Induced Hepatic Fibrosis: An In Vivo Study - Safaa M. Ismail; Zienab E. Eldin; Mohamed H. Elbakkay; Adel Abdel-Moneim; Ahmed A. G. El-Shahawy; Mohamed I. Zanaty (Journal of Pharmaceutical Innovation, 2026)

Preparation and Evaluation of Curcumin Nanocrystals for Topical Administration: Cell Line Analysis and Histopathological Examination - Doaa M. Garhy; Soha Ismail; Howida K. Ibrahim (Journal of Pharmaceutical Innovation, 2026)

Comparative application of different rock mass classification systems for determining rock mass properties and support design for a tunnel in weak rock: a case study - Mamdouh E. Osman; Ashraf M. Osman; Nabil M. Nagy; Ismail M. Kamal (Innovative Infrastructure Solutions, 2026)

Synthesis, computational studies, and biological evaluation of novel cyanoacrylamides as potential anticancer agents - Marwa H. Soliman; Karim Barakat; Ismail A. Abdelhamid; Mona H. Mohamed; Emad M. Elzayat; Abdelhady A. Abdelwahab; Yasmin M. Attia; Mohamed A. Ragheb (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Influence of Infiltration Methods on Runoff Estimation for Sustainable Rainwater Harvesting in Arid Regions - Ismail Abd‐Elaty; Alban Kuriqi; Elsayed M. Ramadan; Marmar Mabrouk; Ibrahim Elbagory (Irrigation and Drainage, 2026)
Arid regions face severe water stress due to limited rainfall and growing water demand, making accurate runoff estimation essential for sustainable water management. Infiltration processes strongly influence both hydrograph volume and peak discharge, and their accurate estimation is critical for hydrological modelling. This study applies the Watershed Modelling System (WMS) to evaluate rainwater harvesting potential in the Wadi El‐Aawag watershed, southwestern Sinai, Egypt, using four infiltration loss estimation methods: Uniform Loss (LU), Green–Ampt (LGA), Holtan (LH) and the Soil Conservation Service (SCS) curve number method. Each method accounts for soil type, land cover and infiltration characteristics, enabling assessment across recurrence intervals of 5, 10, 25, 50 and 100 years. The results indicate considerable variation in runoff response across the selected methods. The estimated runoff volumes were 35.11, 24.10, 31.65 and 23.57 million m 3 for LU, LGA, LH and SCS, respectively, for recurrence intervals of 100 years. Among the tested approaches, the SCS method provided the most reliable and realistic estimates for the study area. These findings emphasise the importance of method selection when modelling infiltration losses and highlight the role of robust hydrological assessment in optimising rainwater harvesting, mitigating drought risks and enhancing long‐term water security in arid regions.

Design of a multi-epitope vaccine candidate against Mycobacterium ulcerans for the prevention of Buruli ulcer - Muhammad Asim; Ramy S. Yehia; Hotaf Hassan Makki; Ahmed M. Ismail (Biologia, 2026)

Ecotoxicological and health risk assessing of heavy metals and microplastics in African catfish (Clarias gariepinus) of Burullus Lake, Egypt - Muhammad A. El-Alfy; Marwa M. AbouHadied; Tahany A. Ismail (Environmental Science and Pollution Research, 2026)

Exploiting the biocontrol potential of Chaetomium globosum against Fusarium solani root rot in wheat: climate-responsive phytohormonal regulation, genetic diversity, and sustainable management - Marwa S. Fouad; Khaled M. A. Ramadan; Hisham A. Mohamed; Mohamed Abou-Zeid; Shafik D. Ibrahim; Muhammad Munir; Eslam S. A. Bendary; Mohamed M. Aboul Fotouh; Sallah A. Al Hashedi; Adil AlShoaibi; Zafar Iqbal; Ahmed M. Ismail; et al. (European Journal of Plant Pathology, 2026)

Paclobutrazol-mediated improvement of brown spot resistance in rice seedlings under salinity stress conditions - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Abdelaziz M. Tahoon; Hosny Hamed Kesba; Elsayed Abd Elmaksoud Abomarzoka; Ahmed Mahmoud Ismail; Awad Mohamed El-Sayed; Wael Elmenofy; Metwaly Mahfouz Salem Metwaly (European Journal of Plant Pathology, 2026)

Microplastic contamination in locally and industrially produced organic fertilizers: Implications for sustainable agriculture and risk mitigation - Mahfuz Ahmmed; Md Hasibuzzaman; Ismail M. Rahman; Sadia Sultana Mitu; Tapos Kumar Chakraborty; Gopal Chandra Ghosh (Chemosphere, 2026)

A preliminary study on eyestalk-based age estimation in the orange mud crab, Scylla olivacea - N. Hasyima-Ismail; A. Hidir; H. Fazhan; K. Waiho; H. Ma; R.M. Piah; M. Ikhwanuddin (Fisheries Research, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

Bioactive fructans from Bacillus subtilis and the multifunctional role of L3 with cytotoxic, anticoagulant, and antimicrobial activities - Amira A. Gamal; Asmaa Ezzat; Shaymaa A. Ismail; Shaimaa A. Nour; Khaled Mahmoud; Amal M. Hashem; Mona A. Esawy (Food Chemistry, 2026)

Relative abundance of genes regulating proliferation and apoptosis of corpus luteum during cold and hot seasons in Egyptian buffaloes - Samaa M. Galal; Sally Ibrahim; Karima Mahmoud; Ola Adel; Aya A. Shokry; M. S. El-Belely; S. T. Ismail (Tropical Animal Health and Production, 2026)

Functional and structural characterization of the SARS-CoV-2 spike N481K mutation - Maria K. Smatti; Hebah Al-Khatib; Muhammad Suleman; Muna Nizar; Hala Abo Khalid; Ruaa Ismail; Gheyath K. Nasrallah; Hadi M. Yassine (Archives of Virology, 2026)
Background: Selective pressure drives SARS-CoV-2 evolution, with spike RBD substitutions shaping ACE2 binding and antibody escape. N481K RBD mutation emerged early in Qatar (2020) and later re-emerged globally, reaching near-fixation by 2024–2025, yet its functional significance remained unexplored. Methods: We analyzed the temporal and geographic circulation of N481K across > 17 million SARS-CoV-2 genomes (2020–2025). Structural effects were assessed using modeling, docking, and molecular dynamics. Functional impact was evaluated using VSV pseudovirus neutralization tests with sera from infected individuals (n = 48) and vaccinated cohorts: mRNA (n = 16), Sinopharm (n = 45), and AstraZeneca (n = 28). Results: N481K was detected in 4.14% (703,777/17,016,111) of global genomes and reached near-fixation (> 90%) in dominant Omicron lineages by 2024, with prevalence rising from 71.5% in early 2024 to 94.4% by week 36 of 2025. Structural analyses showed a 0.706 Å RMSD deviation and higher ACE2 docking affinity (–313 vs. − 308 kcal/mol) compared to the wild-type (WT) RBD. Molecular dynamics confirmed increased stability and lower binding free energy for N481K versus WT (–77.07 ± 0.90 vs. − 43.09 ± 0.98 kcal/mol). Among samples with detectable WT neutralization (n = 89), mean neutralization declined from 69.76% (WT) to 42.47% (N481K) (p

Integrated synthesis and computational assessment of sulfanilamide–triazolo–oxadiazole triads as effective ALP and amylase inhibitors - Bisma Iqbal; Aamer Saeed; Mian Bilal Haider; Hammad Ismail; Guoqiang Yang; Abdullah Tariq; Basant Farag; Sobhi M. Gomha; Hesham R. El-Seedi (In Silico Pharmacology, 2026)

Evaluation of Downscaled CMIP6 Performance for Rainfall and Wind Over the Maritime Continent - Inovasita Alifdini; Fiolenta Marpaung; Erma Yulihastin; M. Furqon Azis Ismail; Abdul Basit (International Journal of Climatology, 2026)
High‐resolution climate change projections over the Maritime Continent (MC) are increasingly critical to develop climate policies and adaptation planning at the regional level. However, modelling rainfall and wind over the MC still leads to substantial errors in capturing climate processes over the most complex land–atmosphere–ocean interaction. This study evaluated the performance of the 14 downscaled CMIP6 models from the NASA Earth Exchange Global Daily Downscaled Projections (NEX‐GDDP) at 0.25° resolution in simulating spatial and temporal variability of rainfall and wind over the MC. The simulated rainfall and wind speed over the period 1995–2014 are evaluated against meteorological station data and gridded datasets, including the Climate Hazards Group InfraRed Rainfall with Station data (CHIRPS) for rainfall and the European Centre for Medium‐Range Weather Forecasts Reanalysis 5 (ERA5) for wind speed. Results demonstrated that the models are capable of representing the regional characteristics of the annual and seasonal variation of rainfall and wind. Nevertheless, systematic biases remain consistently overestimated for rainfall when compared with observations (35%–94%) and slightly underestimated compared with CHIRPS (−4% to −5.6%). The model overestimated wind for both mean and extreme wind (i.e., 34%–120% for observations and 11%–48% for ERA5), except western MC showed a slight underestimation relative to ERA5 (−6.9%). The largest bias of extreme rainfall intensity is mainly depicted over region C (Maluku) compared to regions A (Sumatra) and B (Java). This result suggests that the models are capable of simulating monsoonal and equatorial rainfall patterns compared to anti‐monsoonal rainfall, which may be dominated by anvil rain type. Our study also highlighted that model rankings vary according to the variable, reference dataset and metric used, and that no single model consistently outperforms.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Mineral analysis of Pistacia species with inductively coupled plasma-mass spectrometry (ICP-MS) - Ahmed Boukeloua; Fatima Senouci; Mohamed Boukeloua; Hamdi Bendif; Omar H. Abd-Elkader; İsmail Yener; Maryam M. Alomran; Stefania Garzoli (Natural Product Research, 2026)

Geochemical and isotopic signature of a rift-to-arc transition in the Neoproterozoic Adrar Souttouf Massif, Moroccan Sahara - Omar Guillou; M'hamed El Janati; Nasrrddine Youbi; Andreas Gärtner; Michel Villeneuve; João Mata; Jean-Louis Bodinier; Abdelhak Ait Lahna; Moualy Ahmed Boumehdi; Ismail Hadimi; Oussama Moutbir; Colombo Celso Gaeta Tassinari; et al. (Geochemistry, 2026)

Sycamore fig (Ficus sycomorus) fruit-derived Milk-clotting enzyme as a partial rennet substitute: Effects on physicochemical, textural, and sensory properties of soft white cheese - Wael F. Elkot; Hesham A. Ismail; Tawfiq Alsulami; Mohamed S. Mostafa; Suleiman A. Althawab; Basim M. Alohali; Hadeer Lotfy Abu-Taha; Ammar Al-Farga; Ahmed Elmahdy (Food Research International, 2026)

Impact of carbon ink on papyrus mechanical and chemical characteristics during accelerated aging: an experimental investigation - Bataa S. M. Mazen; Mohamed Z. M. Salem; Mostafa Abdel-Hamied; Badawi M. Ismail; Mahmoud Ali; Wael S. Mohamed; Rushdya R. A. Hassan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)

Synergistic Role of Biochar and Beneficial Aspergillus fumigatus (P2P) in Improving Growth, Physiological Performance, and Antioxidant Activity of Garlic (Allium sativum L.) - Zahir Ullah; Wasim Khan; Naila Shah; Awais Ahmad; Heba I. Mohamed; Abdelrahman R. Ahmed; Haiam O. Elkatry; Ahmed Mahmoud Ismail; Mohamed M. El-Mogy; Wael Elmenofy (Journal of Soil Science and Plant Nutrition, 2026)

Development and Evaluation of Econazole Nitrate Loaded Cubosomal Gel for Enhanced Topical Antifungal Therapy - Sonam M. Gandhi; Yakub Ismail Bhorat; Devesh U. Kapoor; Samaresh Pal Roy; Omar Awad Alsaidan; Sami I. Alzarea (Journal of Pharmaceutical Innovation, 2026)

The possible effects of folic acid and postbiotic yeast on doxorubicin–induced cardiotoxicity in rats: interactions among the gut microbiota, antioxidants, and NLrp3 activities - Heba M. Galal; Marwa H. Bakr; Dalia A. Elgamal; Nahla M. Elsherbiny; Doaa M. Raafat; Asmaa M. Ismail; Sally A. Sayed (Journal of Molecular Histology, 2026)

Biomonitoring of Polycyclic Aromatic Hydrocarbons in Pregnant Women from Mbarara Regional Referral Hospital, Uganda: Predictors of Exposure, Risk Assessment and Health Implications - Nicodemus Niwamanya; Godswill J. Udom; Omoirri M. Aziakpono; Nita-wills G. Udom; Iboro E. Idem; Daniel N. Obot; Ismail O. Akande; Joseph G. Omole; Muyiwa M. Orosun; Mutabar Latipova; Nazira Madatova; Doniyor Jumanazarov; et al. (Exposure and Health, 2026)

The role of melatonin in attenuation of vascular endothelin-1 reactivity via calcium channels and endothelial derived relaxing factors in STZ-induced diabetic aortic rats - Chrakhan J. Khdhir; Ridha H. Hussein; Ismail M. Maulood (Journal of Muscle Research and Cell Motility, 2026)

Cytotoxic pregnane glycosides from Monolluma quadrangula (Forssk.) - Ghada A. Ismail; Mohamed E. Mostafa; Ahmed Y. Mubarak; AbelAziz M. Dawidar; Mamdouh Abdel-Mogib (Natural Product Research, 2026)

Basal immunity of date palm under biotic stress: Redox signaling, immune suppression, and hidden vulnerabilities revealed by red palm weevil attack - Mohamed M. El-Mogy; Mostafa Ibrahim Abdelglil; Mohamed Abdel-Haleem; Amira A. Ibrahim; Fatmah Ahmed Safhi; Hossam S. El-Beltagi; Ahmed M. Ismail; Wael El-menofy; Ahmed I.H. Ismail; Mohamed Gad (Physiological and Molecular Plant Pathology, 2026)

Metabolomics-guided Mechanisms of Mesenchymal Stromal Cell and Exosome Therapies in Chronic Diseases - Asma Ismail Mahmod; Kayatri Govindaraju; Yogeswaran Lokanathan; Nur Akmarina; B. M. Said; Baharudin Ibrahim (Stem Cell Reviews and Reports, 2026)

Comparative analysis of the morphological heterogeneity of smooth muscle cells in two avian species: the muscovy Duck (Cairina moschata) and the Japanese quail (Coturnix japonica): ultrastructural and histochemical study - Hanan H. Abd-Elhafeez; Alaa Sayed Abou-Elhamd; Basma Mohamed Kamal; Hesham Ismail; Sherief M. Abdel-Raheem; Mahmoud H. A. Mohamed; Ahmed M. A. Meligy; Soha A. Soliman (Protoplasma, 2026)

Identification of the holocrine oil gland in gills of silver carp using semi-thin sections and transmission electron microscopy - Hanan H. EL Hafeez; Basma Mohamed Kamal; Hesham Ismail; Sherief M. Abdel-Raheem; Ahmed M. A. Meligy; Soha A. Soliman (Protoplasma, 2026)

Antimicrobial and antibiofilm actions of iridoids: a comprehensive mechanistic review - Ahmed H. Elosaily; Ahmed M. El-Dessouki; Marwa Ali-Tammam; Mona Ismail; Momen Lotfy; Haidy A. Abbas; Mohamed S. Abd El Hafeez; Riham A. El-Shiekh; Dalia El Amir; Ghadir A. Sayed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Trace elements in industrial wastewater: assessment of ETP efficiency and health risks using deterministic and probabilistic methods - N. H. Rupa; M. Ismail; M. T. Rahman; N. Sultana; F. Afrose; H. R. Shuvo; M. Moniruzzaman (International Journal of Environmental Science and Technology, 2026)

Exploring topical atorvastatin hyalurosomal gel as an adjuvant for reducing systemic corticosteroid dosage: a randomized clinical trial in severe oral lichen planus patients - Mahitab Elsayed; Aya Essawy; Radwa M. Ismail; Yasmine Gamil; Mohamed G. Hamed; Dalia Elsabaawy; Eman Abdelhakeem; Doaa Hegazy; Radwa M. A. Abd-Elal (Drug Delivery and Translational Research, 2026)
Oral lichen planus (OLP) is a chronic inflammatory disorder with limited topical treatment options and long-term corticosteroid dependency. This study investigates a novel atorvastatin-loaded hyalurosomal gel (ATV-Hyalugel) as a topical adjuvant to reduce systemic corticosteroid use in severe OLP. The objective of the study is to develop, optimize, characterize ATV-Hyalugel and evaluate its clinical efficacy in a randomized controlled clinical trial. ATV-loaded hyalurosomes (ATV-HAs) were prepared via thin-film hydration and optimized using an I-optimal mixture design (independent variables: phospholipid, Tween 80, and hyaluronic acid; responses: entrapment efficiency (EE%), particle size (PS), and zeta potential (ZP). The optimal formulation was incorporated into a chitosan gel, which was characterized for its pH, rheological behavior, and in-vitro drug release. Four weeks randomized controlled trial (n = 90) compared: group one received standard prednisolone (40 mg/day) while group two received half-dose prednisolone (20 mg/day) in combination with ATV-Hyalugel (topically, three times daily). Pain and ulcer scores were recorded weekly. Between-group comparisons were performed using the Mann–Whitney U test (non-parametric; α = 0.05), and within-group improvement from baseline to Week 4 was assessed using the Kruskal–Wallis test. Optimized ATV-HAs demonstrated high EE% (79.1 ± 0.4%), uniform PS (221.2 ± 5.1 nm), and stable ZP (–31.6 ± 0.2 mV). ATV-Hyalugel exhibited mucosa-compatible pH (6.48 ± 0.2), pseudoplastic rheology, and a sustained release profile dominated by diffusion-driven kinetics. Clinically, group two achieved therapeutic equivalence to group one by Week 2 (p > 0.05), despite receiving 50% less corticosteroid. Both groups showed significant symptom reduction from baseline to Week four (p < 0.0001, Kruskal–Wallis). No adverse events were reported with ATV-Hyalugel. ATV-Hyalugel enables a 50% corticosteroid dose reduction while maintaining clinical efficacy. Its favorable release kinetics and safety profile support its use as an innovative adjuvant therapy for severe OLP.

Mannosylated fisetin/carveol lipid nanocapsules: brain-targeted dual therapy for modulation of epileptogenesis and cognitive deficits - Julie R. Youssef; Nabila A. Boraie; Fatma A. Ismail; Basant A. Bakr; Eman A. Allam; Mahmoud A. Agami; Riham M. El-Moslemany (Drug Delivery and Translational Research, 2026)
Pharmacological treatment of epilepsy is challenged by several barriers with the blood brain barrier (BBB) imposing the utmost restrictions to brain drug delivery. Antiepileptic drugs aim to reduce seizures frequency and severity while exerting minimal toxic effects. Herein, the merits of phytomedicine and brain targeted nanocarriers were combined for the control of seizures in a chronic epilepsy model. Fisetin (FS); a polyphenol and carveol (CAR); a limonene monoterpenoid were selected for their neuroprotective roles and co-loaded into lipid nanocapsules (FS/CAR@LNC). This was further decorated with mannose by post insertion targeting glucose transporter (GLUT-1) overexpressed on BBB (MAN-FS/CAR@LNC). The optimized MAN-FS/CAR@LNC revealed good colloidal properties with particle size (53.17 ± 4.06 nm), and low polydispersity index (0.11) and 26.9 ± 1.05 mV zeta potential. A high entrapment efficiency exceeding 99% and sustained drug release profile over 72 h were observed for both FS and CAR. In the in vivo imaging system (IVIS), MAN-FS/CAR@LNC attained 1.3-fold increase in fluorescence intensity at 5 h interval compared to FS/CAR@LNC. Following intraperitoneal administration in PTZ- induced chronic epilepsy mouse model, MAN-FS/CAR@LNC achieved maximal control of epileptic seizures accompanied with rehabilitation of locomotion, depressive and anxiety like-behaviors compared to FS/CAR and FS/CAR@LNC. Similarly, analysis of biomarkers reflecting depression and anxiety actions (brain-derived neurotrophic factor; BDNF, serotonin and glutamate) together with inflammatory markers (IL-6 and IL-1ꞵ) and histopathological assessment affirmed MAN-FS/CAR@LNC excelling in enhancing LNC brain targetability and hence seizures control. In conclusion, FS/CAR co-therapy aided with mannosylated LNC could present a compelling podium for the effective management of CNS disorders.

Myricetin as a potential therapeutic agent against Pseudomonas aeruginosa : inhibition of biofilm formation, quorum sensing, and virulence factor production - Sallah A. Al Hashedi; Saif M. Dmour; Hamad Sarheed Galut; Ayman Daifallah Ismail Alsheikh; Mohammad H. Abukhalil; Sham Ma’aitah; Najeeb S. Al-Zoreky; Khaled M.A. Ramadan; Muhammad Naeem Sattar; Zafar Iqbal; Adil Alshoaibi; Sultan A. M. Saghir (Biofouling, 2026)

Heavy metals in basic vegetables of the Bagerhat district, Bangladesh - Tusar Kanti Roy; Sudipta Kumar Nag; Md. Saiful Islam; Zulhilmi Ismail; Abubakr M. Idris (Food Additives & Contaminants Part B-Surveillance, 2026)

Pumpkin seed oil improves hepatotoxicity in rats through inhibition of CYP2E1 and activation of Nrf2 signaling pathways - Noran W. Esmail; Sawsan M. El-sheikh; Reda M.S. Korany; Arwa A. Hassan; Sara M. Baraka; Hanan M. Alharbi; Ayman K. Ismail; Doaa A. Mansour; Heba H. Mahboub; Esraa.M. Fahmy (Tissue and Cell, 2026)

Green synthesis of copper oxide nanoparticles using fig leaves extract and their use as an antibacterial agent - Intessar K. Abd; Rusul K. Ismail; Shahlaa M. Abd Al Hussan; Karim Al-Jashamy; Aseel D. salman; Ahlam K. Abd (Next Research, 2026)

Beyond survival: Can we engineer plants to thrive in and remediate radioactive environments? - Iqbal Hossen; M. Mehedi Hasan Rocky; Zinnat Rahman; Ismail Rahman (Journal of Environmental Radioactivity, 2026)

Diagenesis and hydraulic flow characteristics of the Paleozoic Shifa sandstones in the western desert, Egypt: Implications for new prospective reservoir targets - Ahmed Ismail Mahmoud; Xiaodong Ma; Shib Sankar Ganguli; Ahmed Shakkar; Ahmed M. Metwally; Walid M. Mabrouk; Mahmoud Leila (Journal of African Earth Sciences, 2026)

Bioactive-driven modulation of structural, rheological, and functional properties in tiger nut–based frozen food matrices enriched with selected fruit pulps - Hesham A. Ismail; Wafaa M. Salama; Arwa M. Ali; Wael F. Elkot; Tawfiq Alsulami; Suleiman A. Althawab; Basim M. Alohali; Ammar Al-Farga; Rezk A. Awad (Food Research International, 2026)

Atmospheric microplastics deposition in Dhaka City, Bangladesh: occurrence, distribution and ecological risk assessment - Md Tauhiduzzaman; Nishat Salsabil; Kobita Khatun; Md Muhaiminul Haque; Ahsan Habib; Mst Shamima Akter; Sojib Islam; Md Hasibuzzaman; Ismail M. Rahman; Mahfuz Ahmmed; Samina Zaman; Tapos Kumar Chakraborty; et al. (Atmospheric Pollution Research, 2026)

Heat stress in dairy buffalo: biometeorological, molecular, and adaptive strategies for climate change resilience in subtropical regions - Eman M. Ismail; Aly M. Aly; Heba S. Farag; Shaimaa Kamel; Karima M. Fahim (Veterinary Research Communications, 2026)
Buffalo milk production in Egypt has steadily declined since 2014, mainly due to climate-driven heat stress (HS) and rising temperature–humidity index (THI). This quasi-field study randomly evaluated twelve lactating buffalo during peak summer, introducing a biometeorological approach to define and predict HS impacts precisely. Heat stress in buffalo was classified according to THI ranges as follows: non-HS zone (NHSZ, 56.7–73.2), moderate HS zone (MHSZ, 73.2–75.4), severe HS zone (SHSZ, 75.4–80.3), and critical HS zone (CHSZ, ≥ 80.3). Two models were compared: Model I (natural, group A) and Model II (adaptive, group B), which received targeted environmental and management interventions. Continuous monitoring of THI alongside daily milk yield (DMY), physiological responses, oxidative stress biomarkers, and the expression of key energy homeostasis genes was assessed in both groups. Adaptive interventions effectively reduced THI exposure, shifted animals from critical HS to non-HS zones, improved physiological parameters, increased milk yield by 53%, lowered oxidative stress, and enhanced milk quality ( p < 0.05). The study presents the first transcriptional analysis of stress-responsive energy-regulating genes in buffalo, revealing higher AMPK , HRH1 , and mTOR expression in HS-Model I buffalo, which reflects the metabolic strain associated with unmanaged thermal stress. Regression analysis showed that for every one-unit increase in THI above 69, milk yield decreased by 0.17–0.23 kg/day. These findings underscore the value of integrated biostatistical modeling and targeted adaptation strategies for sustaining buffalo productivity under the pressures of subtropical climates. Adaptive housing, nutritional support, and management interventions effectively mitigate the impacts of HS. At the molecular level, evidence of oxidative stress and altered energy regulation highlights the physiological toll of thermal load, emphasizing the need for holistic approaches to protect productivity and herd resilience in heat-stressed regions.

Effect of stinging nettle powder (Urtica dioica) supplementation on productive and physiological performance of laying hens - Magdy Sayed Hassan Hassan; Inas Ibrahim Ismail; Ahmed Mohamed Dief Youssef; Ahmed M. Hussein; Nahla A. Elrazik; Ibrahim Abd El hamed Fathy; EIham Salah Mohamed Ahmed; Waleed Sobhy El Saqa; José del Carmen Rodríguez-Castillo; Mona M. M. Y. Elghandour (Tropical Animal Health and Production, 2026)

The potential role of adenosinergic pathway and methylxanthines in Parkinson’s disease: Blowing in the wind or not - Alaa Ismail; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Luay M. Alkazmi; Abdullah Faisal Albukhari; Mustafa M. Shokr; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Purinergic Signalling, 2026)

Interlayer Slip Mechanisms in Bentonite and Their Influence on Mechanical and Swelling Behavior - Hemin Liu; M. A. M. Ismail; Jianwen Zhang (Geotechnical and Geological Engineering, 2026)

Agrobacterium-mediated transformation of Chlamydomonas reinhardtii to produce recombinant human serum albumin - Pratheesh Prakasam Thanka; Vineetha Mohan; Muraleedhara Kurup; Menatalla M. Ismail; Mallik Sudhanshu; Abdel-Hamid I. Mourad (Algal Research, 2026)

Harnessing bacterial power and omics technologies for sustainable plastic waste biodegradation - Ahmed R. Henawy; Salma M. Ismail; Sama Gharib; Nagwa I. Elarabi; Abdelhadi A. Abdelhadi; Asmaa A. Halema (Biodegradation, 2026)
Plastic pollution constitutes a critical environmental concern of this era, with synthetic polymers, i.e., polyethylene (PE), polyethylene terephthalate (PET), polystyrene (PS), and polyurethane (PU), accumulating in terrestrial and aquatic ecosystems at alarming rates. One of the promising solutions to this worldwide problem is microbial plastic degradation, particularly by bacteria that can convert polymeric materials into less toxic compounds. With an emphasis on enzymatic mechanisms, critical environmental and biochemical factors influencing degradation, and the wide variety of bacteria responsible for breaking down synthetic polymers, this review focuses on the enzymatic and genetic aspects underlying bacterial plastic degradation, highlighting key enzymes such as PETase, METase, esterase, and oxidoreductase, as well as representative plastic-degrading bacteria i.e . Thermobifida, Ideonella, Bacillus, Agromyces, Pseudomonas, Schlegelella species. The significance of multi-omics tools, such as transcriptomics, proteomics, metabolomics, and genomics was demonstrated here in deepening our understanding of microbial plastic degradation without depending on pure culture. It explores the key genes and metabolic pathways that facilitate this process. Moreover, how advanced biotechnological techniques and artificial intelligence (AI) can participate in plastic biodegradation through enzyme engineering, activity-enhancing mutation design, predictive modeling, and omics data analysis was illustrated. Furthermore, this review underscores the necessity for integrative and interdisciplinary approaches to effectively harness bacterial metabolism for long-term reduction of plastic pollution. Also, it outlines future research directions and technological priorities for translating bacterial plastic degradation into practical and sustainable remediation solutions.

Molecular crosstalk between plant defense hormones and reactive oxygen species during fungal infection: Insights into integrated resistance mechanisms - Mohamed M. El-Mogy; Amira A. Ibrahim; Sameh A. Hussein; Hossam S. El-Beltagi; Ahmed M. Ismail; Mohamed Abdel-Haleem (Physiological and Molecular Plant Pathology, 2026)

Thermally activated recycled pottery waste as a porous aluminosilicate sorbent for efficient Uranium(VI) removal from aqueous systems - Amir A. Elzoghby; Hager Fahmy; Osama E. Roshdy; Ahmed M. Masoud; Ahmed M. Ismail; Mohamed H. Taha; Saber Ibrahim (Journal of Environmental Radioactivity, 2026)

Integrating hydrogeochemical analysis and machine learning to assess surface–groundwater interactions in an arid basin (Middle Egypt) - Ahmed A. Abdelhady; Mamdouh S. Morsi; Nouria E.A. Aboshaala; Mahmoud M. Khalil; Hadi M. Elshourbagi; Esam Ismail; Esam El Sayed; Ashraf M.T. Elewa; Emad Youssef; Basma A.A. Balboul (Journal of African Earth Sciences, 2026)

Exploring the gastronomic and functional potential of sycamore fig (Ficus sycomorus) fruit powder in bio-fermented camel–corn milk - Tawfiq Alsulami; Wael F. Elkot; Hesham A. Ismail; Mohamed S. Mostafa; Said Elshahat Abdallah; Hadeer Lotfy Abu-Taha; Suleiman A. Althawab; Basim M. Alohali; Ammar Al-Farga; Ahmed Elmahdy (International Journal of Gastronomy and Food Science, 2026)

State-of-the-art modification, mechanistic insight and breakthrough curve analysis of chitosan scaffolds for sustainable heavy metal adsorbent - A. Zubir; E. Normaya; W. Hazman Danial; P. Sean Goh; M. Bijarimi Mat Piah; P.-L. Show; A. Fauzi Ismail; M. Norazmi Ahmad (International Journal of Environmental Science and Technology, 2026)
Heavy metals are toxic, non-biodegradable pollutants that can persist in the environment and pose serious threats to human health and aquatic ecosystems. Industrial discharge of heavy metal-containing effluents continues to degrade water quality, highlighting the urgent need for effective and sustainable remediation methods. Among various techniques, adsorption stands out for its high efficiency, low cost, and reusability. Chitosan, a biopolymer derived from renewable and abundant sources, has gained significant attention as a promising biosorbent for heavy metal removal. However, its poor acid stability and limited number of active adsorption sites can hinder its performance. This review discusses recent advancements aimed at enhancing chitosan’s adsorption capacity and stability, focusing on three main strategies: (i) structural modification via crosslinking and grafting, (ii) selectivity improvement using the Hard and Soft Acid–Base (HSAB) theory, and (iii) optimization of operational parameters such as pH, contact time, and metal ion concentration. In addition, the adsorption mechanisms, including complexation, electrostatic interactions, and ion exchange, along with breakthrough curve analysis are explored to understand dynamic adsorption behavior. Importantly, this study also covers regeneration techniques, evaluating the reusability of modified chitosan across multiple cycles, cost analysis to assess economic feasibility, and findings from pilot-scale studies that demonstrate real-world applicability. Overall, this review provides a comprehensive guide for the development of efficient, cost-effective, and scalable chitosan-based adsorbents, contributing to the advancement of sustainable heavy metal remediation technologies. Graphical Abstract

Technological trends in rainwater harvesting for micro-hydropower: a scientometric review - S. N. F. Abdullah; M. K. A. Kamarudin; N. A. Wahab; N. Yaakub; A. S. Mohd Saudi; M. N. A. Rahman; S. Sunardi; F. Muhammad-Sukki; I. N. Ismail (International Journal of Energy and Water Resources, 2026)

Integrating NMR T2 distributions, CPI interpretations, and core data to evaluate the Mishrif reservoir in the X oilfield: a case study from Southern Iraq - H. A. Chafeet; M. J. Ismail; A. A. Lazim (Carbonates and Evaporites, 2026)

Isolation, Identification, and Pathogenicity of Entomopathogenic Fungal Strains and Their Secondary Metabolites Against Spodoptera frugiperda (Lepidoptera: Noctuidae) - Fatmaalzahraa A. Senousy; El Arnaouty S.A; Mona N. Kortam; Ismail M. Ismail; Mona Awad; Marwa A. Zayton (Neotropical Entomology, 2026)
The fall aِrmyworm, Spodoptera frugiperda (J.E. Smith), causes significant yield losses due to its high fecundity, broad host range, defoliation capability, and voracious larval feeding. Biological control using microorganisms has gained attention as a sustainable alternative to chemical pest management. Entomopathogenic fungi employ distinct modes of action and produce secondary metabolites with insecticidal properties. This study aimed to isolate and identify indigenous entomopathogenic fungal species and evaluate their pathogenicity against S. frugiperda . Three isolates belonging to the division Ascomycota were recovered from soil samples and identified as Botryotrichum domesticum isolate MP3H-5, Albifimbria verrucaria isolate E16, and Purpureocillium lilacinum isolate WARSO2 6 8. When applied at a concentration of 1 × 10 9 conidia mL⁻ 1 , the fungal isolates induced significant cumulative mortality (60 to 84.44%) in S. frugiperda larvae at 14 days post-treatment. Albifimbria verrucaria was the most virulent, exhibiting the lowest LC 50 (2 × 10 7 conidia mL⁻ 1 ) and LT 50 (0.46 days). At a lower concentration of 1 × 10 7 conidia mL⁻ 1 , the P. lilacinum isolate caused the highest pupal mortality (80%) at 7 days post-treatment. Crude fungal metabolites also demonstrated larvicidal activity, resulting in cumulative mortality rates of up to 50%. Furthermore, larvae treated with the entomopathogenic fungi showed elevated catalase activity. The high toxicity observed is likely associated with fungal secondary metabolites, which were characterized using GC-MS analysis. Under laboratory conditions, the tested entomopathogenic fungal isolates demonstrated strong potential as microbial agents for the control of S. frugiperda . However, further field-based validation is necessary to confirm their efficacy.

Ultrasonic irradiation for ZnO NPs Synthesis and their hepatoprotective effect against acetaminophen induced hepatic toxicity in albino rats: Biochemical, physiological, and histopathological assessments - Yasmine A. Mansour; Fady Sayed Youssef; Shaymaa Hussein; Hanan F. AbdEl_Halim; Sameh H. Ismail; Gehad G. Mohamed; Abdelfattah M. Abdelfattah; Rasha M.M. Ezz-Eldin; Heba H. Mahboub; Sherin Ibrahim (Tissue and Cell, 2026)

Synchronous natural infection of Nile tilapia (Oreochromis niloticus) by drug-resistant Pseudomonas aeruginosa and Saprolegnia parasitica: insights into water quality, phenotypic traits, and genotypic profiles - Reham M. El‑Tarabili; Mahmoud E. Elsayed; Hanan S. Khalefa; Hanan Elghayaty; Zainab Mohamed El Kattawy; Mohamed Marzok; Sherief M. Abdel-Raheem; Hesham L. Ismail; Dalia A. Abdel-moneam (Veterinary Research Communications, 2026)

Maternal high-fat diet and its multigenerational impact on hypertension and metabolic alterations in Wistar rat offspring - Maghawry Hegazy; Mahmoud Mohamed Mokhtar; Elsayed G. E. Elsakka; Hesham A. El-Mahdy; Samy Y. Elkhawaga; Mohamed A. Elkady; Amr Mohamed Yehia; Ahmed Aglan; Ahmed M. Mansour; Salama Abdo Salama; Hamada Ahmed Mokhlis; Hesham Fathy Hassan; et al. (Journal of Molecular Histology, 2026)

Renoprotective effect of diosmin against chlorpyrifos-induced kidney injury is mediated by the regulation of TLR4/HMGB1/NF-κB, PPAR-γ/SIRT1, and Bax/Bcl2 signals - Duaa Althumairy; Mohammad Bani Ismail; Hamad Abu Zahra; Badrah S. Alghamdi; Hanan S. Althagafy; Zainab Mohammed Mahmoud Omar; Emad H. M. Hassanein; Fares E. M. Ali (Journal of Molecular Histology, 2026)

Correction: Biodegradation of ketoprofen using a microalgal–bacterial consortium - Maha M. Ismail; Tamer M. Essam; Yasser M. Ragab; Fathia E. Mourad (Biotechnology Letters, 2026)

Protective Effect of S-Methylcysteine Against Toxoplasma gondii-Induced Reproductive Toxicity in Female Albino Rats - Nermeen I. Ashry; Dina M. M. EL Shewehy; Dina A. Elbadry; Amira Ismail (Acta Parasitologica, 2026)
Background Toxoplasma gondii ( T. gondii ) is a zoonotic parasite that causes severe disease, particularly in immunocompromised individuals. Current treatments have significant side effects and are ineffective against the latent stage of the parasite. S-Methylcysteine (SMC), a compound from garlic, has antioxidant and anti-inflammatory properties, but its efficacy against T. gondii is unknown. Objective To evaluate the in vivo effects of SMC on T. gondii infection, focusing on hormonal and histopathological changes and its therapeutic potential. Materials and Methods Forty-eight adult female albino rats were divided into eight groups of six. Four groups were infected intra-vaginally with 200 T. gondii cysts, while controls received saline. For two months, treatment groups were administered daily doses of SMC (50 mg/kg), Spiramycin (200 mg/kg), or a combination of both via gastric tube. After sacrifice, blood samples were collected for hormonal analysis (estrogen, progesterone, LH, FSH). The ovaries and uterus were excised and histologically examined using hematoxylin and eosin staining for microscopic evaluation. Results Toxoplasma gondii infection caused significant hormonal disruption and severe uterine and ovarian inflammation. Treatment with either SP or SMC alone partially mitigated these effects. However, the combined SMC and Spiramycin treatment showed the most significant improvement, significantly mitigated hormonal imbalances and promoted substantial tissue recovery. Conclusion S-Methylcysteine shows promising therapeutic potential in ameliorating the hormonal and histopathological damage associated with T. gondii infection, especially when combined with Spiramycin. Future studies, including human clinical trials, are needed to investigate its mechanisms and confirm its safety and effectiveness.

Arbuscular mycorrhizal fungi confers resistance to Macrophomina phaseolina in coriander under different nitrogen fertilizer rates - Marzouk R. Abdel-Latif; Abdelrazek S. Abdelrhim; Ranya M. S. El-Ashmony; Yasmin M. R. Abdellatif; Hanaa A. H. Armanious; Ismail A. A. Tantawy; Mahmoud Elsayed; Abeer S. Alqurashi; Hatim M. Al-Yasi; Esmat F. Ali; Abdelmonim Ali Ahmad (Journal of Plant Pathology, 2026)

Actinomycetes in the spotlight: biodiversity and their role in bioremediation - Hagar S. Hashim; Mazen M. Zayan; Ahlam A. Mohamed; Hend Ismail Abd El rahman Abulila (World Journal of Microbiology and Biotechnology, 2026)

Remediation of per- and polyfluoroalkyl substances (PFAS): A critical review of graphene-based photocatalysis as a sustainable solution - M. Rahnuma Iqbal Ifte; M. Kaisher Ahmed; M. Kamrul Hossain; M. Rezaur Rahman; Ismail Rahman; Faisal I. Chowdhury (Journal of Water Process Engineering, 2026)

Tracing surface-adhered and internalized microplastics in leafy vegetables across urban and rural agroecosystems: Occurrence, characteristics, pollution indices, and exposure assessment - Ismail M. Rahman; Gopal Chandra Ghosh; Sadia Sultana Mitu; Mahfuz Ahmmed; Md Hasibuzzaman; Danisha Sultana; Jarin Tasnim Asha; Sojib Islam; Md. Tauhiduzzaman; Tapos Kumar Chakraborty; Samina Zaman; Seiya Hanamoto; et al. (Journal of Hazardous Materials, 2026)

Triphenylene-based porous polymer for selective CO2 capture with molecular modeling insights and CO2/N2 separation performance indicators for vacuum swing adsorption - Mosim Ansari; Ismail Abdulazeez; Abuzar Khan; Aasif Helal; M. Nasiruzzaman Shaikh; Fares Ahmed Turkestani; Mohd Yusuf Khan (Chemical Engineering Journal, 2026)

Genetic and phenotypic associations between peduncle characteristics and spike productivity in wheat under drought and normal conditions - Ahmed Sallam; Mostafa Hashem; Asmaa A. M. Ahmed; Saleh M. Ismail; P. Stephen Baenziger; Andreas Börner (Theoretical and Applied Genetics, 2026)
The peduncle stem plays an essential role in resource allocation and water transport to spike grains under normal conditions. Therefore, exploring peduncle traits and their relationships with spike production under drought stress may provide insights into the mechanisms that mitigate the effects of drought stress on grain yield in wheat. To address this challenge, a panel of 198 highly homozygous and diverse spring wheat varieties was evaluated under normal and drought conditions across two growing seasons. Peduncle traits, namely, length (PL), diameter (PD), and weight (PW), as well as spike traits, namely, spike length (SPL), number of spikelets/spike (NSPS), grain number/spike (GNPS), and grain yield per spike (GYPS), and thousand-kernel weight (TKW), were assessed. We revealed that PW and PD, unlike PL, were significantly and strongly associated with spike traits and grain weight under both conditions. Genome-wide association study (GWAS) revealed that spike and peduncle traits were controlled by different genetic mechanisms, as no stable markers were shared between these two groups. Distinct SNPs found between genotypes with contrasting peduncle traits led to the identification of a key SNP marker in a gene model encoding a protein highly expressed in the peduncle and spike of wheat. Comparing cultivars with low peduncle trait values to cultivars with high peduncle trait values, particularly PW and PD, high peduncle trait cultivars had greater yield-related trait values under both drought and normal conditions. The results of this study shed light on the importance of peduncle traits in enhancing wheat spike productivity under normal and drought stress conditions.

Unveiling the Neuroprotective Effect of Paraoxonase 1 in Neurodegenerative Diseases Focusing on Alzheimer’s Disease - Alaa Ismail; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Gaber El-Saber Batiha (Molecular Neurobiology, 2026)

Integrative network pharmacology and experimental validation of rubus ulmifolius leaf extract in a rat model of MRSA-infected wounds - Essam M Alharshani; Seham S. El-Hawary; Mohamed F. Abdelhameed; Shaymaa Abdalla Ismail; Farid N. Kirol-los; Essam M Abdelkader; Mohamed A. Rabeh; Saad A. Alshehri; Mohamed A. El Raey; E. M. Al; S. A. I (Inflammopharmacology, 2026)

Assessing trace metal based human health risks in the highly consumed vegetables collected from the industrialized zones of Bangladesh - Ummeh Sadia; Md. Nazrul Islam; Md. Ashraful Hoque; Taznova Anwar Tanbi; S. M. Ashraful Abedin Asha; Sabbir Howlader; Nobonita Sarker; Shahidul Islam; Ismail Rahman; Amitava Bandyopadhyay; Sumon Ganguli (Environmental Geochemistry and Health, 2026)

Radiolabelling and bioequivalence of modified Tamoxifen solid lipid nanoparticles as a targeted chemotherapeutic drug - Rania S. Abdel-Rashid; Eman S. El-leithy; Ismail T. Ibrahim; Khaled M. Attallah (Drug Delivery and Translational Research, 2026)
There are several types of breast cancer where the breast's cells proliferate uncontrollably. A selective oestrogen receptor modulator called Tamoxifen citrate (TAM) is used to treat and prevent breast cancer in both men and women. TAM is classified as class II under the biopharmaceutical categorization system (BCS) of medications. It exhibits low plasma levels, which can result in therapeutic failure due to its poor water solubility. To improve its chemotherapeutic efficiency and drug targeting, nanotechnology was exploited. In this article, TAM-loaded SLNs were prepared, characterized, and radiolabelled with Technetium-99m ([ 99m Tc]Tc) using stannous salts followed by the assessment of their radiochemical efficiency and in vivo biodistribution compared to the radiolabelled free TAM ([ 99m Tc]Tc-TAM). The results showed that the concentration of lipid had a highly prominent effect on the particle size and encapsulation efficiency of the drug, where the best selected formula showed spherical, non-aggregated morphology with a 134.6 ± 0.3 nm size and 83.9 ± 2.5% drug encapsulation. The radiolabelling purity was more than 97.4%, and it was stable for at least 6 h. In solid tumor-bearing mice, [ 99m Tc]Tc-TAM-SLNs exhibited around 3 times more uptake than [ 99m Tc]Tc-TAM solution. Accordingly, [ 99m Tc]Tc-TAM-SLNs can be suggested as a useful targeted delivery strategy for chemotherapy drugs. Graphical Abstract

Assessing heavy metals toxicity in marine bed sediments of the Bay of Bengal: A novel baseline study on geochemical speciation, source, and risks - Md. Saiful Islam; Nor Aida Mahiddin; Debolina Halder Hemy; Abdullah Al Bakky; Uttam Biswas Antu; Zulhilmi Ismail; Nusrath Jahan Dristy; Tusar Kanti Roy; Mahmudul Hasan; Khalid A. Ibrahim; Abubakr M. Idris (Marine Pollution Bulletin, 2025)

Simulation-based multi-objective optimization for mission specific tuning of swarming robots - Reda Ghanem; Ismail M. Ali; Kathryn Kasmarik; Matthew Garratt (Swarm and Evolutionary Computation, 2025)

A critical review of per- and polyfluoroalkyl substances (PFAS) in wastewater biosolids and sludge - Usman M. Ismail; Chedly Tizaoui (Journal of Environmental Chemical Engineering, 2025)

Potentials of energy-active windows with integrated airflow geometries for improved thermal comfort and energy efficiency - Syed Y. Mahdi; Mohammed Alhaji Mohammed; Ismail M. Budaiwi; Adel A. Abdou (Energy and Buildings, 2025)

Full scale performance evaluation of a partial-depth floating fish guidance bar rack - Halvor Kjærås; Henrik Baktoft; Ana T. Silva; Karl Øystein Gjelland; Finn Økland; Mohammadreza Maddahi; Ismail Albayrak; Leif Lia; Robert M. Boes; Torbjørn Forseth (Ecological Engineering, 2025)

Synthesis, characterization, and applications of chitosan-isatin Schiff base tethered N-(4-methoxyphenyl)acetamide: Adsorption, docking, antioxidant, and antibacterial properties - Ahmed M. Elgamal; Mostafa E. Salem; Amira A. Hamed; Ismail A. Abdelhamid; Tayseer A. Abdallah; Hossameldin A. Ali; Nadeem Raza; Mohamed A. Ragheb (Carbohydrate Polymers, 2025)

Potential use of titanium nano-gel to palliate redox status, DNA damage, histopathological changes, and renal-hepatic disorders induced by Candida albicans in Clarias gariepinus - Randa Y. Thabet; Abdallah Tageldein Mansour; Heba H. Mahboub; Yousef Alkhamis; Hesham A. Hassanien; Ahmed Abbas; Adnan Alhaje; Sameh H. Ismail; Afaf N. Abdel Rahman; Heba Allah M. Elbaghdady (Veterinary Research Communications, 2025)

Protective Role of Nano-encapsulated Bifidobacterium breve, Bacilllus coagulans, and Lactobacillus plantarum in Colitis Model: Insights Toward Propagation of Short-Chain Fatty Acids and Reduction of Exaggerated Inflammatory and Oxidative Response - Doaa Ibrahim; Safaa I. Khater; Hoda S. Sherkawy; Aya Elgamal; Asmaa A. Hasan; Asmaa A. Muhammed; Mohamed F. M. Farag; Samar A. Eissa; Tamer Ahmed Ismail; Hemmat M. Eissa; Areej A. Eskandrani; Wafa S. Alansari; et al. (Probiotics and Antimicrobial Proteins, 2025)

Molecular characterization and cuticular stomatal anatomy of Punica Granatum L. cultivars study in Dohuk governorate - Dalal Y. Kh. Sinjare; Shamiran S. Abdulrahman; Nizek S. Khalid; Rizgar Y. Ismail; Muhammad Yasir Naeem; Zeliha Selamoglu; Gani Issayev; Aveen M. N. Ahmed (Molecular Biology Reports, 2025)

Interconnection between myasthenia gravis and type 2 diabetes: emerging role of metformin in modulating PI3K/AKT/mTOR/AMPK axis - Ahmed salem Al-Dhahi; Hayder M. Al-Kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Aya M. Mustafa; Alaa Ismail; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Metabolic Brain Disease, 2025)

Efficient removal of MB dye from wastewater via cadmium ferrite nanocomposites - A. H. Abdalsalam; S. M. Alardhi; A. A. Ati; S. Bassim; R. A. Ismail; S. S. Shaker; S. Dabagh (International Journal of Environmental Science and Technology, 2025)

Green Synthesis of Platinum Nanoparticles Using Aqueous Broccoli Extract for Antimicrobial, Antioxidant, Wound Healing, Antidiabetic, and Anticancer Applications - Yasser M. Taay; Mustafa Taha Mohammed; Ali Hussain Alwan; Ahmad Hussein Ismail (Cell Biochemistry and Biophysics, 2025)

Characterizing Tropical Cyclone from Altimeter Wind Speed Profile - Nik Raisyha Nurfarain Abdullah; Syarawi M. H. Sharoni; Mohd Nadzri Md Reba; Hwee San Lim; Nurul Najwa Ayob; Ismail Ahmad Abir; Muhammad Zahir Ramli (Marine Geodesy, 2025)

Origin and processes of groundwater salinity hotspots in the irrigated Sahara Desert lands of Egypt - Mahmoud M. Khalil; Mohamed H. Farag; Tomochika Tokunaga; Thomas Pichler; Esam Ismail; Abotalib Z. Abotalib (Groundwater for Sustainable Development, 2025)

Hydrogen storage in MgH2 catalyzed by Fe nanoparticles and hollow silica spheres - Mohammed Faraj Saeid; B.A. Abdulkadir; M. Ismail; H.D. Setiabudi (Fuel, 2025)

Facile synthesis of Se-decorated titanium carbide/titanium oxide nanocomposite (Se-TiC/TiO2) for overall water-splitting in an alkaline medium - Saira Sardar; Samon Nazeer; Faisal Naeem; Sana Ben Khalifa; Saleh Chebaane; Taoufik Saidani; Mostafa A. Ismail; M. Abdul (Fuel, 2025)

Effect of using kiwi fruit and heart of date palm slurries as a novel acceleration ripening enzyme source on the physicochemical, textural, and sensorial properties of Ras cheese - Wael F. Elkot; Tawfiq Alsulami; Rafik A.M. Khalil; Ahmed Elmahdy; Suleiman A. Althawab; Basim M. Alohali; Ammar Al-Farga; Hadeer Lotfy Abu-Taha; Hesham A. Ismail (Food Chemistry, 2025)

Building-integrated photovoltaics (BIPV) in Saudi Arabia for sustainable energy transition: A comprehensive review of status, challenges, and future prospects - Abdultawab M. Qahtan; Nedhal Al-Tamimi; Ismail Baklouti; Yakubu Aminu Dodo; Shukri Elbellahy (Energy and Buildings, 2025)

Sex- and age-related differences in thermal sensitivity to radiant cooling in sleeping pods - Omar A. Ismail; Sally Hussain; Ahmed M. Ali; Mohamed W. Tawfik; Federica Fiacco; Muhammed A. Hassan; Mohamad T. Araji (Energy and Buildings, 2025)

Nutritional composition, phytochemical profile, HPLC analysis, and antioxidant activity of leaf and flower extracts of Rumex nervosus from Yemen - Muneer Mohammed Saleh Alsayadi; Mufeda Ahmed Hazea Gazaem; Sharifah Aminah Syed Mohamad; Nor Hadiani Ismail; Mohammed A.A. Alshoaiby; Hasan M. Agha; Abdulmutalib Alabeed Alkamil; Mustapha Salihu; Fatimah Salim (Biocatalysis and Agricultural Biotechnology, 2025)

Lavender cotton ( Achillea fragrantissima (Forssk.) Sch.Bip. (Asteraceae)), a common herbal tea and food additives in Middle East: variation of volatiles and chemical profiling - Arbi Guetat; Abdelrhman T. Abdelwahab; Marwa A. Abdelfattah; Abd Ealrhman M. Elhaj; Roaa T. Mogharbel; M. J. A. Abualreish; Abdullah F. Alanazi; Abdennacer Boulila; Ismail M. A. Shahhat (Natural Product Research, 2025)

The protective effect of Adansonia digitata fruit extract against severe heat stress on growth performance, feed efficiency, and health status of fattened rabbits - Rehab F. S. A. Ismail; Mahmoud A. E. Hassan; Sahar R. M. Hammoudah; Mona A. Ragab; Abdelhamid M. Abdelhamid; Alaa M. A. Gad (Tropical Animal Health and Production, 2025)

Chromium reduction by indigenous Bacillus sp. isolate S1: optimal performance, characterization, and pathway - N. N. Ramli; A. R. Othman; N. S. M. Said; J. Alias; S. R. S. Abdullah; H. A. Hasan; N. ‘I. Ismail; S. B. Kurniawan (International Journal of Environmental Science and Technology, 2025)

Innovative approach for modeling the mechanical properties of the concrete modified with recycled aggregate for various curing times and mix proportions - Yousif J. Bas; Jamal I. Kakrasul; Kamaran S. Ismail; Samir M. Hamad (Innovative Infrastructure Solutions, 2025)

Comprehensive assessment of marsh soil health index in beel aquaculture systems of coastal Bangladesh - Fariha Farzana; Tusar Kanti Roy; Mir Mohammad Ali; Sk Arafat Hossain; Rituparna Ghosh; Tatia Biswas; Mahjabin Mazrin; Jayosri Roy Jayoti; Bikash Chandra Sarker; Abu Shamim Khan; Md. Tanvir Anjum; Zulhilmi Ismail; et al. (Aquaculture International, 2025)

In silico identification of GTPase inhibitors from selected anti-gonorrheal plants against Neisseria gonorrhoeae - Blessing O. Awoyemi; Badmus Jamiu Damilare; Abdullahi Tunde Aborode; Che Muhammad Khairul Hisyam Ismail; Abdulqohar Adebayo; Haruna Isiyaku Umar; Ibrahim Akindeji Makinde; Ridwan Opeyemi Bello; Sodiq Fakorede; Mohammed M. Alshehri; Ahmed F. Alanazi (The Nucleus, 2025)

Mechanistic insights into cross-modal aroma-taste interactions mediating sweetness perception enhancement in Fu brick tea - Zhihui Hu; Amr M. Bakry; Lin Shi; Ping Zhan; Wanying He; Walaa A.M. Eid; Hussein Ferweez; Yahya S. Hamed; Hesham A. Ismail; Honglei Tian; Peng Wang (Food Chemistry, 2025)

Sustainable waste water purification via integration of novel COF@UiO-66 dual-layer PVDF/PEI hollow fiber membranes - Nethravathi Prabhakar; Arun M. Isloor; Mohd Hafiz Dzarfan Othman; Ahmad Fauzi Ismail (Chemical Engineering Journal, 2025)

Microplastic toxicity in fish: A potential review on sources, impacts, and solution - Md. Towhidul Islam; Uttam Biswas Antu; Md. Shifat Hossain; Joyti Rani Paul; Tahsin Hasan; Pronayan Singha; Sandip Mitra; Sk Md Shoib Hasan; Zulhilmi Ismail; Md. Saiful Islam; Taher Sahlabjii; Abubakr M. Idris (Aquatic Toxicology, 2025)

Correction to: A flavonoid Ombuin ameliorates thioacetamide-mediated liver cirrhosis in vivo: biochemical, immunohistochemical, inflammatory approaches - Khaled Abdul-Aziz Ahmed; Talal Salem Al-Qaisi; Ahmed A.j. Jabbar; Parween Abdul-Samad Ismail; Mohammed M. Hussein M. Raouf; Hanan Ibrahim Althagbi; Bassam Ali Abed Wahab; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Ahmed Hameed Al-Dabhawi; Musher Ismael Saleh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A flavonoid Ombuin ameliorates thioacetamide-mediated liver cirrhosis in vivo: biochemical, immunohistochemical, inflammatory approaches - Khaled Abdul-Aziz Ahmed; Talal Salem Al-Qaisi; Ahmed A.j. Jabbar; Parween Abdul-Samad Ismail; Mohammed M. Hussein M. Raouf; Hanan Ibrahim Althagbi; Bassam Ali Abed Wahab; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Ahmed Hameed Al-Dabhawi; Musher Ismael Saleh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Grosvenorine (Monk Fruit flavonoid) Attenuates Indomethacin-mediated Gastropathy in Vivo: Role of P53/Bcl-2, Antioxidant, and Inflammatory Mediators - Khaled Abdul-Aziz Ahmed; Khalid M. Alqaisi; Ahmed A.j. Jabbar; Parween Abdulsamad Ismail; Noralhuda Ayad Ibrahim; Hanan Ibrahim Althagbi; Rawaz Rizgar Hassan; Muzhda Haydar Saber; Goran Noori Saleh; Musher Ismail saleh; Talal Salem Alqaisi; Ahmed Hameed Al-Dabhawi (Journal of Pharmaceutical Innovation, 2025)

Coenzyme Q10 may protect ovarian tissue against by the nearly century-old drug methotrexate caused gonadotoxicity: a biochemical, flow cytometric, and histopathological study - Zuleyha Erisgin; Hasan Serdar Mutlu; İsmail Turkoglu; Esma Cinar; M. Zuhal Barak; Ismail Aydin; Murat Usta; Yavuz Tekelioglu (Journal of Molecular Histology, 2025)

Biorefinery practice for valorizing Mediterranean bloomed Pterocladia capillacea into valued and sustainable bioproducts with numerous green solicitations - N. Sh. El-Gendy; H. N. Nassar; A. R. Ismail; H. R. Ali; B. A. Ali; K. M. Abdelsalam; M. Mubarak (International Journal of Environmental Science and Technology, 2025)
As a solution for ecosystem bioremediation from the gigantic red seaweed proliferation across the Mediterranean shorelines, this work investigates the effective utilization of Pterocladia capillacea to produce different esteemed and viable bioproducts. The nutritional composition of approximately 6.88 ± 0.31%, 20.15 ± 0.2%, 42.16 ± 0.3%, and 2.51 ± 0.05% (w:w) protein, fiber, carbohydrate, and lipid, respectively, promotes its application in the human food and animal fodder industries. Its N + P 2 O 5 + K 2 O, undesirable heavy metals, organic carbon, and organic matter contents of 5.48 ± 0.07%, 2.82 ± 0.15 mg/kg, 16.11 ± 0.15%, and 27.71 ± 0.26% are all within the ranges allowed by the Egyptian standard for organic fertilizer. Its calorific value of 16.16 ± 0.5 MJ/kg and relatively low ash and heavy metals contents are in accordance with the international standards for primary solid biofuel. Its relatively high holocellulose content of 44 ± 0.5% (w/w) recommends its applicability in the liquid biofuels sector. Further, via a pioneering practice, a sequential, eco-friendly, and fully integrated bioprocess Pt. capillacea biomass is valorized into natural pigments of approximately 5.05 ± 0.05 mg/g total chlorophyll, 2.12 ± 0.05 mg/g carotenoids, phycobiliproteins of approximately 1.33 ± 0.05 mg/g phycocyanin, 3.07 ± 0.05 mg/g allophycocyanin, and 0.97 ± 0.05 mg/g phycoerythrin, hydrocolloids of approximately 28.21 ± 2.5% carrageenan and 20.46 ± 1.5% agar, and finally cellulose of approximately 20.15 ± 1.5%. Additionally, the extracted carrageenan proved an efficient antimicrobial action against pathogenic microorganisms that supports its use for water densification, food packing, and wound dressing.

Pyramiding of disease resistant and heat shock protein genes of chili revealed through tightly linked SSRs for sustainable yield under biotic and abiotic stresses - Mst. Farhana Nazneen Chowdhury; Mohd Y. Rafii; Siti Izera Ismail; Shairul Izan Ramlee; Monir Hosen; M. A. Haque (Euphytica, 2025)

Bioprotective potential of biosynthesized copper oxide nanoparticles and copper phosphite against Alternaria-solani-induced leaf spot in pepper plants - Mohamed S. Attia; Mohamed H. Moustafa; Amr H. Hashem; Salah M. Elsayed; Abeer S. Aloufi; Ismail Mostafa Ismail Abdelaleem; Karim A. Alshahed; Abdelrhman S. Ismail; Abdelrhman M. Ibrahim; Mostafa A. Abdel-Maksoud; Abdulaziz Alamri; Hossam Ebaid; et al. (Antonie van Leeuwenhoek, 2025)

Prevalence and Risk Factor Analysis of Bovine Trypanosoma Infection in Cattle across Three Egyptian Governorates - Abdelfattah Selim; Mohamed Marzok; Hattan S. Gattan; Mohammed H. Alruhaili; Hesham Ismail; Abdelrahman M. Hereba (Acta Parasitologica, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Umbelliferone reverses neuronal damage induced by chronic Chlorpyrifos exposure via suppressing NF-κB/STAT3/NLRP3 and boosting Keap-1/Nrf2/HO-1 signals - Salwa Fares Ahmed; Tarek Hamdy Abd-Elhamid; Sarah Abdulaziz Alamer; Mohammad Bani ismail; Fares E. M. Ali; Emad H. M. Hassanein; Hanan S. Althagafy; Amany Refaat Mahmoud (Metabolic Brain Disease, 2025)

Multicompartmental monitoring and associated health risks estimation of some selected pesticides in the aquatic ecosystems of Sungai Besar, Sekinchan, Malaysia - Md Ariful Islam; S. M. Nurul Amin; Dania Aziz; Mohd Fadhil Syukri Ismail; Christopher L. Brown; Abdul Shukor Juraimi; Md Abdul Halim; Md Kamal Uddin; Yahia Mahmud; Md Lifat Rahi; Aziz Arshad (Environmental Science and Pollution Research, 2025)

Assessing Heavy Metals using ICP-MS in Fruits from the Developing World and their Associated Health Risks - Tusar Kanti Roy; Sk Arafat Hossain; Md. Saiful Islam; Md. Fuad Hasan; Mahjabin Mazrin; Bikash Chandra Sarker; Zulhilmi Ismail; Khalid A. Ibrahim; Abubakr M. Idris (Biological Trace Element Research, 2025)

Evaluation of methanolic extracts from five important medicinal plants: Phytochemical profiling, antioxidant capacity, in vitro antidiabetic activity, and cytotoxicity assay - Md. Shakil Ahmed; Md. Taohid Hasan; Reaz Ahmmed; Md. Bismillah; M. Matiar Rahman; Mohammad Ismail Hossain; Masudul Hasan Khan; Mohammad Amirul Islam (South African Journal of Botany, 2025)

Investigation of anti-inflammatory activity and metabolomic profiling of two varieties of Taxodium distichum (L.) Rich (bald cypress) using UPLC/MS/MS coupled to multivariate analysis: molecular docking, and molecular dynamic studies - Dina A. Selim; Hala M. Hammoda; Doaa A. Ghareeb; Heba M. Osama; Fatma A. Abdelrahim; Ismail Celı̇k; Reham S. Darwish (South African Journal of Botany, 2025)

Unveiling chemical profile and health benefits of Launaea intybacea: A study of its anticoagulant, anti-inflammatory, antimicrobial and antioxidant effects: Preliminary study - Mabrouk A. Abo-Zaid; Tawfiq Alfaifi; Mohamed Fawzy Ramadan; Khatib Sayeed Ismail; Abdel-Rahman Mohammed Shater; Ali H. Amin; Maysa M. Hegazy; Ahmed S. Mabrouk; Ahmed H. Ismail (South African Journal of Botany, 2025)

Perichondral telocytes and their role in cartilage development and regeneration: Insights from histochemistry, immunohistochemistry, and TEM - Hanan H. Abd-Elhafeez; Alaa Sayed Abou-Elhamd; Hesham Ismail; Sherief M. Abdel-Raheem; Ahmed M.A. Meligy; Soha A. Soliman (Research in Veterinary Science, 2025)

First-principles study of lead-free Rb2LiTlCl6 double perovskite: Structural, electronic, optical, and mechanical properties - M. Ashraful Hasan; Ismail M.M. Rahman; Mayeen Uddin Khandaker; Pramod K Singh; Faisal Islam Chowdhury (Next Research, 2025)

Guggul gum and clove essential oil synergistically reduced anthracnose disease and modulated physicochemical changes in tomato during storage - Lawang Khan; Ghulam Khaliq; Ehsan Ullah; Adams Abdul-Rahaman; Mohamed M. El-Mogy; Hosny H. Kesba; Ahmed Mahmoud Ismail; Hossam S. El-Beltagi (Journal of Stored Products Research, 2025)

Seismic data interpretation and 3D static reservoir modeling in the Temsah area, eastern offshore Nile Delta, Egypt - Amir Ismail; Hatem E. Semary; Nader A. Edress; Abdelrahman S. Gad; Aicha Hadded; M.A. Abdelkawy; Mahmoud M. Abdelwahab; Mona G. Safa; Amer A. Shehata (Journal of African Earth Sciences, 2025)

Effective separation of agrochemicals and textile dyes from polluted aqueous solution employing ternary ZnCoFe layered double hydroxide incorporated polyethersulfone hollow fiber ultrafiltration membrane - Haritha Pallot; Arun M. Isloor; Ahmad Fauzi Ismail (Chemical Engineering Journal, 2025)

Production of cellulose nanocrystals from the residual mass of P. chaba stem after methanol extraction as potential reinforcement in sustainable nanocomposite manufacturing: A cutting-edge approach in waste management - Md. Elius Hosen Pk; Md. Mahmudur Rahman; Bijoy Chandra Ghos; Nazim Uddin Ahmed; Md. Nakib Hossen; Salah Knani; M. Safiur Rahman; Md. Ismail Hossain (Bioresource Technology Reports, 2025)

Exogenous Application of ZnO Nanoparticles (NPs) To Palliate Salinity Induced Oxidative Stress in Lettuce (Lactuca Sativa L.) Plant - Tusar Kanti Roy; Md. Saiful Islam; Uttam Biswas Antu; Mousumi Jahan Sumi; Israt Jahan Irin; Sk Arafat Hossain; Keya Akter; Mahjabin Mazrin; Nor Aida Mahiddin; Habiba Zannat Meem; Abdullah Al Bakky; Zulhilmi Ismail; et al. (Journal of Soil Science and Plant Nutrition, 2025)

A review on end-of-life waste toner powder: recovery, utilization and upcycling - M. Ismail Shahib; Glen Cletus Dsouza; R.P. Vijayakumar (Waste Management, 2025)

High-resolution sequence stratigraphy and microfacies analysis of the lower part of the Sa'di Formation in selected wells from the West Qurna oilfield, southern Iraq - Maher J. Ismail; Maher M. Mahdi; Frank R. Ettensohn; Rafea A. Abdullah; Amna M. Handhal; Alaa M. Al-Abadi (Journal of African Earth Sciences, 2025)

Evaluation and application of the CROPGRO – Cowpea model for simulating appropriate sowing window and planting density of cowpea varieties across contrasting environments - Alpha Y. Kamara; Reuben Solomon; Abdullahi I. Tofa; Ismail I. Garba; Osagie B. Eseigbe; Jibrin M. Jibrin; Lucky O. Omoigui; Kamaluddin T. Aliyu; Musibau A. Adeleke; Jenneh F. Bebeley; Helen P. Jerome (Field Crops Research, 2025)

Synthesis, cytotoxicity, oxidative stress, anti-metastatic and anti-inflammatory effects of novel 2-methylene-1H-indene-1,3-dione tethered 2-(2-methoxyphenoxy)-N-arylacetamide: induction of apoptosis in HCT116 and HeLa cells - Nada S. Ibrahim; Eman Hatem Shoukry; Marwa Sharaky; Hadeer M. Diab; Ahmed H.M. Elwahy; Ismail A. Abdelhamid (Chemico-Biological Interactions, 2025)

Iron- and Zirconium-Modified Nanocellulose Adsorbent: Broad-Range Selectivity Test for Potentially Toxic Elements and Effective Arsenite Removal - Ratul Kumar Shil; Ismail M. M. Rahman; Yuto Sakai; Moe Marumoto; M. Mehedi Hasan Rocky; Masaru Endo; Kuo H. Wong; Asami S. Mashio; Hiroshi Hasegawa (Water, Air, & Soil Pollution, 2025)

Phytochemistry and therapeutic potential of the genus Asphodelus L.: an update - Lutfun Nahar; Afaf Al Groshi; Lakshmi Thangavelu; Fyaz M. D. Ismail; Andrew R. Evans; Satyajit D. Sarker (Phytochemistry Reviews, 2025)

Neuroprotective Effects of Cucurbita pepo Extract in Cuprizone-Induced Multiple Sclerosis Animal Model - Mohamed Rahamathulla; Rupesh Kumar; Yazan AlRashdan; Madhura M. Bose; Arumugam Muthukumar; Md Salahuddin; Mohammed Muqtader Ahmed; Thippeswamy Boreddy Shivanandappa; Ismail Pasha (Molecular Neurobiology, 2025)

Therapeutic effects of Euphorbia altissima on excisional wound model: role of apoptosis, oxidative stress, and inflammatory molecules - Hanan Ibrahim Althagbi; Khalid M. Alqaisi; Noralhuda Ayad Ibrahim; Parween Abdul-Samad Ismail; Ahmed A. J. Jabbar; Rawaz Rizgar Hassan; Muzhda Haydar Saber; Ahmed Hameed Al-Dabhawi; Goran Noori Saleh; Talal Salem Al-Qaisi (Journal of Molecular Histology, 2025)

Thermo-economic performance augmentation of a three-stage flash distillation unit combined with a parabolic collector: Experimental evaluation - Swellam W. Sharshir; Mamoun M. Elsayad; M. Ismail; A.W. Kandeal; Mohamed Nasser; Areej Al Bahir; N.S. Abd EL-Gawaad; M.O.A. El-Samadony; Zhanhui Yuan (Process Safety and Environmental Protection, 2025)

Thermo-economic and environmental evaluation of thin film evaporation using novel metal-organic frameworks to enhance solar desalination performance - Swellam W. Sharshir; Mohamed R. Abdo; Kareem Yusuf; Ahmed A. El-Naggar; Abanob Joseph; M. Ismail; Ashraf Mimi Elsaid; M.O.A. El-Samadony; Mahmoud Abdelfatah; Abdelhamid El-Shaer; Zhanhui Yuan (Process Safety and Environmental Protection, 2025)

Exploring the impact of bioactive peptides from fermented Milk proteins: A review with emphasis on health implications and artificial intelligence integration - Hosam M. Habib; Rania Ismail; Mahmoud Agami; Ahmed F. El-Yazbi (Food Chemistry, 2025)

Excellent but strange adsorption performance of shrimp shell-derived adsorbent for anionic pollutant removal - Kanokwan Yamsomphong; Hao Xu; Pu Yang; M Ismail Bagus Setyawan; Natnicha Yotpanya; Toshiyuki Yokoi; Fumitake Takahashi (Chemical Engineering Journal, 2025)

Molecular mechanisms of phytoconstituents from selected Egyptian plants against non-small cell lung cancer using integrated in vitro network pharmacology and molecular docking approach - Lamiaa A. Shaala; Diaa T. A. Youssef; Mahmoud A. Ramadan; Azza A. Khalifa; Reham S. Ibrahim; Fred Valeriote; Ismail Celik; Hend M. Dawood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Non-small cell lung cancer (NSCLC) is a widespread highly malignant type of lung cancer. Conventional chemotherapeutic drugs may be accompanied by both drug resistance and serious side effects in patients. Therefore, safer and more effective medications are urgently needed for the treatment of NSCLC. This study investigates the mode of action of 21 phytoconstituents previously isolated from the Amaryllidaceous plants Crinum bulbispermum (Burm.f.), Pancratium maritimum L., and Hippeastrum vittatum Herbert alongside the Asteraceous plant Centaurea scoparia Sieb. for therapy of NSCLC via in vitro cytotoxic, network pharmacology, and molecular docking analyses. Despite the in vitro and in vivo cytotoxic studies carried out on phytoconstituents from these plants in treating numerous cancer types, scarce information documenting their cytotoxic activity towards NSCLC cells is available. First, the compounds were tested for their in vitro cytotoxic activities and selectivity on human non-small cell lung cancer cells using disk diffusion assay. Compounds having significant potencies were promoted for network pharmacology analysis. Pharm mapper, Genecards, STRING, and KEGG databases were utilized for surfing target genes and pathways for these compounds, while for construction of compound-target-pathway (C-T-P) network, Cytoscape 3.7.1. freeware was used. Molecular docking and dynamics simulation were run for the top hit constituents against the most enriched molecular targets followed by in silico ADMET studies using Schrodinger ® suite and Gromacs. In vitro cytotoxicity testing demonstrated that crinamine was the most potent compound followed by lycorine, hemanthidine, and haemanthamine. The network pharmacology approach revealed the enrichment of acetyllycoramine, pluviine, 5-hydroxy-7-methoxy-2-methylchromone, and ismine. Whereas, androgen receptor (AR), epidermal growth factor receptor (EGFR), and estrogen-sensitive receptor alpha (ESR1) were the most enriched target genes. Pathway analysis revealed that central carbon metabolism, EGFR tyrosine kinase inhibitor endocrine resistance, and non-small cell lung cancer were the most enriched cancer-related pathways. Ismine possessed the most stable ligand-protein interactions when docked to the three proteins, with MD simulations further confirming its strong and consistent binding to AR, moderate stability with ESR-1, and lower stability with EGFR over the 100 ns trajectory. ADMET study conducted on the above compounds confirmed their excellent drug-likeness properties, oral bioavailability, and safety profiles highlighting the need for some structural modifications to pluviine to enhance its oral bioavailability. These integrated approaches showed that some constituents from the investigated plants interact synergistically against non-small cell lung cancer-related genes and pathways.

Synthesis and antimicrobial evaluation of a new hybrid bis-cyanoacrylamide-based-piperazine containing sulphamethoxazole moiety against rheumatoid arthritis-associated pathogens - Mona M. Soliman; Ahmed H. M. Elwahy; Ahmed M. Sayed; Mahmoud Ibrahim; Mohamed A. Dawoud; Shahd Hisham Mohamed Ali; Menna Tallah S. Nady; Nada A. Hassan; Wessam Saad; Ismail A. Abdelhamid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Piperazine-based compounds have garnered significant attention due to their notable biological and pharmacological activities, making them essential in fine chemical and pharmaceutical applications. In this study, we managed to synthesize a novel hybrid bis-cyanoacrylamide bearing the piperazine core via phenoxymethyl linker and incorporating sulphamethoxazole moiety. The novel compound was fully characterized using different spectral data including 1H-NMR, 13 C-NMR, and FTIR spectroscopy. Piperazine-based compounds were screened for in silico studies to understand the antimicrobial activity against infections that may contribute to rheumatoid arthritis symptoms. The tested piperazine compound was also evaluated for its antimicrobial activity against Aspergillus niger , Candida albicans , Enterococcus faecalis ATCC 29212, Staphylococcus aureus ATCC 29213, Pseudomonas aeuroginosa ATCC 27853, Escherichia coli ATCC 25922, and Klebsiella pneumoniae ATCC 700603. S. aureus showed the highest inhibition, with a zone diameter of 16.0 ± 1.0 mm at a concentration of 0.8 mg/ml. The minimal inhibitory concentration (MIC) for all bacterial species ranged from 5 to 40 mg/ml. In contrast, fungal species were the most resistant to the tested compound. Molecular docking studies were conducted to elucidate the interaction mechanisms, binding energies, and hydrogen bonding interactions within protein–ligand complexes. Molecular docking studies were performed against five bacterial proteins and two fungal proteins, including DNA gyrase subunit B (UniProt ID: Q839Z1), protein RecA of (UniProt ID: P0A7G6), cyclic AMP-AMP-AMP synthase (UniProt ID: P0DTF7), UDP-N-acetylglucosamine 1-carboxyvinyl transferase (UniProt ID: A0A1S5RKE3), and clumping factor A (UniProt ID: Q53653). The tested compound achieved the highest binding score of ∆G = − 10.9 kcal/mol at the cyclic AMP synthase active site (UniProt ID: P0DTF7), forming 26 interactions. The results demonstrated that the synthesized piperazine compound exhibits promising antibacterial and antifungal activities, highlighting its potential as a candidate for antimicrobial development.

Liraglutide mitigates dexamethasone-induced fatty acid synthase (FASN) and the cluster of differentiation36 (CD36) expression: a potential treatment for glucocorticoid-induced non-alcoholic fatty liver disease (NAFLD) - Dahshan Hassan Selim; Hamada Ahmed Mokhlis; Abdelrahman M. Elsayed; Abdel-Aziz S. Shatat; Salama Abdou Salama; Raed Shahat Ismail (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
The clinical use of dexamethasone (DXM) is associated with the development of non-alcoholic fatty liver disease (NAFLD). However, the mechanisms by which DXM-induced NAFLD is still incompletely known. Therefore, the current study aims to test the hypothesis that DXM-induced NAFLD is mediated by dysregulation of key genes involved in lipid metabolism and liraglutide (LG) can ameliorate these effects. The histopathological and biochemical analysis assessed the effects of DXM and/or LG in liver tissue. The computational analysis was performed to detect the glucocorticoid response elements (GRE) in the promotor regions of FASN and CD36 genes. The effects of DXM and LG on the expression of FASN and CD36 were determined by real-time quantitative reverse transcription PCR (RT-qPCR), western blot (WB) and immunohistochemical (IHC) analyses. The NAFLD induced by high-fat diet (HFD) and DXM was manifested by increased levels of liver enzymes, deterioration of histological architecture of the liver tissue and accumulation of fat droplets. Computational analysis revealed that the promotor regions of FASN and CD36 harper several GRE. Most importantly, treatment with DXM decreased phosphorylated adenosine monophosphate-activated protein kinase (p-AMPK) levels, while LG upregulate it. In addition, treatment with DXM increased expression of FASN and CD36 , whereas LG ameliorated these effects in a dose-dependent manner. DXM-induced NAFLD is mediated by upregulation of FASN and CD36 expression which may be attributed to GRE. LG coupling with DXM mitigates this induction by downregulating FASN and CD36 levels and therefore mitigates the development of NAFLD.

Remote sensing, petrogenesis and tectono-magmatic evolution of the Wadi Queh-Wadi Abu Shigeili area: a window into the transitional history of the central Egyptian-Nubian Shield from pre-plate collision to post-collision magmatism - Osama K. Dessouky; El-Sayed H. El-Sawey; Yasser S. Badr; Sobhi Nasir; Gehad M. Saleh; Ahmed M. Dardier; Kamal A. Ali; Abdel-Rahman Fowler; Saleh E. Ammar; Ahmed M. Ismail; Mahmoud M. Hassan (International Journal of Earth Sciences, 2025)

A baseline toxicity assessment of sediment geochemistry, potentially toxic elements contamination, and ecological risk in sediment profiles of the Bay of Bengal coast, Bangladesh - Md. Saiful Islam; Abdullah Al Bakky; Nor Aida Mahiddin; Md. Towhidul Islam; Uttam Biswas Antu; Zulhilmi Ismail; Tusar Kanti Roy; Mahmudul Hasan; Kazi Aminul Islam; Avijit Sarkar; Khalid A. Ibrahim; Abubakr M. Idris (Regional Studies in Marine Science, 2025)

Efficient removal of hazardous dyes/heavy-metal ions by in-house fabricated poly (vinylidene fluoride) thin-film nanocomposite membranes with functionalized Zr-based metal-organic framework - Nethravathi Prabhakar; Arun M. Isloor; Ramin Farnood; Ahmad Fauzi Ismail (Journal of Environmental Chemical Engineering, 2025)

Green hydrogen-powered air conditioning system for hot climates: Performance and economic analysis - M. Ismail; A.W. Kandeal; Swellam W. Sharshir; N.S. Abd EL-Gawaad; Areej Al Bahir; Mohamed Nasser (Energy and Buildings, 2025)

Genome-wide association study for salinity tolerance in the African rice, Oryza glaberrima - Nafeti Titus Mheni; Newton Kilasi; Atugonza Bilaro; Marie-Noelle Ndjiondjop; Shalabh Dixit; Abdelbagi M. Ismail; Susan Nchimbi Msolla (Euphytica, 2025)

Geochemistry of the U-bearing lithofacies within the major graben in Um Bogma area, Sinai, Egypt: implications for mineralization genesis and controlling factors - Ahmed E. Shata; Alaa Mostafa; Mahmoud M. Nasr; Ahmed M. Ismail; Hesham S. Serag El Din (Carbonates and Evaporites, 2025)

Preliminary Assessment of Essential and Potentially Toxic Elements in the Most Common Spices in a Developing Country: Health Hazard Implication - Md. Saiful Islam; Uttam Biswas Antu; Ruma Akter; Md. Shifat Hossain; Sujat Ahmed; Tusar Kanti Roy; Zulhilmi Ismail; Abubakr M. Idris (Biological Trace Element Research, 2025)

Evaluation of antioxidant potential and active compounds of selected wild plants using four different assays - Mazen M. Zayan; Mohamed K. Hassanien; Omnia A. Salm; Shimaa M. Abdnaiem; Ayman S. Mohamed; Mohamed A. Saeed; Toka M. Elhossiny; Amr M. Abdallah; Lina M. Ismail; Emad A. Shalaby (Food and Humanity, 2025)

Radiation-induced nanogel engineering based on pectin for pH-responsive rutin delivery for cancer treatment - Khaled El-Adl; Mohamed M. Ghobashy; Amel F. M. Ismail; Ahmed El-morsy; Nabil A. Shoman (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
This research investigates the formulation of a nanogel complex using pectin and poly(acrylic acid) (PAAc) to encapsulate rutin. The nanogel’s pH-responsive behavior and its potential as a targeted drug delivery platform are investigated. The gamma irradiation–induced crosslinking mechanism is elucidated, highlighting its role in creating a stable three-dimensional network structure within the polymer matrix. Fourier transform infrared spectroscopy analysis sheds light on the molecular interactions within rutin and the nanogel-rutin complex. The pH-responsive behavior of the nanogel is explored, showcasing its ability to release rutin selectively in response to pH variations and displaying high physical and chemical stability. Transmission electron microscopy imaging provides visual insights into nanogel morphology and interactions. The cumulative drug content from the nanogel was 86.14 ± 2.61%. The pH-dependent release profile of the nanogel was examined, demonstrating selective rutin release in response to varying pH levels. Cytotoxicity studies were conducted against four human cancer cell lines—HepG2, A549, MCF-7, and HCT-116 showing significant reductions in IC 50 values, indicating enhanced therapeutic efficacy. Additionally, molecular docking studies revealed strong binding interactions of rutin with VEGFR-2 and EGFR T790M . Our nanogel compound 5 significantly reduced the IC 50 values for HepG2, A549, MCF-7, and HCT-116 cells by 58.19%, 81.29%, 71.81%, and 67.16%, respectively. Furthermore, it lowered the IC 50 values for VEGFR-2 and EGFR T790M by 29.66% and 68.18%, respectively. Graphical Abstract

Evaluation of near-isogenic lines of rice introgressed with submergence tolerance and deep rooting at early growth stage - Ibrahim Soe; Nguyen Thi Thu Hang; Emmanuel Odama; Rael Chepkoech; Taiichiro Ookawa; Abdelbagi M. Ismail; Jun-Ichi Sakagami (Euphytica, 2025)
Rice varieties that minimise shoot elongation under submergence and provide tolerance for up to two weeks carry SUB1A . Conversely, DRO1 responsible for deep-rooting, helps in water and nutrient acquisition under drought. In this study, we compared the growth of NIL-SUB1, NIL-DRO1, and NIL-SUB1DRO1 with IR64 background for its dual tolerance to submergence, drought, and recovery. Submergence was on 14- and 16-days old seedling for 7 and 10 days and allowed to recover for 7 and 10 days respectively. Drought was also imposed on 14- and 13-days old seedlings for 18 and 29 days followed by 10 days recovery respectively. Submergence and drought adversely affected growth and performance of the genotypes. Compared to IR64, NIL-SUB1DRO1 suppressed shoot elongation during flooding, maintained the function of the leaf photosystem, and under drought conditions, maintained leaf water potential and contributed to increased dry matter weight of shoots and roots. In addition, NIL-SUB1DRO1 exhibited deep rooting, with roots extending into the lower subsurface layers under drought condition. It is suggested that NIL-SUB1 showed potential tolerance to submergence and NIL-DRO1 to drought. Furthermore, NIL-SUB1DRO1 was found to be tolerant to both drought and flooding.

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

A comprehensive assessment of smokeless tobacco (Shammah) extract: unraveling the effects on hematological parameters, antioxidant defense mechanisms, and organ health in rats - Mabrouk A. Abo-Zaid; Mohammed Abdulaziz Alfattah; Nabila Fathi Elashmawy; Hanan Ahmed Hamdi; Bedor Ali Yatimi; Latifah Abdu Hakami; Amira Ahmed Malhan; Tawfiq AlFaifi; Abadi M. Mashlawi; Sultan Areshi; Ali Hassan Amin; Khalid M. Elazab; et al. (Journal of Molecular Histology, 2025)

Research progress on application and adsorption performance of chitosan and its derivatives in the field of water treatment - M. Ismail; Y. Zhang; M. Mustafa; L. Ren; X. Chen (International Journal of Environmental Science and Technology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

The impact of melatonin and its agonist on blood pressure and serum endothelin-1 in continuous light and pinealectomized rats - Evan B. Othman; Ismail M. Maulood; Nazar M. Shareef Mahmood (Journal of Comparative Physiology B, 2025)

Gold mineralization and environmental impacts of artisanal mining in the Um Araka area, Egypt: Microanalyses and heavy metals assessment - Adel A. Surour; Mostafa M. El Desouky; Mariam M. Ismail; Raneem Abo Aissa; Hamada Zaghloul (Journal of African Earth Sciences, 2025)

From robust deep-learning regression to refined design formulas for punching shear strength of internal GFRP-reinforced flat slab-column connections - Ammar Babiker; Yassir M. Abbas; M. Iqbal Khan; Fouad Ismail Ismail (Engineering Structures, 2025)

Physiological and Molecular Responses of Red Amaranth (Amaranthus cruentus L.) and Green Amaranth (Amaranthus hypochondriacus L.) to Salt Stress - Tartil M. Emam; Abd Elaziz M. Hosni; Ahmed Ismail; Ramy G. El-Kinany; Mohammed Hewidy; Hani Saber Saudy; Mohamed M. A. Omar; Mariam T. S. Ibrahim; Shunzhao Sui; Salwa M. El-Sayed (Journal of Soil Science and Plant Nutrition, 2025)
Salinization, as a serious climate change phenomenon, continues to cause critical issues for soils and crops. Abundance of genetic diversity of plants could contribute in solving the impacts of salinity. However, the relations between physiological and molecular traits of plant species need deep investigation and interpretation. Pot experiments were conducted in the greenhouse to investigate the difference in behavior between two amaranth species when they were beforehand subjected to salinity-stress conditions, specifically on some specific physiological and molecular characteristics. After 45 days from transplanting, salt stress was induced using a 150 mM sodium chloride solution. Treatments were arranged in randomized complete block design using three replications. After 0, 2, 6, 10, and 24 h, samples were collected to evaluate physiological data as well as diversity of gene expression. The samples were immediately frozen in liquid nitrogen and stored in -80⁰ C ultralow temperature refrigerators. Findings revealed that the red amaranth species ( Amaranthus cruentus ) was more tolerant to saline stress than the green amaranth species ( Amaranthus hypochondriacus ). Result data revealed that malondialdehyde (MDA) content in the red amaranth increased after 2 h then decreased (after 6 and 10 h) before rising again after 24 h. In the green amaranth, MDA content initially decreased after 2 h before increasing and later decreasing in a zigzag pattern ending in an increase after 24 h. There was an initial steep rise in proline content of green amaranth after 2 h which continued to still rise moderately till 24 h. In the red amaranth the initial rise in proline continued after 2, 6 and 10 h before it stopped. Results also showed that red amaranth gave higher value of superoxide dismutase (SOD) activity as compared with green amaranth in all tested salinity exposure times. The investigation on the expression of four genes assessed through quantitative PCR indicated the efficiency of red amaranth in increasing the expression of SOS1, HKT1, NHX1, and DGR2 genes, which encode adaptation-related proteins under salinity stress. In summary, the current work demonstrated that red amaranth could be an efficient genetic resource in improving salt-tolerant genotypes belonging to Amaranthus genus.

Rotor–stator hydrodynamic cavitation reactor for intensification of castor oil biodiesel production - M. Khater; O. Aboelazayem; A. R. Ismail; A. Soliman; S. A. Abu Amr; N. Sh. El-Gendy; A. A. Ezzat (International Journal of Environmental Science and Technology, 2025)
Nowadays, the intensification of the production of biodiesel from non-edible oil crops is mandatory to overcome petrol-fuel depletion and environmental pollution. For the first time, enhanced biodiesel production from castor oil via rotor–stator hydrodynamic cavitation has been studied in this work. Response surface methodology based on one-factor-at-a-time design of experiments was employed for modelling and optimizing the biodiesel yield and the decrease in feedstock viscosity, density, and total acid number (TAN). The predicted optimum parameters of 8.15:1 methanol:oil (M:O), 1499 rpm, 29.38 min, 48.43 °C, and a KOH catalyst concentration of 0.74 wt.% resulted in a 96% biodiesel yield with a concomitant decrease in viscosity, density, and TAN of approximately 95%, 5.12%, and 90.02%, respectively. According to the results of the breakthrough kinetic calculations, the reaction is pseudo-second order, with the activation energy, frequency factor, and reaction rate constant being 0.23 M −1 min −1 , 18.77 kJ/mol, and 6.32 M −1 min −1 , respectively. The fuel properties of the produced biodiesel and bio-petro-diesel blends were good, comparable to international standards and the marketed Egyptian petro-diesel.

The Gastroprotective Effects of Salvia indica L. and Selenium In Vivo Study - Talal Salem Al-Qaisi; Ahmed A. J. Jabbar; Mohammed M. Hussein M. Raouf; Parween Abdul-Samad Ismail; Ramzi A. Mothana; Hanan M. Al-Yousef; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Musher Ismael Saleh; Mohammed Awad; Mohamad Fawzi Mahomoodally (Biological Trace Element Research, 2025)

A Comprehensive Assessment of Health Risks Associated with Heavy Metal Through Ingestion of Two Predominant Fish Species in a Developing Country - Tusar Kanti Roy; Sudipta Kumar Nag; Uttam Biswas Antu; Sk Arafat Hossain; Abdullah Al Bakky; Md. Tanvir Anjum; Bikash Chandra Sarker; Md. Rahamat Ullah; Fariha Farzana; Nor Aida Mahiddin; Ashish Biswas; Pronayan Singha; et al. (Biological Trace Element Research, 2025)

Molecular identification and characterization of waterborne protozoa among stranded Dugong dugon - Sonia Boughattas; Layla Ben Ayed; Hamed Mirjalali; Marianna Marangi; Dana Albatesh; Abdelrahman ElGamal; Ismail Al-Shaikh; Nayla Al-Neama; Asmaa A. Althani; Panagiotis Karanis; Fatiha M. Benslimane (Marine Pollution Bulletin, 2025)

Unlocking the therapeutic potential of cinchonains: a comprehensive review - Nidal Fahsi; Ismail Mahdi; Hassan Annaz; Gabin Thierry M. Bitchagno; Mona F. Mahmoud; Mansour Sobeh (Phytochemistry Reviews, 2025)

Age, growth, and intrinsic sensitivity of Endangered Spinetail Devil Ray (Mobula mobular) and Bentfin Devil Ray (M. thurstoni) in the Indian Ocean - Ellen Barrowclift; Andrew J. Temple; Sebastián A. Pardo; Alexander M. A. Khan; Shoaib Abdul Razzaque; Nina Wambiji; Mochamad Rudyansyah Ismail; Lantun Paradhita Dewanti; Per Berggren (Marine Biology, 2025)
Devil rays ( Mobula spp.) are caught in fisheries across the Indian Ocean, with reports of significant recent declines in catch and sightings. Globally, the few populations studied have extremely low population growth rates due to low fecundity and long reproductive cycles, making them highly vulnerable to overfishing. To allow for assessment of the current sustainability of devil ray catch in the Indian Ocean, we provide estimates of age using the caudal vertebrae; somatic growth using a Bayesian, multi-model approach; maximum intrinsic rate of population increase ( r max ); and fishing mortality for Endangered Spinetail Devil Ray ( Mobula mobular ) and Bentfin Devil Ray ( M. thurstoni ) sampled from small-scale fisheries catch in Indonesia, Kenya, and Pakistan. The oldest individuals of Spinetail Devil Ray ( n = 79) and Bentfin Devil Ray ( n = 59) were 17.5 and six years, respectively. Both species had relatively low growth coefficients ( k = 0.05 and g = 0.19 year −1 , respectively), with the von Bertalanffy and logistic models providing the best fitting growth models, and low r max (0.109 and 0.107 year −1 , respectively) indicating that they are highly sensitive to overexploitation. Fishing mortality F estimates (0.16 and 0.18 year −1 , respectively) were higher than r max and exploitation ratio E (0.77 and 0.80, respectively) were higher than an optimum value of 0.5 for biological sustainability for both species, suggesting that the fisheries catches of the species are unsustainable. We demonstrate an approach to assess data-poor species and apply this to two Indian Ocean devil ray species. The results highlight the urgent need for better management actions to reduce the catch of all devil rays to prevent species extinction and aid in population recovery.

Persimmon (Diospyros kaki L.) leaves accelerates skin tissue regeneration in excisional wound model: possible molecular mechanisms - Talal Salem H. Al-Qaisi; Ahmed A. j. Jabbar; Mohammed M. Hussein M. Raouf; Parween AbdulSamad Ismail; Ramzi A. Mothana; Mohammed F. Hawwal; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Musher Ismael Saleh; Mohammed Awad (Journal of Molecular Histology, 2025)

Bioaccumulation, biochemical responses and health risk assessment of heavy metals in seaweeds from Alexandria Coast: pollution case - M. M. Ismail; G. M. El Zokm; H. A. Abdel-Mohsen (International Journal of Environmental Science and Technology, 2025)

Physiological, biochemical, apoptosis-linked gene expression, and histopathological insights in Nile catfish subjected to toxicity by magnetite nanogel - Yasmina K. Mahmoud; Shaimaa A. A. Ahmed; Heba H. Mahboub; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Ahmed A. Elnegiry; Sherif M. Shawky; Sahar H. Orabi; Sameh H. Ismail; Simon J. Davies; Mahmoud I. M. Darwish (Fish Physiology and Biochemistry, 2025)

Brain targeted lactoferrin coated lipid nanocapsules for the combined effects of apocynin and lavender essential oil in PTZ induced seizures - Julie R. Youssef; Nabila A. Boraie; Fatma A. Ismail; Basant A. Bakr; Eman A. Allam; Riham M. El-Moslemany (Drug Delivery and Translational Research, 2025)
Apocynin (APO) is a plant derived antioxidant exerting specific NADPH oxidase inhibitory action substantiating its neuroprotective effects in various CNS disorders, including epilepsy. Due to rapid elimination and poor bioavailability, treatment with APO is challenging. Correspondingly, novel APO-loaded lipid nanocapsules (APO-LNC) were formulated and coated with lactoferrin (LF-APO-LNC) to improve br ain targetability and prolong residence time. Lavender oil (LAV) was incorporated into LNC as a bioactive ingredient to act synergistically with APO in alleviating pentylenetetrazol (PTZ)-induced seizures. The optimized LF-APO-LAV/LNC showed a particle size 59.7 ± 4.5 nm with narrow distribution and 6.07 ± 1.6mV zeta potential) with high entrapment efficiency 92 ± 2.4% and sustained release (35% in 72 h). Following subcutaneous administration, LF-APO-LAV/LNC brought about ⁓twofold increase in plasma AUC and MRT compared to APO. A Log BB value of 0.2 ± 0.14 at 90 min reflects increased brain accumulation. In a PTZ-induced seizures rat model, LF-APO-LAV/LNC showed a Modified Racine score of 0.67 ± 0.47 with a significant increase in seizures latency and decrease in duration. Moreover, oxidant/antioxidant capacity and inflammatory markers levels in brain tissue were significantly improved. Histopathological and immunohistochemical assessment of brain tissue sections further supported these findings. The results suggest APO/LAV combination in LF-coated LNC as a promising approach to counteract seizures. Graphical Abstract

Effect of low doses of gamma radiation on cell growth over an electrospun polycaprolactone/zinc acetate scaffold for biomedical applications - Naglaa M. Ismail; Soheir Korraa; M. B. S. Osman; Eman El Sheikh (Biophysical Reviews, 2025)

Metallic nanoparticles: a promising novel therapeutic tool against antimicrobial resistance and spread of superbugs - Naheem Adekilekun Tijani; Joseph Hokello; Emmanuel Eilu; Saheed Adekunle Akinola; Abdullateef Opeyemi Afolabi; Danladi Makeri; Tonny Wotoyitide Lukwago; Irene M. Mutuku; Alex Mwesigwa; Andrew Baguma; Ismail Abiola Adebayo (BioMetals, 2025)

Dust over Saudi Arabia from multisource data: case studies in winter and spring - Mazen E. Assiri; M. Nazrul Islam; Md Arfan Ali; Arjan O. Zamreeq; Ayman S. Ghulam; Muhammad Ismail (Air Quality, Atmosphere & Health, 2025)

Sunflower germplasms’ response to different water and salinity stress levels in greenhouse and field conditions under subsurface drip irrigation - Sevgi Saylak; Suat Irmak; Kent M. Eskridge; Ismail Dweikat (Irrigation and Drainage, 2025)
Sunflower ( Helianthus annuus L.) is moderately tolerant to salt and water stress, but its production can still be significantly and adversely affected by increases in these stressors as a result of the negative impacts of climate change on agricultural soil and crop productivity. The morphological and productivity (dry head weight, dry root weight, dry shoot weight, head diameter, whole seed weight, crude protein content, crude oil content, palmitic acid, stearic acid, oleic acid, linoleic acid, eicosanoic acid, 11‐eicosenoic acid, homo‐gamma‐linolenic w6 acid, lignoceric acid and plant height) responses of modern sunflower germplasms to different levels of salt and drought stress under greenhouse and field conditions were investigated and analysed. Six germplasms were evaluated under three salt concentrations (0, 150 and 250 mM), and two germplasms were evaluated for drought response under three irrigation levels. Significant differences in the response of sunflower germplasms to water and salinity were detected. The same germplasms exhibited significant differences in response to water and salinity between the treatments, which also varied significantly between the germplasms for the same treatment. The irrigation level significantly influenced the amount of oil but not the crude protein or fatty acid composition. The results and information of this research can aid in selecting and improving sunflower productivity under adverse (i.e. saline and drought) conditions.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Microbial-priming of seeds with plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi for improving cotton (Gossypium barbadense L.) growth, yield and water productivity under drought stress - Hossam S. El-Beltagi; Essam Abdelaziz El-Waraky; Mohamed M. El-Mogy; Mohamed Fathi El-Nady; Ahmed Mahmoud Ismail; Elsayed B. Belal; Mohammed I. Al-Daej; Nagwa Mohamed El-Khateeb; Lamy Hamed; Metwaly Mahfouz Salem Metwaly (Biologia, 2025)

Lead toxicity in African catfish: Promising role of magnetite nanogel against etho-neurological alterations, antioxidant suppression, gene toxicity, and histopathological/ immunohistochemical disruptions - Afaf N. Abdel Rahman; Heba H. Mahboub; Rasha M.M. Ezz-Eldin; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Tarek Khamis; Enas K. Aziz; Walaa A.A. Basha; Ibrahim Elmaghraby; Simon J. Davies; Sameh H. Ismail; Yasmin A. Reyad (Aquaculture, 2025)

Life cycle assessment on the role of H2S-based hydrogen via H2S-methane reforming for the production of sustainable fuels - Kalppana Chelvam; Marlia M. Hanafiah; Ismail I.I. Alkhatib; Sawsan M. Ali; Lourdes F. Vega (Science of The Total Environment, 2025)

Expression profiling of antimicrobial peptides and immune-related genes in Nile tilapia following Pseudomonas putida infection and nano-titanium dioxide gel exposure - Heba H. Mahboub; Morteza Yousefi; Hosny Ahmed Abdelgawad; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Emad Sakr; Tarek Khamis; Sameh H. Ismail; Afaf N. Abdel Rahman (Fish & Shellfish Immunology, 2025)

Liposome encapsulating pine bark extract in Nile tilapia: Targeting interrelated immune and antioxidant defense to combat coinfection with Aeromonas hydrophila and Enterococcus faecalis - Doaa Ibrahim; Sara E. Shahin; Shimaa S. Elnahriry; Sara M. El-Badry; Reham M. Eltarabili; Sara T. Elazab; Tamer Ahmed Ismail; Marwa I. Abd El-Hamid (Fish & Shellfish Immunology, 2025)

Overexpression of OsSTP1 increases grain yield via enhancing carbohydrate metabolism and transport in rice - Dong Liu; Ming-juan Li; Jin-song Luo; Hai-fei Chen; Yong Yang; Gui Xiao; Jun Wu; Abdelbagi M. Ismail; Zhen-hua Zhang (Planta, 2025)

Novel nafion-palygorskite composite for Pb/Lead treatment - M. Sabbagh; M. Hussaini; U. Ismail; H. R. Ahmed; M. Al-Suwaiyan; M. Vohra (International Journal of Environmental Science and Technology, 2025)

Microfluidic-based fluorescence enhancement of silica-embedded carbon dots for direct detection and quantification of unamplified HCV RNA in clinical samples - Hanan Shaat; Mohamed Sharafeldin; Amany Mostafa; Eman H. Ismail; Mohmed K. Hassan; Mohamed H. Alkordi; El-Zeiny M. Ebeid; Hesham Elghazaly; Sara H. Agwa; Sherif M. Shawky (Analytica Chimica Acta, 2025)

Correction to: The effects of nano‑selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El‑Aziz; Yasmin A. Reyad; El‑Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

The effects of nano-selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El-Aziz; Yasmin A. Reyad; El-Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

H2S and SO2 toxic gases removal using date palm-tree branches based activated carbon: experimental findings and machine learning (ML) modeling - Usman M. Ismail; Minaam Hussaini; Muhammad S. Vohra (Environment, Development and Sustainability, 2024)

A consensus-based, revised and comprehensive catalogue for Mediterranean water masses acronyms - KATRIN SCHROEDER; SANA BEN ISMAIL; MANUEL BENSI; ANTHONY BOSSE; JACOPO CHIGGIATO; GIUSEPPE CIVITARESE; FRANCESCO FALCIERI M; GIANNETTA FUSCO; MIROSLAV GAČIĆ; ISAAC GERTMAN; ELISABETH KUBIN; PAOLA MALANOTTE-RIZZOLI; et al. (Mediterranean Marine Science, 2024)
Addressing the need for clear communication in Mediterranean oceanography, this study presents a revised and comprehensive catalogue of water mass acronyms. Although there is no universal set of standard rules for assigning acronyms to water masses, as these can vary among different research groups, regions, or scientific communities, scientists generally aim for clarity and consistency when naming and abbreviating water masses to facilitate communication within the scientific community. The team of experts, guided by the CIESM (the Mediterranean Science Commission) C2 Committee on the Physics and Climate of the Ocean, reviewed existing literature and established new acronyms and naming guidelines. This standardized system, emphasizing clarity and consistency, replaces the current variable practices employed by different research groups.

Integrating ports into green shipping corridors: Drivers, challenges, and pathways to implementation - Ahmed M. Ismail; Fabio Ballini; Aykut I. Ölçer; Anas S. Alamoush (Marine Pollution Bulletin, 2024)

Morphological and molecular characterization of the green algae Ulva in the Mediterranean Coast of Egypt - Nermin A. Ibrahim; Enas M. Abdelghany; Soha Shabaka; Mona Ismail; Ola Shalaby; Mohamed Ismail (Regional Studies in Marine Science, 2024)

Emerging technologies for efficient water use in agriculture: A review of current trends and future directions - Uttam Biswas Antu; Md. Saiful Islam; Sujat Ahmed; Md. Arifuzzaman; Sawmitra Saha; Puja Rani Mitu; Aditya Raj Sarkar; Nor Aida Mahiddin; Zulhilmi Ismail; Khalid A. Ibrahim; Abubakr M. Idris (Journal of Water Process Engineering, 2024)

A multifunctional natural treasure based on a “one stone, many birds” strategy for designing health-promoting applications: Tordylium apulum - Nilofar; Gokhan Zengin; Abdullahi Ibrahim Uba; Nurgul Abul; Ilhami Gulcin; Ismail Koyuncu; Ozgur Yuksekdag; Sathish Kumar M Ponnaiya; Surendar Tessappan; Filomena Nazzaro; Florinda Fratianni; Francesca Coppola; et al. (Food Bioscience, 2024)

The Novel Study On Arsenic Contamination, Health Risk, and Approaches to Its Mitigation From Water Resource of a Developing Country: A potential review - Md.Saiful Islam; Abdullah Al Bakky; Abu Reza Md. Towfiqul Islam; Mir Mohammad Ali; Md. Towhidul Islam; Zulhilmi Ismail; Md. Tanvir bin Hossain; Sujat Ahmed; Khalid A. Ibrahim; Abubakr M. Idris (Water, Air, & Soil Pollution, 2024)

Effect of a single dose of letrozole on ejaculation time, semen quality, and testicular hemodynamics in goat bucks subjected to heat stress - Ola Adel; Hossam R. El-Sherbiny; Abdallah M. Shahat; Sayed Taha Ismail (Veterinary Research Communications, 2024)
Letrozole (LTZ) is an aromatase inhibitor that limits estrogen (E2) production and increases testosterone (T) levels. This research aimed to examine the impact of a single dose of LTZ on testicular hemodynamics, ejaculation time, and semen quality in goats under heat stress (HS). Therefore, Doppler examination and semen evaluation were performed on twelve mature bucks for two weeks (W-1, W-2) as pre-heat stress control during winter. Then during summer HS bucks were subjected to Doppler examination, semen evaluation, and hormonal analysis (T, E2, and LH) at 0 h. Afterward, bucks were assigned into two groups and subcutaneously injected with physiological saline ( n = 6; CON) or LTZ (0.25 mg/kg BW; n = 6; LTZ). Both groups were subjected to Doppler scanning and hormonal analysis at 2, 4, 24, 48, 72, 96,144, and 168 h. Semen evaluation was performed at 48 and 168 h. The LTZ group showed increasing ( P < 0.05) in semen volume, sperm motility, and viability and decreasing ( P < 0.05) in ejaculation time and sperm abnormalities compared to CON group at 48 h. Additionally, T concentrations increased ( P < 0.01) at 2, 24, and 48 h, E2 decreased ( P < 0.01) from 2 to 48 h, and LH raised ( P < 0.01) at 2 and 72 h in LTZ group compared to CON one. Doppler indices reduced ( P < 0.05) at 96 h in LTZ group. semen pH and scrotal circumference were not affected by LTZ. In conclusion, LTZ administration shortened ejaculation time and enhanced semen quality in bucks during HS.

Synthesis, cytotoxicity, anti-inflammatory, anti-metastatic and anti-oxidant activities of novel chalcones incorporating 2-phenoxy-N-arylacetamide and thiophene moieties: induction of apoptosis in MCF7 and HEP2 cells - Nada S. Ibrahim; Hager Ahmed Sayed; Marwa Sharaky; Hadeer M. Diab; Ahmed H. M. Elwahy; Ismail A. Abdelhamid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Eight Novel chalcones were synthesized and their structures were confirmed by different spectral tools. All the prepared compounds were subjected to SRB cytotoxic screening against several cancer cell lines. Compound 5c exerted the most promising effect against MCF7 and HEP2 cells with IC 50 values of 9.5 and 12 µg/mL, respectively. Real-time PCR demonstrated the inhibitory effect of compound 5c on the expression level of Antigen kiel 67 (KI-67), Survivin, Interleukin-1beta ( IL-1B ) , Interleukin-6 ( IL-6 ), Cyclooxygenase-2 (COX-2 ) and Protein kinase B (AKT1) genes. Flow-cytometric analysis of the cell cycle indicated that compound 5c stopped the cell cycle at the G0/G1 and G2/M phases in MCF7 and HEP2 treated cells, respectively. ELISA assay showed that Caspase 8, Caspase 9, P53, BAX, and Glutathione (GSH) were extremely activated and Matrix metalloproteinase 2 (MMP2), Matrix metalloproteinase 9 (MMP9), BCL2, Malondialdehyde (MDA), and IL-6 were deactivated in 5c treated MCF7 and HEP2 cells. Wound healing revealed that chalcone 5c reduced the ability to close the scrape wound and decreased the number of migrating MCF7 and HEP2 cells compared to the untreated cells after 48 h. Theoretical molecular modeling against P53 cancer mutant Y220C and Bcl2 showed binding energies of -22.8 and -24.2 Kcal/mole, respectively, which confirmed our ELISA results.

Enhancing Surface Properties of Circular Carbon Biochar Derived from Spent Coffee Beans Through ZnCl2/KOH Activation - Gowthami D.; R. K. Sharma; M. Khalid; Muhammad Yusri Ismail (BioEnergy Research, 2024)

New ternary 0D/1D/2D CdO/Y2O3/graphene oxide nanocomposites with improved photocatalytic characteristics: Solar dye decolorization and H2-evolution - Heba Ali; Asmaa M. Abozied; A.M. Ismail (Journal of Water Process Engineering, 2024)

Scaling up dry methane reforming: Integrating computational fluid dynamics and machine learning for enhanced hydrogen production in industrial-scale fluidized bed reactors - Fahad N. Alotaibi; Abdallah S. Berrouk; Ismail M. Salim (Fuel, 2024)

Toxicity assessment of heavy metals translocation in maize grown in the Ganges delta floodplain soils around the Payra power plant in Bangladesh - Md Saiful Islam; Abdullah Al Bakky; Sujat Ahmed; Md Towhidul Islam; Uttam Biswas Antu; Md Sadik Mahmud Saikat; Ruma Akter; Tusar Kanti Roy; Yeasmin Nahar Jolly; Kazi Aminul Islam; Avijit Sarkar; Zulhilmi Ismail; et al. (Food and Chemical Toxicology, 2024)

Recovery of precious metals from aqua regia leachate of e-wastes using dithiocarbamate-modified cellulose and development of a novel kinetic model - M. Mehedi Hasan Rocky; Ismail M.M. Rahman; Shunsuke Taka; Moe Marumoto; Shafiqur Rahman; Masaru Endo; Kuo H. Wong; Asami S. Mashio; Hiroshi Hasegawa (Chemical Engineering Journal, 2024)

Synthesis and Characterization of Low-Cost Zirconium Nanocomposites as Novel Adsorbents for Arsenazo III Pollutant - Ahmed A. Eliwa; Ahmed M. Abdel-Razik; Mohamed S. Hagag; Ahmed M. Ismail; Amal E. Mubark (Water, Air, & Soil Pollution, 2024)
Removing contaminated Arsenazo III dye from contaminated effluent is a challenge and of great interest due to its hazard and environmental impact. Therefore, the biggest challenge was producing highly efficient, easy to recycle, and economically inexpensive adsorbent materials for the contaminated dye. Three chemically stable zirconium nanocomposites with unique properties were synthesized by gel-precipitation technology. The composition, chemical, and physical properties of zirconium molybdate, tungstate, and silicate nanocomposites have been extensively proven using many different and appropriate devices such as XRD, SEM–EDX, TEM, FT-IR, BET, DLS, TGA-DTA, and zeta potential. By utilizing the most effective adsorption techniques, Azo-dye was successfully bound to ZrMo-NPs, ZrW-NPs, and ZrSi-NPs composites. The uptake capacities for these composites were measured at 0.29, 0.79, and 1.61 mmol.g −1 , respectively. The sorption parameters were optimized as follows: a feed solution pH of 3 for ZrMo-NPs, a pH of 2.3 for ZrW-NPs, and a pH of 2.3 for ZrSi-NPs. The stirring time was set at 30 min, the metal ion concentration was 1.64 mmol L −1 , and the sorbent dose was 7.5 mg. The adsorption results agreed well with the Langmuir isotherm and the pseudo-second-order reaction models and demonstrated the endothermic nature and kinetic improvement by increasing temperatures. The three nanocomposites effectively eliminated tainted dye from lab wastewater, offering promise for their potential applications in the future. Graphical Abstract

A new framework integrating flood inundation modeling and multicriteria decision-making for enhanced flood risk mapping - Ismail Jesna; Cicily Kurian; S. M. Bhallamudi; K. P. Sudheer (Natural Hazards, 2024)

Paracetamol in diverse water sources: health hazards and treatment efficacy emphasizing adsorption techniques—a review - B. Mohammed Al-howri; S. Farhan Azha; M. Sharafee Shamsudin; N. A. Hamid; A. Mubarak Alsobaai; S. Ismail (International Journal of Environmental Science and Technology, 2024)

Toxicity factors, ecological and health risk assessments of heavy metal in the urban soil: a case study of an agro-machinery area in a developing country - Md. Saiful Islam; Abdullah Al Bakky; Md. Sadik Mahmud Saikat; Uttam Biswas Antu; Ruma Akter; Tusar Kanti Roy; Zulhilmi Ismail; Khalid A. Ibrahim; Abubakr M. Idris (Environmental Geochemistry and Health, 2024)

Discovery of Knock‐Down Resistance in the Major African Malaria Vector Anopheles funestus - Joel O. Odero; Tristan P. W. Dennis; Brian Polo; Joachim Nwezeobi; Marilou Boddé; Sanjay C. Nagi; Anastasia Hernandez‐Koutoucheva; Ismail H. Nambunga; Hamis Bwanary; Gustav Mkandawile; Nicodem J. Govella; Emmanuel W. Kaindoa; et al. (Molecular Ecology, 2024)
A major insecticide resistance mechanism in insect pests is knock‐down resistance ( kdr ) caused by mutations in the voltage‐gated sodium channel ( Vgsc ) gene. Despite being common in most malaria Anopheles vector species, kdr mutations have never been observed in Anopheles funestus , the principal malaria vector in Eastern and Southern Africa, with resistance mainly being conferred by detoxification enzymes. In a parallel study, we monitored 10 populations of An . funestus in Tanzania for insecticide resistance unexpectedly identified resistance to a banned insecticide, DDT, in the Morogoro region. Through whole‐genome sequencing of 333 An . funestus samples from these populations, we found eight novel amino acid substitutions in the Vgsc gene, including the kdr variant, L976F (equivalent to L995F in An . gambiae ), in tight linkage disequilibrium with another (P1842S). The mutants were found only at high frequency in one region and were accompanied by weak signatures of a selective sweep, with a significant decline between 2017 and 2023. Notably, kdr L976F was strongly associated with survivorship to exposure to DDT insecticide, while no clear association was noted with a pyrethroid insecticide (deltamethrin). The WHO prequalifies no DDT products for vector control, and the chemical is banned in Tanzania. Widespread DDT contamination and a legacy of extensive countrywide stockpiles may have selected for this mutation. Continued monitoring is necessary to understand the origin of kdr in An . funestus , and the threat posed to insecticide‐based vector control in Africa.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Trace element contamination in water and sediment in an estuarine ecosystem connected to the Bay of Bengal: A preliminary assessment of ecological and human health risks - Arnob Ghosh; Kowshik Das Karmaker; Mahmudul Hasan; Mahfujur Rahman; Nusrat Jahan Shimu; Md. Saiful Islam; M. Safiur Rahman; Md. Shawon Hossain; Zulhilmi Ismail (Marine Pollution Bulletin, 2024)

Fabrication of TiO2@ZIF-67 metal organic framework composite incorporated PVDF membranes for the removal of hazardous reactive black 5 and Congo red dyes from contaminated water - Nethravathi Prabhakar; Arun M. Isloor; Mahesh Padaki; Ahmad Fauzi Ismail (Chemical Engineering Journal, 2024)

Machine learning modeling and statistical optimization of dye removal from contaminated water using CTAB-functionalized graphene oxide - Sally AlNaimat; Usman M. Ismail; Ahmed I. Ibrahim; Abdimalik Muse; Kashif Faheem; Mohamed Mustafa; Muhammad S. Vohra; Sagheer A. Onaizi (Water, Air, & Soil Pollution, 2024)

A triterpenoid (corosolic acid) ameliorated AOM-mediated aberrant crypt foci in rats: modulation of Bax/PCNA, antioxidant and inflammatory mechanisms - Morteta H. Al-Medhtiy; Mohammed T Mohammed; Mohammed M. Hussein M. Raouf; Ayman M. Al-Qaaneh; Ahmed A.j. Jabbar; Fuad Othman Abdullah; Ramzi A. Mothana; Abdullah R. Alanzi; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Musher Ismail saleh; Sidgi Hasson (Journal of Molecular Histology, 2024)

Scrutinizing gully erosion hotspots to predict gully erosion susceptibility using ensemble learning framework - Qing tao Guan; Zhong ling Tong; Alireza Arabameri; M. Santosh; Ismail Mondal (Advances in Space Research, 2024)

The Egyptian Nile estuarine habitats: a review - Khaled M. Abdelsalam; Hermine R. Z. Tadros; Abeer A. Moneer; Mona Kh. Khalil; Samia K. Hamdona; Laila Shakweer; Madelyn N. Moawad; Abeer A. M. El-Sayed; Ghada F. El-Said; Mona M. Ismail; Aida H. Shobier; Shimaa Hosny; et al. (Aquatic Sciences, 2024)
Estuaries are nutrient-rich environments characterized by a gradient in salinity due to the mixing of freshwater and seawater. These bodies of water play vital functions in nature and provide a wide variety of essential ecosystem services. In general, many natural and/or man-made activities have strongly stressed the Egyptian Nile estuarine habitats, as has the water shortage that was expected after the construction of the Grand Ethiopian Renaissance Dam. In recent decades, the Nile Delta has been considered to be one of the most important productive oil-producing petroleum regions due to onshore and offshore gas discoveries alongside gasoline and base oil generation. Up-to-date systematic reviews of the Egyptian estuarine habitats (Rosetta and Damietta) are missing, and the review reported here was undertaken to fill this gap. In this review, we consider the physical, chemical, geological, pollution, and biological parameters of Egyptian Nile estuaries. In this context, our aim is to contribute to a broader understanding of the Egyptian estuarine habitat; moreover, we provide potential warning signals that may aid in estuarine environmental protection. We found that most of the previous studies had focused on the two branches of the Nile or on the marine waters adjacent to these branches, and that only a few studies focused on the estuarine habitats themselves. In most of these previous studies, the salinity gradient of water was reported to be a significant factor in the distribution of the different measured parameters while, in contrast, more recent investigations confirm the importance of potential effluent sources in affecting the distribution of these parameters. We highly recommend that the data reported here be updated in future studies on different environmental aspects.

Effect of prolonged photoperiod on growth, gonadal development, sex ratio, and skin coloration of red tilapia (O. mossambicus × O. urolepis hornorum) - Hossam E. R. Sharaf; Samira S. Assem; Rania F. Ismail; Ashraf A. M. Zeitoun; Tarek M. A. Srour (Aquaculture International, 2024)
Farming of red tilapia is one promising direction in aquaculture. The objective of this study was to investigate the impact of long-day photoperiod on the growth performance, reproductive parameters, maturity, sex ratio, β-carotene content, and skin coloration of red tilapia. Early life larvae were allocated into three treatment groups in triplicates: T1 = control group (12L:12D), T2 = long-day group (18L:6D), and T3 = continuous illumination group (24L:0D) for 90 days. By the end of the experiment, gonadosomatic index (GSI), relative fecundity, steroid hormones, maturity stages, sex ratio, and ovarian and testicular histology were examined; also, growth performance, survival rate, skin color, and total β-carotene content were measured. The results indicated that GSI% and serum testosterone (T) in T3 group significantly increased with greater amount of spermatozoa of male fish. Also, growth parameters and HSI% in female fish displayed significantly increased for T3 group. Females in group T2 showed significant elevation in GSI%, relative fecundity, and estradiol (E2) with higher number of mature stage. Continuous light group (T3) showed shifted male sex ratio, while female percentage was higher in T2 group. The total β-carotene content of T3 group showed significant elevation with less number of black spots. This study demonstrated that continuous light manipulation during red tilapia early life could stimulate the growth and enhance coloration by reducing black spots that significantly affects economic profitability. Long-day application was effective in female reproductive performance and maturity. This study also served as an important reference for red tilapia aquaculture.

Toxicological insight of magnetite nanogel: neuro-ethological, hepato-renal, antioxidant, and histopathological traits in Clarias gariepinus - Samar Kamel; Shaimaa A. A. Ahmed; Asmaa Elsayyad; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Mohamed Shaalan; Mohamed M. S. Gaballa; Heba H. Mahboub; Tarek Khamis; Sameh H. Ismail; Simon J. Davies; Zeinab Hassan (Aquaculture International, 2024)
Assessment of acute toxicity of magnetic nanogel (MNG) is crucial to conclude the safe applicable dose and to warrant its application in aquaculture. Therefore, the current study is a novel step to assess behavior, neuro-stress response, hepato-renal, oxidative, and histopathological variations produced by MNG’ acute toxicity in Clarias gariepinus . Two experiments were conducted: the first was a determination of the 96-h lethal concentration 50 (LC 50 ) of MNG in C. gariepinus . Meanwhile, the second was an assessment of the toxicological impacts of three different concentrations of MNG in C. gariepinus following a 10-day exposure period and a subsequent 10-day depuration trial. One hundred and eighty fish were allotted to four groups exposed to 0, 1/10, 1/8, or 1/5 96-h LC 50 of MNG. The outcomes exhibited that 96-h LC 50 of MNG for C. gariepinus was 44 mg/L. The subjected group to MNG induced a concentration-dependent elevation in the serum values of cortisol, alanine transaminase, aspartate transaminase, urea, and creatinine following MNG exposure. Marked elevation in the oxidative stress indicators (catalase (CAT), glutathione S-transferase activity (GST), and superoxide dismutase (SOD)) was also evident. Meanwhile, the value of the neurological biomarker, acetylcholinesterase (AChE), was markedly reduced in a concentration-dependent way. These biochemical changes were complemented by pathological alterations in the hepato-renal architecture. Interestingly, in response to the 10-day depuration period, most of the tested parameters were eliminated in C. gariepinus exposed to 1/10 of LC 50 . Conclusively, MNG can induce numerous adverse effects only at higher doses (1/5 and 1/8 of LC 50 ). Meanwhile, the lowest tested concentration of MNG (1/10 of LC 50 ) was safe for application in aquaculture practices with only mild disruptions in the bio-indices. In addition, a retrieval period of 10 days was sufficient to renovate these alterations only in fish exposed to the same concentration.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Effect of interleukin 6 (IL-6) on sperm quality, kinematic parameters, acrosome integrity, apoptosis, ultrastructure, and molecular docking in cryopreserved ram spermatozoa - Mahmoud A.E. Hassan; Wael A. Khalil; Aya A. Ismail; Maha Abdullah Momenah; Khaled M. Al-Marakby; Sameh A. Abdelnour (Reproductive Biology, 2024)

Influence of catalyst agglomerate internal structure on PEFC performance investigated by a multiscale numerical model - J. Tian; M.S. Ismail; K.J. Hughes; D.B. Ingham; L. Ma; M. Pourkashanian (Fuel, 2024)

Coupling of a streamlined solid-liquid extraction protocol with LC-ESI-MS/MS for the regular oversight of illegal bromate additive use: An accurate and sensitive determination method in preliminary and bakery products - Amira A. Abdulrahman El-Bahar; Amr H. Shendy; Alaa El-Dean Fathy Ahmed Aboalhassen; Ahmed M. Gomaa; Eman H. Ismail (Food Chemistry, 2024)

Improving functionality and texturization potential of novel pennycress (Thlaspi arvense) protein by inducing polymerization - Rachel M. Mitacek; Job Ubbink; Baraem P. Ismail (Food Hydrocolloids, 2024)

Assessment of thermal performance of energy-active window systems in hot climates - Mahmoud Magzoub; Mohammed Alhaji Mohammed; Ismail M. Budaiwi; Mohammad S. Al-Homoud (Energy and Buildings, 2024)

Comprehensive insights into aqua regia-based hybrid methods for efficient recovery of precious metals from secondary raw materials - M. Mehedi Hasan Rocky; Ismail M.M. Rahman; Masaru Endo; Hiroshi Hasegawa (Chemical Engineering Journal, 2024)

Biological evaluation of levofloxacin and its thionated derivatives: antioxidant activity, aldehyde dehydrogenase enzyme inhibition, and cytotoxicity on A549 cell line - Hamza Abumansour; Osama H. Abusara; Wiam Khalil; Hassan Abul-Futouh; Ali I. M. Ibrahim; Mohammad K. Harb; Dina H. Abulebdah; Worood H. Ismail (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Nose to brain delivery of mirtazapine via lipid nanocapsules: Preparation, statistical optimization, radiolabeling, in vivo biodistribution and pharmacokinetic study - Mennatullah M. Ibrahim; Emad B. Basalious; Mohamed A. El-Nabarawi; Amal IA. Makhlouf; Marwa Eid Sayyed; Ismail Taha Ibrahim (Drug Delivery and Translational Research, 2024)
Mirtazapine (MZPc) is an antidepressant drug which is approved by the FDA. It has low bioavailability, which is only 50%, in spite of its rapid absorption when orally administered owing to high first-pass metabolism. This study was oriented towards delivering intranasal (IN) mirtazapine by a direct route to the brain by means of preparing lipid nanocapsules (LNCs) as a targeted drug delivery system. MZP-LNCs were constructed by solvent-free phase inversion temperature technique applying D-Optimal mixture design to study the impact of 3 formulation variables on the characterization of the formulated nanocapsules. Independent variables were percentage of Labrafac oil, percentage of Solutol and percentage of water. Dependent variables were particle size, polydispersity index (PDI), Zeta potential and solubilization capacity. Nanocapsules of the optimized formula loaded with MZP were of spherical shape as confirmed by transmission electron microscopy with particle diameter of 20.59 nm, zeta potential of − 5.71, PDI of 0.223 and solubilization capacity of 7.21 mg/g. The in vivo pharmacokinetic behavior of intranasal MZP-LNCs in brain and blood was correlated to MZP solution after intravenous (IV) and intranasal administration in mice. In vivo biodistribution of the drug in mice was assessed by a radiolabeling technique using radioiodinated mirtazapine ( 131 I-MZP). Results showed that intranasal MZP-LNCs were able to deliver higher amount of MZP to the brain with less drug levels in blood when compared to the MZP solution after IV and IN administration. Moreover, the percentage of drug targeting efficiency (%DTE) of the optimized MZP-LNCs was 332.2 which indicated more effective brain targeting by the intranasal route. It also had a direct transport percentage (%DTP) of 90.68 that revealed a paramount contribution of the nose to brain pathway in the drug delivery to the brain. Graphical Abstract

The Role of Chlorella vulgaris in Attenuating Infertility Induced by Cadmium Chloride via Suppressing Oxidative Stress and Modulating Spermatogenesis and Steroidogenesis in Male Rats - Mayada R Farag; Nesma I. El-naseery; Eman I. El behery; Doaa S. Nouh; Amany El-Mleeh; Ismail M.A. Mostafa; Mahmoud Alagawany; Alessandro Di Cerbo; Mahmoud M. Azzam; Suzan A. Mawed (Biological Trace Element Research, 2024)

Polycyclic aromatic hydrocarbons in ship breaking area and associated ecological risk assessment: evidence from the Sitakund ship-breaking area in Bangladesh - Suman Barua; Rajesh Mutsuddi; Sabrina Sultana; Md. Samrat Mohay Menul Islam; Suman Das; Mohammad Mostafa; Dipankar Chakraborty; Ismail M. M. Rahman (Environmental Science and Pollution Research, 2024)

Unlocking the functional potential of Nitraria schoberi extracts using chemical fingerprinting, biological efficiencies, in silico and network pharmacological approaches - Stefano Dall’Acqua; Sakina Yagi; Stefania Sut; Abdullahi Ibrahim Uba; Evren Yildiztugay; Ismail Koyuncu; Ozgur Yuksekdag; Sathish Kumar M. Ponniya; Ashokkumar Jayavel; Gokhan Zengin (Food Bioscience, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

MitoQ and its hyaluronic acid–based nanopreparation mitigating gamma radiation–induced intestinal injury in mice: alleviation of oxidative stress and apoptosis - Mohamed Dawoud; Khalid M. Attallah; Ismail T. Ibrahim; Heba M. Karam; Ayman A. Ibrahim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Groundwater spring potential mapping: Assessment the contribution of hydrogeological factors - Rui Zhao; Chenchen Fan; Alireza Arabameri; M Santosh; Lal Mohammad; Ismail Mondal (Advances in Space Research, 2024)

Mucoadhesive Chitosan Composite Sponge as a Carrier for β-Sitosterol Cubosomes for Thermal Burn Treatment - Abeer Khattab; Soha Ismail; Areeg M. Abd-Elrazek (AAPS PharmSciTech, 2024)
Our study aimed to explore the potential of using nanostructured lipid carriers (NLCs) to enhance the topical administration of β-sitosterol, a bioactive that is poorly soluble in water. Here, we have taken advantage of the unique characteristics that cubosomes have to provide as a drug delivery system. These characteristics include a large surface area, thermal stability, and the capacity to encapsulate molecules that are hydrophobic, amphiphilic, and hydrophilic. The cubosomal formulation was optimized by building a central composite design. The optimum dispersion exhibited a particle size of 88.3 nm, a zeta potential of -43, a polydispersity index of 0.358, and drug entrapment of 95.6%. It was composed of 15% w/w oleic acid and 5% w/w pluronic F127. The optimized cubosome dispersion was incorporated into a sponge formulation. The optimized cubosome sponge achieved a higher drug release compared with the cubosome dispersion. The SEM micrograph of the selected sponge showed that it has an interwoven irregular fibrous lamellar structure with low density and high porosity. The in-vivo data revealed that topical application of the β-sitosterol cubosomal sponge showed significant higher wound closure percentage relative to the β-sitosterol product (Mebo)®. Graphical Abstract

Investigating the comparative utility of ECMWF precipitation forecasts as an alternative to reanalysis data - Muhammad Amjad; M. Tugrul Yilmaz; Ismail Yucel; Koray K. Yilmaz; Kurtuluş Öztürk (Hydrological Sciences Journal, 2024)

Answer to comments on "Accuracy of Rapid Emergency Medicine Score and Sequential Organ Failure Assessment Score in predicting acute paraphenylenediamine poisoning adverse outcomes" - Ghada N. El-Sarnagawy; Mona M. Ghonem; Marwa A. Abdelhameid; Omaima M. Ali; Asmaa M. Ismail; Doaa M. El Shehaby (Environmental Science and Pollution Research, 2024)

Integration of internet of things (IoT) technology in the design model of sustainable green building spaces - Yuchen Wang; Lu Liu; Shubham Sharma; Fuad A. Awwad; M. Ijaz Khan; Emad A. A. Ismail (Environment, Development and Sustainability, 2024)

A comprehensive study on chemical and biological profiles of Algerian Azadirachta indica (A. Juss) - Ahmed Boukeloua; Soudani Leila; Hamdi Bendif; Ahmed M. Mustafa; Mehmet Boga; Maria Luísa Serralheiro; Mustafa Abdullah Yilmaz; Ismail Yener; Stefania Garzoli (Phytochemistry Letters, 2024)

Antifouling macrocyclic-engineered PVDF membrane for the low-pressure separation of surfactant-stabilized oily wastewater - Najah F.H. Alrasheedi; Ismail Abdulazeez; Nadeem Baig; Billel Salhi; Hamza A. Asmaly; Shamsuddeen A. Haladu; Asma M. Elsharif (Journal of Environmental Chemical Engineering, 2024)

Adsorptive removal of heavy metals from aqueous solutions: Progress of adsorbents development and their effectiveness - Usman M. Ismail; Muhammad S. Vohra; Sagheer A. Onaizi (Environmental Research, 2024)

Characterization of the Ayran Made with Commercial Probiotic Cultures for Fatty Acids, Cholesterol, Folic Acid Levels, and Anti-Oxidative Potential - Ola M. A. K. Shalabi; Amina M. Hassan; Magdy M. Ismail; Reham K. El-Menawy (Probiotics and Antimicrobial Proteins, 2024)
Ayran is a salted drinkable fermented milk food which consumed in many countries around the world. In this study, some chemical parameters were determined to evaluate the healthy properties of ayran prepared using various commercial probiotic cultures. Four treatments of ayran were made from cow’s milk and using classic yogurt culture ( L. delbrueckii subsp. bulgaricus and Streptococcus thermophilus ) [T1], ABT-5 culture ( L. acidophilus, Bifidobacterium and S. thermophilus ) [T2], exopolysaccharide producing culture (EPS-producing, L. delbrueckii subsp. bulgaricus and S. thermophilus ) [T3], and EPS-producing culture + Bifidobacterium animalis subsp. lactis BB12 (mixture culture) [T4]. Treatment 1 had the highest acidity, acetaldehyde, and diacetyl values. Using probiotic [T2] or mixture cultures [T4] reduced saturated fatty acids by 1.97% and increased monounsaturated and polyunsaturated fatty acids of ayran by 4.94 and 5.72%, respectively. Also, the levels of oleic acid (omega-9), linoleic acid (omega-6), and α-linolenic acid (omega-3) increased in ayran produced using probiotic or mixture cultures. Sample T4 was highly richer in the value of antioxidant activity (27.62%) and folic acid (0.1566 mg/100 g) whereas possessed the lowest cholesterol amount (8.983 mg/100 g). Mixture culture (EPS-producing culture + Bifidobacterium animalis subsp. lactis BB12) is a good starter to improve the healthy and nutritional characteristics of bio-ayran.

Evaluation of TRMM 3B43 V7 precipitation data in varied Moroccan climatic and topographic zones - Mourad Aqnouy; Younes Ommane; Abdessalam Ouallali; Abdelali Gourfi; Gebiaw T. Ayele; Yassine El Yousfi; Ismail Bouizrou; Jamal Eddine Stitou El Messari; Amin Zettam; Assefa M. Melesse; Christopher E. Ndehedehe; Mohamed Abioui; et al. (Mediterranean Geoscience Reviews, 2024)

Investigation on the key mix design parameters of slag-based geopolymer concrete - Nada M. Nagy; Ismail Amer; El-Sayed A. R. Nasr; Mohamed Kohail (Innovative Infrastructure Solutions, 2024)

Tracking of uranium and thorium natural distribution in the chemical fractions of the Nile Valley and the Red Sea phosphorites, Egypt - Sami K. Aita; Marwa M. Abdel-Azeem; Hanaa A. Abu Khoziem; Gehan A. Aly; Nasser M. Mahdy; Ahmed M. Ismail; Hani H. Ali (Carbonates and Evaporites, 2024)
The present study aims to elucidate the possible sources of uranium and thorium content in the Campanian–Maastrichtian phosphorites from the Duwi Formation in the Nile Valley and Red Sea by conducting facies analysis and sequential leaching method. Nile Valley samples were collected from the El-Sibaiya East area, while those of the Red Sea were collected from two locations: Hamadat and Zug El Bahar. The petrographic investigation revealed that the Sibaiya East phosphorites exhibit peloidal bioclastic phospharenite–phospharudite microfacies, while Hamadat and Zug El Bahar phosphorites display peloidal bioclastic phosphalutite and silicified peloidal bioclastic phospharenite microfacies, respectively. Besides, U–Th bearing accessory minerals, such as zircon and monazite occur in Sibaiya East phosphorites. Thorium is present in Zug El Bahar phosphorites as minute accumulations associating apatite and quartz. Moreover, uranium is found with vanadium and iron as fine patches in the Sibaiya East phosphorite, and as small disseminations associated with Ca and Si in the Hamadat phosphorite. The X-ray diffraction shows that the investigated phosphorites are essentially built up of hydroxyl apatite Ca 5 (PO 4 ) 3 (OH) and quartz SiO 2. To accurately evaluate the bioavailability and mobility of uranium and thorium in the investigated phosphorites, it was necessary to identify the overall concentration and the various chemical forms of these elements by a five-step sequential leaching technique. The results indicate that Th and U are more abundant in the Red Sea phosphorites than in the Nile Valley phosphorites. Furthermore, Th is not bio-available and it is mostly found in the residue as Th-bearing minerals. Uranium, unlike Th is bio-available and fractionates among all fractions, indicating that U accumulation is the result of various diagenetic processes.

Comparison of crude nano-hydroxyapatite extracted from calcified seaweed in terms of composition, antibacterial activity, and cytotoxicity - Ghada F. El-Said; Gehan M. El Zokm; Amany El-Sikaily; Mona M. Ismail (Environmental Nanotechnology, Monitoring & Management, 2024)

Influence of coupling air conditioner with hybrid PCMs on building interior conditions and consumed power: Experimental investigation - M. Ismail; Hamdy Hassan (Energy and Buildings, 2024)

Evaluation of the fully coupled WRF and WRF-Hydro modelling system initiated with satellite-based soil moisture data - Eren Duzenli; Ismail Yucel; M. Tugrul Yilmaz (Hydrological Sciences Journal, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Improving complementary feeding in low- and middle-income countries: a review of crayfish’s nutritive and health values - Halid S Adegbusi; Amin Ismail; Norhaizan M Esa; Zulfitri AM Daud; Nurul HM Shukri (Current Opinion in Food Science, 2024)

From diagnosis to resistance: a symphony of miRNAs in pheochromocytoma progression and treatment response - Elsayed G. E. Elsakka; Ahmed Elshafei; Mohamed A. Elkady; Amr Mohamed Yehia; Ahmed I. Abulsoud; Reem K. Shahin; Nourhan M. Abdelmaksoud; Samy Y. Elkhawaga; Ahmed Ismail; Mahmoud Mohamed Mokhtar; Mahmoud A. Elrebehy; Maghawry Hegazy; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Silica nanoparticles alleviate the immunosuppression, oxidative stress, biochemical, behavioral, and histopathological alterations induced by Aeromonas veronii infection in African catfish (Clarias gariepinus) - Heba H. Mahboub; Wafaa M. Gad; Enas K. Aziz; Mona Abdelghany Nasr; Esraa M. Fahmy; Dina Mohamed Mansour; Nesma Rasheed; Hanaa S. Ali; Sameh H. Ismail; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2024)
In the aquaculture industry, silica nanoparticles (SiNPs) have great significance, mainly for confronting diseases. Therefore, the present study aims to assess the antibacterial efficiency of SiNPs as a versatile trial against Aeromonas veronii infection in African catfish ( Clarias gariepinus ). Further, we investigated the influence of SiNPs in palliating the immune-antioxidant stress biochemical, ethological, and histopathological alterations induced by A. veronii . The experiment was conducted for 10 days, and about 120 fish were distributed into four groups at random, with 30 fish each. The first group is a control that was neither exposed to infection nor SiNPs. The second group (SiNPs) was vulnerable to SiNPs at a concentration of 20 mg/L in water. The third group was experimentally infected with A. veronii at a concentration of 1.5 × 10 7 CFU/mL. The fourth group ( A. veronii + SiNPs) was exposed to SiNPs and infected with A. veronii . Results outlined that A. veronii infection induced behavioral alterations and suppression of immune-antioxidant responses that appeared as a clear decline in protein profile indices, complement 3, lysozyme activity, glutathione peroxidase, and total antioxidant capacity. The kidney and liver function biomarkers (creatinine, urea, alkaline phosphatase, and alanine aminotransferase) and lipid peroxide (malondialdehyde) were substantially increased in the A. veronii group, with marked histopathological changes and immunohistochemical alterations in these tissues. Interestingly, the exposure to SiNPs resulted in a clear improvement in all measured biomarkers and a noticeable regeneration of the histopathological changes. Overall, it will establish that SiNPs are a new, successful tool for opposing immunological, antioxidant, physiological, and histopathological alterations induced by A. veronii infection.

The effect of thyroxine (T4) and goitrogen on growth, liver, thyroid, and gonadal development of red tilapia (O. mossambicus × O. urolepis hornorum) - Rania F. Ismail; Samira S. Assem; Hossam E. R. Sharaf; Ashraf A. M. Zeitoun; Tarek M. A. Srour (Aquaculture International, 2024)
This study provides comprehensive results on the growth, thyroid, liver, and gonadal condition, maturity, and sex ratio in red tilapia exposed to exogenous thyroxine and goitrogen. One-gram red tilapia fingerlings were reared in three groups: control, thyroxine (T4) (10 nM), and goitrogen (sodium perchlorate, 30 mg/L) for 30 days, followed by 30 days without treatment. After the first 30 days of treatment, liver enzymes and whole-body T4 and T3 were assessed. The gonadosomatic index (GSI), maturity stages and sex ratio were examined. Final body weight (FBW), weight gain (WG), specific growth rate (SGR), and survival rate were also measured. Results revealed insignificant differences among groups in FBW, WG, SGR, and GSI, but the hepatosomatic index (HSI) of the goitrogen group significantly increased. Exogenous thyroxine significantly increased whole-body T4. Liver enzymes were not affected. Thyroid follicles of the thyroxine-treated fish showed large thyroid follicles, whereas the goitrogen-treated fish showed degenerated and negligible thyroid follicles. Liver tissue of the thyroxine-treated fish group displayed a few fat vacuoles, while perchlorate-treated fish showed hydrophobic degenerated hepatocytes. At the end of 60 days, the thyroxine treatment significantly increased FBW, WG, SGR, female GSI, and male hepatosomatic index (HSI). Perchlorate and thyroxine exposure, respectively, skewed sex ratios toward males and females. Exogenous T4 enhanced the maturity stages of both females and males, while perchlorate exposure delayed their gonadal ripening. These results validated the significant role of T4 during early life of red tilapia as it could improve the growth and maturity, and affect its sex ratio, while T4 insufficiency could alter these factors.

New bithiophene derivative attenuated Alzheimer’s disease induced by aluminum in a rat model via antioxidant activity and restoration of neuronal and synaptic transmission - Kholoud AbdEl-Raouf; Hussein S.H. Farrag; Rashed Rashed; Mohamed A. Ismail; Monir A. El-Ganzuri; Wael M. El-Sayed (Journal of Trace Elements in Medicine and Biology, 2024)

WITHDRAWN: Trace metals translocation from soil to plants: Health risk assessment via consumption of vegetables in the urban sprawl of a developing country - KM Shamsul Haque; Md Saiful Islam; Sujat Ahmed; Md Zillur Rahman; Debolina Halder Hemy; Md Towhidul Islam; Md Kamal Hossain; Md Rafiq Uddin; Abu Reza Md Towfiqul Islam; Md Yousuf Mia; Zulhilmi Ismail; Abdullah Al Bakky; et al. (Food and Chemical Toxicology, 2024)

Patterned hydrophobic gas diffusion layers for enhanced water management in polymer electrolyte fuel cells - F. Calili-Cankir; E.M. Can; D.B. Ingham; K.J. Hughes; L. Ma; M. Pourkashanian; S.M. Lyth; M.S. Ismail (Chemical Engineering Journal, 2024)

Untangling the taxonomic ambiguities of the spotted seerfish Scomberomorus guttatus with the description of a new species from India - Eruppakkottil M. Abdussamad; Thomas Toji; Amalraj M. R. Margaret; Kalappurakkal G. Mini; Kothanahally M. Rajesh; Pokkathappada A. Azeez; Vinothkumar Ramar; Thayichira B. Retheesh; Athikkattil M. Abbas; Ismail Shihab; Sneha M. George; Rohith Prathibha; et al. (Journal of Fish Biology, 2024)
Scomberomorus guttatus has been subjected to a series of synonym assignations over the years. Its taxonomy has been mired with ambiguities due to the greater‐than‐average morphological variations observed in samples from different regions. An integrated taxonomic revision with molecular support indicated that the species that was thought to be a single entity, in reality, is a complex of three distinct species. They are morphologically distinct with respect to the body depth and elongation, cephalic morphometry, and meristic characteristics. Otolith morphometry and phylogenetic evidence further established the taxonomic divergence within the spotted seerfish complex. The phylogenetic characteristic as indicated by the mitochondrial Cytochrome c Oxidase subunit I (COI) sequence unveiled that S. guttatus had a high intraspecific divergence of 11.1% from its two identical congeners and a divergence of 2.34% between the congeners, indicating scope for categorizing them as separate species. Based on the morphological and molecular evidence, S. guttatus is redescribed; the senior synonym Scomberomorus leopardus is resurrected as a valid species; and a new species Scomberomorus avirostrus n. sp. is described with keys for species distinction.

Nanofibrillated cationic cellulose derivatives as flocculants for domestic wastewater treatment - Margarida Ribau Teixeira; Abdullah Ismail; Bruno Medronho; Luís Alves; Jorge F.S. Pedrosa; Paulo J.T. Ferreira; Vânia Serrão Sousa; Ana M. Rosa da Costa (Journal of Water Process Engineering, 2024)

Synthesis of mesoporous p-CuAl2O4/n-YVO4 heterojunction nanocomposites and their utilization as effective photocatalysts for hydrogen evolution - Soha M. Albukhari; Adel A. Ismail (Fuel, 2024)

Xylanase immobilization using activated carrier of gellan gum-agar beads: Improved stability and catalytic activity for the production of antioxidant and anti-proliferative xylooligosaccharides - Marwa I. Wahba; Shaymaa A. Ismail; Amira A. Hassan; Sekena H. Abdel-Aziem; Aziza M. Hassan; Shaimaa A. Nour (Biocatalysis and Agricultural Biotechnology, 2024)

Correction: Activated Carbon from Sugarcane Bagasse Pyrolysis for Heavy Metals Adsorption - S. M. Kakom; N. M. Abdelmonem; I. M. Ismail; A. A. Refaat (Sugar Tech, 2024)

Chemoprevention by Microencapsulated Lactiplantibacillus Plantarum LAB12 Against Orthotopic Colorectal Cancer Mice is Associated with Apoptosis and Anti-angiogenesis - Ismail M. Fareez; Siong Meng Lim; Kalavathy Ramasamy (Probiotics and Antimicrobial Proteins, 2024)

Eco-friendly approach to decrease the harmful effects of untreated wastewater on growth, yield, biochemical constituents, and heavy metal contents of carrot (Daucus carota L.) - Abdulrahman Alhashimi; Ayman Abdelkareem; Mohamed A. Amin; Abdelatti I. Nowwar; Amr Fouda; Mohamed A. Ismail; Abeer E. Mustafa; Maha Alharbi; Amr Elkelish; Abdelrahman M. Sayed; Hanan A. Said (Environmental Science and Pollution Research, 2024)

The anti-bacterial efficacy of zinc oxide nanoparticles synthesized by Nelumbo nucifera leaves against Clostridium perfringes challenge in Oreochromis niloticus - Rowida E. Ibrahim; Moustafa M.S. Fouda; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Gamal A. Salem; Ahmed Asaid Elkady; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture, 2024)

Effect of the addition of platelet-rich plasma to Boer buck semen on sperm quality and antioxidant activity before and after cryopreservation and in vivo fertility - Maha S. Salama; Ahmed M. Shehabeldin; Mohey A. Ashour; Muath Q. Al-Ghadi; Basma H. Marghani; Ismail El-kon; Mustafa Shukry (Small Ruminant Research, 2024)

Nelumbo nucifera synthesized selenium nanoparticles modulate the immune-antioxidants, biochemical indices, and pro/anti-inflammatory cytokines pathways in Oreochromis niloticus infected with Aeromonas veronii - Rowida E. Ibrahim; Gehad Elshobaky; Mohamed ElHady; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Nasreddin R. Rhouma; Suzan K. Murad; Engy Mohamed Mohamed Yassin; Tarek Khamis; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman (Fish & Shellfish Immunology, 2024)

Minimizing CO2 emissions by photocatalytic CO2 reduction to CH3OH over Li2MnO3/WO3 heterostructures under visible illumination - Soha M. Albukhari; L.A. Al-Hajji; Adel A. Ismail (Environmental Research, 2024)

Muscovite clay for methylene blue removal: advanced optimization and Al-guided breakthroughs—an independent application from prior antibiotic removal investigation - Raouia Lebbihi; Larbi Haddad; Chouaib Labiod; Ahmed Musaad Ismail; Soumaia M’Nassri; Rajouene Majdoub (Environmental Science and Pollution Research, 2023)

Contamination and ecological risk assessment of Cr, As, Cd and Pb in water and sediment of the southeastern Bay of Bengal coast in a developing country - Md. Saiful Islam; Md. Towhidul Islam; Uttam Biswas Antu; Md. Sadik Mahmud Saikat; Zulhilmi Ismail; Shamsuddin Shahid; Abu Reza Md. Towfiqul Islam; Mir Mohammad Ali; Abdullah Al Bakky; Sujat Ahmed; Khalid A. Ibrahim; Rahmah N. Al-Qthanin; et al. (Marine Pollution Bulletin, 2023)

An explainable two-stage machine learning approach for precipitation forecast - Ali Ulvi Galip Senocak; M. Tugrul Yilmaz; Sinan Kalkan; Ismail Yucel; Muhammad Amjad (Journal of Hydrology, 2023)

Interactive effects of cadmium and titanium dioxide nanoparticles on hepatic tissue in rats: Ameliorative role of coenzyme 10 via modulation of the NF-κB and TNFα pathway - Yasmina M. Abd-Elhakim; Mohamed M.M. Hashem; Khaled Abo-EL-Sooud; Mohamed R. Mousa; Ahmed M. Soliman; Samar M. Mouneir; Sameh H. Ismail; Bayan A. Hassan; Hayat H.M. El-Nour (Food and Chemical Toxicology, 2023)

Elettaria cardamomum seed extract synthesized silver nanoparticles for efficient catalytic reduction of toxic dyes - Muhammad Zahid; Abdul Sattar M. Segar; Shaymaa Al-Majmaie; A.H. Shather; Muhammad Farooq Khan; Arnold C. Alguno; Rey Y. Capangpangan; Ahmed Ismail (Environmental Nanotechnology, Monitoring & Management, 2023)

Extraction of lignin from sugarcane trash and its potency as biosurfactant - Azizatul Karimah; Izdihar Khosani Hani; Raden Permana Budi Laksana; Maya Ismayati; Nissa Nurfajrin Solihat; Fahriya Puspita Sari; Ismail Budiman; Muhammad Ghozali; Obie Farobie; Deded Sarip Nawawi; Muhammad Adly R. Lubis; M. Hazwan Hussin; et al. (Bioresource Technology Reports, 2023)

Field Evaluation of Certain Compounds Against Spodoptera littoralis (Lepidoptera: Noctuidae): Their Impact on its Predator, Chrysoperlacarnea (Neuroptera: Chrysopidae) - Seham Mansour Ismail; A. S. H. Abo-Shanab; M. A. El-Malla (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Synthesis, Antioxidant, Bactericidal and Antihemolytic Activity of Al2O3 and SnO2 Nanoparticles - Amulya Giridasappa; M. Ismail Shareef; S. M. Gopinath; Dinesh Rangappa; Prasanna Doddakunche Shivaramu; Chetana Sabbanahalli (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Oncoinformatic screening of the gene clusters involved in the HER2-positive breast cancer formation along with the in silico pharmacodynamic profiling of selective long-chain omega-3 fatty acids as the metastatic antagonists - A K M Helal Morshed; Salauddin Al Azad; Md. Abdur Rashid Mia; Mohammad Fahim Uddin; Tanzila Ismail Ema; Rukaiya Binte Yeasin; Sanjida Ahmed Srishti; Pallab Sarker; Rubaita Younus Aurthi; Farhan Jamil; Nure Sharaf Nower Samia; Partha Biswas; et al. (Molecular Diversity, 2023)

Chemical composition, antioxidant, herbicidal and antifungal activities of leaf essential oils from three Tunisian Eucalyptus species - Habiba Kouki; Ismail Amri; Mouna Souihi; Ylenia Pieracci; Imen Trabelsi; Lamia Hamrouni; Guido Flamini; Ann M. Hirsch; Yassine Mabrouk (Journal of Plant Diseases and Protection, 2023)

Evaluation of the response of phytoplankton communities to heavy metal stresses using multi-statistical approaches, Alexandria coast, Egypt - M. M. Ismail; G. M. El Zokm (International Journal of Environmental Science and Technology, 2023)
This is the first study to investigate the antioxidant response of the phytoplankton community to heavy metal stress in the open sea. The levels of Cu, Zn, Cd, Mn, Pb, and Fe were determined in the phytoplankton community and water in Abu Talat (AT), and El Dekhella Harbour (DH), Alexandria coast during spring 2018 and autumn 2019. Furthermore, the changes in phytoplankton abundance, the bioconcentration factor (BCF), the metal pollution index (MPI), and the pollution load index (PLI) were used to assess pollution status. The phytoplankton density in the DH stations was 17–42 folds higher than in the AT. The order of BCF during spring was Fe > Zn > Pb > Cu > Mn > Cd. However, Fe > Zn > Mn > Cu > Pb > Cd was found in both areas during the autumn. The BCF, MPI, and PLI of the phytoplankton community revealed that DH is more polluted than AT. The phenol, 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity and total antioxidant activity of the phytoplankton communities achieved higher values in DH than in AT stations, in response to heavy metal stresses. Principal component analysis was performed to follow pollution sources, suggesting that station 3 in both seasons was a hot spot because of stagnant water. A correlation matrix indicated that phenol and DPPH interacted positively in both locations during the two seasons. Analysis of variances with replicate tests on heavy metals in phytoplankton revealed significant seasonal differences across the two areas at a significance level < 0.05.

Exposure of road users to the traffic noise in urban environment: insights from a mega metropolitan city - A. Ahmed; F. Khan; M. Ahmed; M. A. Ismail; N. Ahmad (International Journal of Environmental Science and Technology, 2023)

Rhein methotrexate-decorated solid lipid nanoparticles altering adjuvant arthritis progression through endoplasmic reticulum stress-mediated apoptosis - Wessam M. El-Refaie; Mostafa S. Ghazy; Fady A. Ateyya; Eman Sheta; Mohanad Y. Shafek; Mahmoud S. Ibrahim; Mahmoud MA. Ismail; Mennatallah A. Gowayed (Inflammopharmacology, 2023)
Methotrexate (MTX) and diacerein (DIA) are two of the most potent disease-modifying anti-rheumatic drugs used for the treatment of rheumatoid arthritis (RA). DIA has reflected some GIT and hepatobiliary manifestations in numerous cases. It undergoes biotransformation in the liver into the active metabolite rhein (RH) which is characterized by its excellent anti-inflammatory activity and lower side effects. However, RH's hydrophobic nature and low bioavailability do not encourage its use in RA. The current study aims to use RH in combination with MTX in targeted solid lipid nanoparticles (RH-MTX-SLNs) for better effectiveness and shadowing light on its possible mechanistic pathways. RH-MTX-SLNs were prepared and assessed for their quality attributes. The effect of the formulation was assessed in-vivo in an adjuvant arthritis animal model investigating the role of the endoplasmic reticulum stress (ERS)-induced apoptosis. Results revealed that RH-MTX-SLNs were in the suitable nanosized range with high negative zeta potential indicating good stability. In-vivo, RH-MTX-SLNs significantly improved all measured inflammatory and arthritic markers, confirmed by electron microscopy and histology examination of the joints. Besides, the formulation was able to alter the ERS-mediated apoptosis. In conclusion, RH-MTX-SLNs can represent a promising therapeutic approach for RA showing significant anti-arthritic activity. Graphical abstract

Promising effect of Geranium robertianum L. leaves and Aloe vera gel powder on Aspirin®-induced gastric ulcers in Wistar rats: anxiolytic behavioural effect, antioxidant activity, and protective pathways - Basma M. Bawish; Mariem A. Rabab; Safaa T. Gohari; Marwa S. Khattab; Naglaa A. AbdElkader; Samar H. Elsharkawy; Amr M. Ageez; Manal M. Zaki; Shaimaa Kamel; Eman M. Ismail (Inflammopharmacology, 2023)
Background Many drugs have been restricted in the treatment of gastric ulcers (GU). So, herbal medicines are now in great demand for their better cultural acceptability, compatibility, and minimal side effects. Therefore, our study aimed to assess the protective efficacy of Aloe vera gel and Geranium robertianum extracts against Aspirin®-induced GU in Wistar rats. Methods Antioxidant activity and chemical composition of both herbs were analysed. Then, we divided forty female Wistar rats into five groups: a negative control group, a positive control group of Aspirin®-induced GU, and pretreated groups with Aloe Vera , geranium, and Famotidine (reference drug). The locomotor disability, anxiety-like behaviour, and ultrasonography were assessed. Ultimately, scarification of animals to determine gastric juice pH and ulcer index. Then the collection of stomach and liver for histopathological and immunohistochemical examinations, besides tracing the oxidative stress biomarkers and related genes. Results High content of polyphenols was revealed in both extracts. The pretreatment with Aloe vera gel and geranium showed significant antioxidant activities with free radical scavenging and ferric-reducing power (FRAP). Moreover, they improved the stomach architecture and alleviated anxiety-like behaviour and motor deficits. They significantly reduced the expression of proinflammatory cytokine (TNF-α), inflammatory, and oxidative stress genes (NF-KB, HO-1, Nrf-2) while increasing the Keap-1 in gastric mucosa. Conclusion Data presented a significant protective effect of Aloe vera gel and geranium against Aspirin®-induced GU; they reduced gastric mucosal injury with potential anxiolytic effects through their anti-inflammatory and antioxidant properties. Therefore, they may be considered promising agents for preventing or treating gastric ulceration.

Valorization and co-treatment of hazardous petroleum refinery oily sludge and sewage associated with bioenergy recovery in tubular microbial fuel cell - Rusul M. Khazaal; Zainab Z. Ismail (Environmental Science and Pollution Research, 2023)

An integrated strategy combining UPLC-MS/MS, chemometrics, molecular docking, and molecular dynamics simulation for metabolic profiling of onion (Allium cepa L.) cultivars and unravelling potential anti-COVID-19 metabolites - Mariam M. Elattar; Hala M. Hammoda; Doaa A. Ghareeb; Mostafa F. El-Hosseny; Mohamed G. Seadawy; Ismail Celı̇k; Reham S. Darwish; Hend M. Dawood (South African Journal of Botany, 2023)

How sustainable and profitable are large-scale hydrogen production plants from CH4 and H2S? - Sawsan M. Ali; Ismail I.I. Alkhatib; Ahmed AlHajaj; Lourdes F. Vega (Journal of Cleaner Production, 2023)

Appraisals on the chemical characterization and biological potentials of Ranunculus constantinopolitanus extracts using chromatographic, computational, and molecular network approaches - Irina Lazarova; Gokhan Zengin; Diletta Piatti; Abdullahi Ibrahim Uba; Gianni Sagratini; Giovanni Caprioli; Gizem Emre; Sathish Kumar M. Ponniya; Kannan RR. Rengasamy; Nicholas Joseph Paradis; Ismail Koyuncu; Fatma Şeker; et al. (Food and Chemical Toxicology, 2023)

Tiagabine and zonisamide differentially regulate the glial properties in an astrocyte-microglia co-culture model of inflammation - Fatme Seval Ismail; Pedro M. Faustmann; Eckart Förster; Franco Corvace; Timo Jendrik Faustmann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Due to the role of astrocytes and microglia in the pathophysiology of epilepsy and limited studies of antiseizure medication (ASM) effects on glial cells, we studied tiagabine (TGB) and zonisamide (ZNS) in an astrocyte-microglia co-culture model of inflammation. Different concentrations of ZNS (10, 20, 40, 100 µg/ml) or TGB (1, 10, 20, 50 µg/ml) were added to primary rat astrocytes co-cultures with 5–10% (M5, physiological conditions) or 30–40% (M30, pathological inflammatory conditions) microglia for 24 h, aiming to study glial viability, microglial activation, connexin 43 (Cx43) expression and gap-junctional coupling. ZNS led to the reduction of glial viability by only 100 µg/ml under physiological conditions. By contrast, TGB revealed toxic effects with a significant, concentration-dependent reduction of glial viability under physiological and pathological conditions. After the incubation of M30 co-cultures with 20 µg/ml TGB, the microglial activation was significantly decreased and resting microglia slightly increased, suggesting possible anti-inflammatory features of TGB under inflammatory conditions. Otherwise, ZNS caused no significant changes of microglial phenotypes. The gap-junctional coupling was significantly decreased after the incubation of M5 co-cultures with 20 and 50 µg/ml TGB, which can be related to its anti-epileptic activity under noninflammatory conditions. A significant decrease of Cx43 expression and cell–cell coupling was found after the incubation of M30 co-cultures with 10 µg/ml ZNS, suggesting additional anti-seizure effects of ZNS with the disruption of glial gap-junctional communication under inflammatory conditions. TGB and ZNS differentially regulated the glial properties. Developing novel ASMs targeting glial cells may have future potential as an “add-on” therapy to classical ASMs targeting neurons.

Time-independent bias correction methods compared with gauge adjustment methods in improving radar-based precipitation estimates - Kaveh P. Yousefi; M. Tugrul Yilmaz; Kurtuluş Öztürk; Ismail Yucel; Koray K. Yilmaz (Hydrological Sciences Journal, 2023)

Synergistic effect of Bacillus subtilis and benzothiadiazole (Bion®) on the suppression of Fusarium oxysporum and the enhancement of disease resistance in Capsicum annuum - Kamal A. M. Abo-Elyousr; Nashwa M.A Sallam; Magdy A. A Mousa; Muhammad Imran; Ismail R. Abdel-Rahim (Journal of Plant Pathology, 2023)

Evaluation of newly designed flushing techniques for on-site remediation of arsenic-contaminated excavated debris - Shafiqur Rahman; Makoto Saito; Shoji Yoshioka; Shengbin Ni; Kuo H. Wong; Asami S. Mashio; Zinnat A. Begum; Ismail M. M. Rahman; Akio Ohta; Hiroshi Hasegawa (Environmental Science and Pollution Research, 2023)

Fabrication of Co3O4/Co3S4/CNTs for photocatalytic treatment of wastewater under xenon lamp - Manal F. Abou Taleb; Alizah Jabeen; Faten Ismail Abou El Fadl; Hanan A. Albalwi; Mohamed M. Ibrahim (Environmental Science and Pollution Research, 2023)

Hydrophilic polydopamine/polyvinylpyrrolidone blended polyphenylsulfone hollow fiber membranes for the removal of arsenic-V from water - Mithun Kumar; Arun M. Isloor; M.C.S. Nayak; Somasekhara Rao Todeti; Mahesh Padaki; Ahmad Fauzi Ismail (Journal of Environmental Chemical Engineering, 2023)

Growth characteristics and yield of contrasting rice genotypes under long-term stagnant flooding - Guanglong Zhu; Hao Wu; Yutiao Chen; Satyen Mondal; Abdelbagi M. Ismail (Field Crops Research, 2023)

Mobile Signaling Peptides: Secret Molecular Messengers with a Mighty Role in Plant Life - Deepu Pandita; Javaid Akhter Bhat; Shabir Hussain Wani; Abdelaleim Ismail ElSayed; Ghazala Nawaz; Soumya Mukherjee; Vincent P. Reyes; Anuj Kumar; Qiufang Shen; Showkat Ahmad Ganie; Kadambot H. M. Siddique (Journal of Plant Growth Regulation, 2023)
Adaptive mechanisms for unfavorable environments have evolved in plants for thousands of generations, primarily in the form of endogenous chemical signals and the coordination of physiological processes. Signaling peptides (SPs) are diverse molecular messengers in various stress responses which have been identified in different plant families. SPs are recognized by the membrane-localized receptors and co-receptors, leading to downstream signaling for various plant responses. Progress in in silico analysis, along with other factors, has increased our understanding of the signaling peptide-mediated regulatory mechanisms underlying the entire plant life cycle. SPs mediate both long-distance (root-to-shoot-to-root) and local cell–cell communication via vascular system to communicate and coordinate with plant organs at distant locations. During abiotic stress, SPs inside plant cells perceive stress signals and transfer information at short and long physiological ranges through the signal transduction pathway, causing stress-responsive gene expression. SPs interact with pathogens and mediate cell-to-cell communication via signaling pathways. There are intriguing relationships between phytohormones and the secondary signaling cascades which are mediated by SPs. During biotic or abiotic stress, different peptides trigger jasmonic acid, ethylene, and ABA signaling, involving several secondary messengers. These messengers mediate the stress response via shared signaling components of ROS, Ca 2+ , and MAPKs, and they modify the gene expression for different phytohormones. In this review, we highlight current knowledge on the role of signaling peptides in plant adaptation, growth, and development. We aim to analyze the SP-receptor interactions and the significance of crosstalk between a few sample SPs and phytohormones. Potential directions on how scientists can use this information for crop improvement are also suggested.

Thymus satureioides Coss. combats oral ulcer via inhibition of inflammation, proteolysis, and apoptosis - Mahmoud H. Elbatreek; Ayman M. Fathi; Ismail Mahdi; Mohamed A. O. Abdelfattah; Mona F. Mahmoud; Mansour Sobeh (Inflammopharmacology, 2023)

Synergistic effects of suppress resistance of cypermethrin and chlorpyrifos in the cotton leafworm, Spodoptera littoralis (Boisduval) populations in Egypt - Seham M. Ismail (International Journal of Tropical Insect Science, 2023)

Interactions among Sodalis, Glossina pallidipes salivary gland hypertrophy virus and trypanosomes in wild Glossina pallidipes - Deusdedit J. Malulu; Hamisi S. Nyingilili; Delphina Edward; Peter Lucas; Ismail W. R. Taifa; Imna I. Malele; Adly M. M. Abd-Alla (International Journal of Tropical Insect Science, 2023)

Comparison of two newly suggested power, refrigeration, and hydrogen production, for moving towards sustainability schemes using improved solar-powered evolutionary algorithm optimization - Tao Hai; Nasser M. Abd El-Salam; Teeba Ismail Kh; Rishabh Chaturvedi; Walid El-Shafai; Babak Farhang (Chemosphere, 2023)

Chemical profiling of Artemisia herba-alba, Cuminum cyminum, Cinnamomum camphora, and Salvia rosmarinus essential oils and assessment of their insecticidal potential to control the wild cochineal Dactylopius opuntiae (Cockerell) - Imane Naboulsi; Karim El Fakhouri; Hassan Annaz; Rachid Lamzira; Chaimae Ramdani; M. Bitchagno Gabin Thierry; Rachid Boulamtat; Widad Ben Bakrim; Ismail Mahdi; Aziz Aboulmouhajir; Abdelaziz Yasri; Mustapha El Bouhssini; et al. (Crop Protection, 2023)

The optimal design of solid oxide and molten carbonate fuel cells integration with a CO2 recycling unit: An attempt to reach a clean transition process - Tao Hai; Walid El-Shafai; Riyadh AL-Obaidi; Bhupendra Singh Chauhan; Teeba Ismail Kh; Nasser M. Abd El-Salam; Babak Farhang (Process Safety and Environmental Protection, 2023)

Relationship between structural style and the petroleum system in the siba gas field, southern Iraq - Amna M. Handhal; Mohammed Q. Aljazaeri; Wathiq Abdulnaby; Frank R. Ettensohn; Alaa M. Al-Abadi; Maher J. Ismail (Marine and Petroleum Geology, 2023)

Controls on hydrocarbon accumulation in the pre-rift paleozoic and late syn-rift cretaceous sandstones in PTAH oil field, north Western Desert, Egypt: Insights from seismic stratigraphy, petrophysical rock-typing and organic geochemistry - Ahmed Ismail Mahmoud; Ahmed M. Metwally; Walid M. Mabrouk; Mahmoud Leila (Marine and Petroleum Geology, 2023)

Linking diagenesis and reservoir quality to depositional facies in marginal to shallow marine sequence: An example from the Campano-Maastrichtian Gombe Sandstone, Northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Muhammad A. Ismail; Shehu Mukkafa; Usman Abubakar; Ibrahim A. Kwami; Khalid Al-Ramadan; Abduljamiu O. Amao; Murtada Al-Hashem; Anas M. Salisu; Aliyuda Kachalla; Muhammad B. Abubakar; et al. (Marine and Petroleum Geology, 2023)

Enzymatic arabinose depletion of wheat arabinoxylan regulates in vitro fermentation profiles and potential microbial degraders - Hong Yao; Bernadine M. Flanagan; Barbara A. Williams; Munirah Ismail; Astrada Dyna Ersya; Michael J. Gidley; Deirdre Mikkelsen (Food Hydrocolloids, 2023)

Effect of potential microplastics in sewage effluent on Nile Tilapia and photocatalytic remediation with zinc oxide nanoparticles - Manal Qayyadh Alanazi; Promy Virk; Seham Soliman Alterary; Manal Awad; Zubair Ahmad; Abdulrehman M. Albadri; KalidM. Ortashi; Mohieldeen Mahgoub A. Ahmed; Mohamed Ismail Ali Yousef; Mai Elobeid; Ebtesam Abdullah Al-Qahtani (Environmental Pollution, 2023)

Cellulose-based materials for scavenging toxic and precious metals from water and wastewater: A review - M. Mehedi Hasan Rocky; Ismail M.M. Rahman; Foni B. Biswas; Shafiqur Rahman; Masaru Endo; Kuo H. Wong; Asami S. Mashio; Hiroshi Hasegawa (Chemical Engineering Journal, 2023)

Delineating bedrock topography with geophysical techniques: An implication for groundwater mapping - Jeeban Panthi; Carole D. Johnson; Soni M. Pradhanang; Brian Savage; Mamoon Y. Ismail; Thomas B. Boving (CATENA, 2023)

Geosites of High Atlas of Marrakech (Morocco): Geological Characterization, Accessibility, and Potential Interests for Sustainable Tourism - Salma Wakass; Abdelkrim Ezaidi; Mohammed El Youssi; Ismail Mansouri; Hamid Achiban; Soukaina Chellik; M’hammed El Azzouzi (Geoheritage, 2023)

Trophic status determination of the Egyptian Eastern Mediterranean Sea based on phytoplankton diversity and their biochemical contents - Mona M. Ismail; Mohamed H. Diab; Mostafa M. El-Sheekh (Environmental Monitoring and Assessment, 2023)
The present study attempted to test the applicability of using phytoplankton as a bioindicator for assessing water quality along the Eastern Alexandria coast, Egypt. Eight stations were selected to cover the different characteristics of seawater during the summer 2022. Six algal groups were detected in different ratios: Bacillariophyceae, Cyanophyceae, Dinophyceae, Chlorophyceae, Silicoflagellata, and Euglenophyceae. Phytoplankton abundance was found highest at the Port Said (PS) beach, and the lowest abundance was detected at Ras El Bar (RB) beach. According to the evaluation of phytoplankton abundance, all the studied stations are oligotrophic state except PS was eutrophic. Based on Chl a concentration, the selected stations could be described as good-bad from west to east. The Shannon diversity and Pielou evenness indexes classified the studied stations as being moderate pollution except for PS and RB stations. The existence of organic pollution indicators species like Navicula , Synedra , and Euglena is a warning indication of the declining water quality especially in B and M stations. The biochemical compositions of the collected phytoplankton were spatial fluctuated. Protein and carbohydrates were the dominant macromolecules in the phytoplankton community compared with lipids. These macromolecules are used to assess trophic states whereas the ratio between protein and carbohydrate > 1 represents a healthy coast as observed in some stations. Thus, phytoplankton should be considered a bioindicator within Water Framework Directive monitoring programs for the Mediterranean Sea. For the long-term monitoring of the Mediterranean Sea’s ecosystem, it is recommended that the macromolecules of phytoplankton should be determined.

In vitro antibacterial activity and synergetic effect of crude extract of the Wohlfahrtia nuba (Diptera: Sarcophagidae) flesh fly larvae - Azza M. Khedre; Tarek G. Ismail; Gehad A. Hashem; Islam M. Zakaria (Brazilian Journal of Microbiology, 2023)
Multidrug-resistant pathogens have become ubiquitous, and effective treatment alternatives are urgently required. Maggot therapy is a promising agent that is being studied to overcome antibiotic-resistant pathogens. This study evaluated the antibacterial activity of the larvae extract of the Wohlfahrtia nuba (wiedmann) (Diptera: Sarcophagidae) flesh fly on the growth of five pathogenic bacterial species (methicillin-sensitive Staphylococcus aureus [ATCC 29213], methicillin-resistant Staphylococcus aureus [ATCC BAA-1680], Pseudomonas aeruginosa [ATCC 27853], Escherichia coli [ATCC 25922], and Salmonella typhi [ATCC 19430]) in vitro by using different techniques . Resazurin-based turbidimetric assay demonstrated that the W. nuba maggot exosecretion (ES) was potent against all the bacterial species tested, and according to the determined minimum inhibitory concentration (MIC) for each bacterium, gram-negative bacteria were more sensitive than gram-positive bacteria. Additionally, colony-forming unit assay showed that maggot ES was able to inhibit bacterial growth rate for all bacterial species tested, where the highest bacterial reduction was observed with methicillin-sensitive S. aureus (MSSA) followed by S. typhi . Moreover, maggot ES was shown to be concentration-dependent, where 100 μL of ES at 200 mg/mL was bactericidal towards methicillin-resistant S. aureus (MRSA) and P. aeruginosa compared with 100 μL at the MIC of the ES. Moreover, based on the result of agar disc diffusion assay, maggot extract was more efficient against P. aeruginosa and E. coli than the remaining reference strains tested. Furthermore, the combination between regular antibiotics with maggot ES at different concentrations indicated that ES acts synergistically with the tested antibiotics against the five bacterial models.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Influence of Different Arsenic Species on the Bioavailability and Bioaccumulation of Arsenic by Sargassum horneri C. Agardh: Effects under Different Phosphate Conditions - M. Abdullah Al Mamun; Shuhei Hayashi; Rimana Islam Papry; Osamu Miki; Ismail M. M. Rahman; Asami S. Mashio; Hiroshi Hasegawa (Environmental Science and Pollution Research, 2023)

Priorities for Mediterranean marine turtle conservation and management in the face of climate change - Antonios D. Mazaris; Charalampos Dimitriadis; Maria Papazekou; Gail Schofield; Aggeliki Doxa; Anastasia Chatzimentor; Oguz Turkozan; Stelios Katsanevakis; Aphrodite Lioliou; Sara Abalo-Morla; Mustapha Aksissou; Antonella Arcangeli; et al. (Journal of Environmental Management, 2023)

Desalination concentrate microalgae cultivation: biomass production and applications - Ghada Al Bazedi; Maha M. Ismail; Muziri Mugwanya; Hani Sewilam (Sustainable Water Resources Management, 2023)
The environmental consequences of desalination concentrate disposal have limited the practical adoption of desalination systems for inland brackish water. Desalination concentrate, which is generated by desalination facilities, has the ability to offer water and nutrients for microalgal growth. A useful application for concentrate from desalination systems is required to boost the feasibility of installing desalination procedures for both inland brackish and seawater plants. Several research has been conducted to investigate the use of desalination concentrate as a medium for microalgal culture. This paper reviews the impact of desalination concentrate on microalgal productivity by describing instances of microalgae cultivated in desalination concentrate. Based on the research results, it was found that Chlorella vulgaris , Scendesmus quadricauda , S. platensis, Nannochloropsis oculata and Dunaliella tertiolecta can be cultivated on desalination brine. Also, the paper reviews the different applications of these types which may contribute to adding revenue that will reduce the cost of desalinated water.

Chemodiversity and bioactivity assessment of phlorotannins from some Phaeophyta species from the Red Sea - Mona M. Ismail; Gehan M. El Zokm; Amany M. El Sikaily; Adel I. Selim; Gehan A. Ismail (Journal of Applied Phycology, 2023)
Phlorotannins are a unique and diverse category of secondary polyphenolic metabolites biosynthesized by brown seaweeds. They have revealed a huge potential for food and medicinal applications. In this study, five brown seaweed species were investigated: Polycladia myrica , Sirophysalis trinodis, Dictyota spiralis , Sargassum euryphyllum , and Turbinaria decurrens . All seaweed species contained considerable amounts of phlorotannins with P. myrica recording the highest content (as mg PGEs g −1 DW), followed by S. euryphyllum and then S. trinodis . The presence of phlorotannins was detected using UV–Vis spectroscopy analysis in the characterized range of 280 nm to 300 nm. All species exhibited highly significant antioxidant activity using four different techniques compared to ascorbic acid. For antidiabetic activity, the maximum α-amylase and α-glucosidase activity inhibition were recorded for P. myrica (68.79 ± 0.7%; 66.73 ± 0.5%), followed by T. decurrens (66.38 ± 0.6%; 61.34 ± 0.4%) and then D. spiralis (65.99 ± 0.5%; 60.58 ± 0.4%) compared to the acarbose standard drug (73.76 ± 0.6%; 68.38 ± 0.6%), which nominated these extracts as candidates for antidiabetic drugs. Moreover, the obtained results showed effective anti-inflammatory arthritis effects, with the maximum activity value of 86.02 ± 1.3% recorded for S. euryphyllum, followed by D. spiralis (86.23 ± 1.1%), and then P. myrica (85.94 ± 1.4%). On the other side, a low inhibition percentage of acetyl cholinesterase (AChE) activity was recorded for different phlorotannin extracts, indicating low potentiality as anti-alzheimer materials. Moreover, the P. myrica phlorotannins’ extract showed no toxicity on the WISH normal cell line by using the MTT assay. The same extract comprised a variety of phlorotannins, viz fucophlorethol, fuhalol, and phlorethol compounds, as revealed by UPLC-MS/MS analysis. Graphical Abstract

Synthesis of Cu and CuO nanoparticles from e-waste and evaluation of their antibacterial and photocatalytic properties - Sabah M. Abdelbasir; Diaa A. Rayan; Mahmoud M. Ismail (Environmental Science and Pollution Research, 2023)
Waste printed circuit boards (WPCBs) contain a plethora of valuable metals, considered an attractive secondary resource. In the current research, a hydrometallurgical process combined ammonia/ammonium chloride leaching and reduction (using L-ascorbic acid) to recover copper and its oxide (CuO) as nanosized particles from WPCBs was investigated. The results of leaching indicated that 96.7% of copper could be recovered at a temperature of 35 °C for a leaching duration of 2 h with ammonium chloride and ammonia concentration of 2 mol/L at a solid:liquid ratio of 1:10 g/cm 3 . The synthesized particles exhibit spherical and distorted sphere morphology with average particle size of 460 nm and 50 nm for Cu and CuO NPs, respectively. The antibacterial activity of Cu, CuO, and a (1:1) blend of both (Cu/CuO) has been examined against five different bacterial and fungal strains. The highest zone of inhibition was measured as 21.2 mm for Cu NPs toward Escherichia coli and 16.7 mm for Cu/CuO blend toward Bacillus cereus bacteria. The highest zone of inhibition was measured as 13 mm and 13.8 mm for Cu/CuO blend toward Fusarium proliferatum and Penicillium verrucosum fungi. Cu/CuO blend showed notable photocatalytic activity towards Rhodamine B dye under visible light irradiation with 96% degradation rate within 120 min. Using the process developed in this study, copper and its oxide as nanoparticles can be produced from WPCBs and used for multifunctional applications. Graphical abstract

Polysulfone-based mixed matrix membranes loaded with a multifunctional hierarchical porous Ag-Cu dendrites@SiO2 core-shell nanostructure for wastewater treatment - Ahmed H. Sadek; Ahmed Abdel-Karim; Sajjad Mohsenpour; Sameh H. Ismail; Ahmed M. Bayoumy; Medhat Ibrahim; Gehad G. Mohamed (Process Safety and Environmental Protection, 2023)

Curcumin loaded liposome formulation: Enhanced efficacy on performance, flesh quality, immune response with defense against Streptococcus agalactiae in Nile tilapia (Orechromis niloticus) - Bassam Alhawas; Marwa I. Abd El-Hamid; Zeinab Hassan; Ghada A. Ibrahim; Ahmed N.F. Neamat-Allah; Waleed Rizk El-Ghareeb; Badr Abdul-Hakim Y. Alahmad; Ahmed M.A. Meligy; Sherief M. Abdel-Raheem; Hesham Abdel-Moez Ahmed Ismail; Doaa Ibrahim (Fish & Shellfish Immunology, 2023)

Maternal nutrition and effects on offspring vascular function - Taylor A. Ricci; Nicha Boonpattrawong; Ismail Laher; Angela M. Devlin (Pflügers Archiv - European Journal of Physiology, 2023)

Evolution of double vortices induce tropical cyclogenesis of Seroja over Flores, Indonesia - Erma Yulihastin; Ankiq Taofiqurohman; Ibnu Fathrio; Fadli Nauval; Dita Fatria Andarini; Rahaden Bagas Hatmaja; Akhmad Fahim; Namira Nasywa Perdani; Haries Satyawardhana; M. Furqon Azis Ismail; Dwiyoga Nugroho; Suaydhi; et al. (Natural Hazards, 2023)

Effects of Zinc Oxide Nanoparticle Supplementation on Performance, Digestibility, and Blood Biochemistry of Californian Male Rabbits Under Hot Climatic Conditions - A. A. A. Abdel-Wareth; M. A. H. Raslan; Z. S. H. Ismail; W. Salem; J. Lohakare (Biological Trace Element Research, 2023)

Spatio–temporal attention based real-time environmental monitoring systems for landslide monitoring and prediction - M. Vijay Sekhar Babu; N. Ashokkumar; Anjali Joshi; Pallavi Sagar Deshpande; Ismail Keshta; Renato R. Maaliw (Spatial Information Research, 2023)

Editorial: Microbial ecology of the Arabian/Persian Gulf - Huda Mahmoud; Wael Ismail; Raeid M. M. Abed; Shady A. Amin (Frontiers in Marine Science, 2023)

Switchable hepatic organelles aberrations in DEN-induced mice under the influence of chemically characterized silk sericin - Basant A. Bakr; Ismail A. Sadek; Lamia M. El-Samad; Abeer El Wakil (Tissue and Cell, 2023)

Hematological consequences of polyethylene microplastics toxicity in male rats: Oxidative stress, genetic, and epigenetic links - Amina A. Farag; Heba S. Youssef; Rania E. Sliem; Walaa Bayoumie El Gazzar; Nashwa Nabil; Maha M. Mokhtar; Yasmin M. Marei; Nesma S. Ismail; Shaimaa E. Radwaan; Amira M. Badr; Alaa El-Din Hamid Sayed (Toxicology, 2023)

Sustainable application of tubular photosynthesis microbial desalination cell for simultaneous desalination of seawater for potable water supply associated with sewage treatment and energy recovery - Ahmed M. Sadeq; Zainab Z. Ismail (Science of The Total Environment, 2023)

Bibliometric approach to trehalulose research trends for its potential health benefits - Muhammad Faiz Zulkifli; Mohanasundarapandian Sivakumar; M. Maulidiani; Wan Iryani Wan Ismail (Food Bioscience, 2023)

Activated Carbon from Sugarcane Bagasse Pyrolysis for Heavy Metals Adsorption - S. M. Kakom; N. M. Abdelmonem; I. M. Ismail; A. A. Refaat (Sugar Tech, 2023)
Sugarcane bagasse is an agro-industrial waste available in enormous quantities in Egypt. It is rich of organic carbon which makes it a potential feedstock for activated carbon production. This study provides an optimized pyrolysis method for activated carbon production from Sugarcane bagasse. Sugarcane bagasse samples impregnated with sulfuric acid, for 24 h, and carbonized at 500 °C, for two hours, yielded the best activated carbon with a surface area of 431.375 m 2 /g. The best impregnation ratio was 2.5:1 (sulfuric acid/bagasse). The prepared activated carbon was used for adsorbing heavy metals (Pb, Cd, Mn, Cu, Cr) from Nile Tilapia reused frying oil. It could adsorb 80% of the heavy metals and particularly removed the Cd. The characteristics of the prepared activated carbon are comparable to those recommended for the commercial activated carbon. The production cost of the activated carbon using this method is about 707 $ which is cheaper than the commercial activated carbon by about 40%.

In silico and in vitro studies of novel cyanoacrylamides incorporating pyrazole moiety against breast and prostate carcinomas - Farid M. Sroor; Karima F. Mahrous; Heba I. Shafey; Nedal R. Eid; Ismail A. Abdelhamid; Nada S. Ibrahim (Medicinal Chemistry Research, 2023)
We report novel cyanoacrylamide derivatives bearing the pyrazole moiety. The molecular structures of the prepared cyanoacrylamides were confirmed by the different spectral tools such as NMR, IR, and elemental analyses. The anticancer effect of all the newly prepared cyanoacrylamides was studied against four cancer cell lines (HEPG2, MCF7, PACA2, and PC3) as well as the normal cell line (BJ1). The best cytotoxic effect was shown against PC3, where compounds 5f and 5i revealed promising IC 50 values (11.7 and 66.8 µM) respectively compared to doxorubicin (43.8 µM). In addition, the effective compounds were screened against a normal BJ1 cell line, which showed promising selectivity against PC3 and moderate selectivity toward MCF7 cells. The molecular docking study showed the affinities of compounds 5c and 5d toward STAT1 protein and compound 5i toward KRAS with promising energy scores. The subsequent molecular experiments were studied on compounds 5b , 5c , 5d , 5f , and 5i . Quantitative Real-time-PCR revealed that the expression of RBL2 and STAT2 genes were down-regulated in 5c and 5d treated MCF7 cells much lower than the other treated MCF7 samples. Also, the expression level of KRAS and SMAD genes was determined, which revealed the significant down-regulation of them in compounds 5f and 5i treated PC3 cells. The percentages of DNA damage were raised significantly in all treated MCF7 and PC3 samples as compared to the negative control, and the highest percentages were for compounds 5c and 5d treated MCF7 cells. Graphical Abstract

Evaluation of the therapeutic potential of cerebrolysin and/or lithium in the male Wistar rat model of Parkinson’s disease induced by reserpine - Engy K. Tharwat; Ahmed O. Abdelaty; Alaa I. Abdelrahman; Hebatallah Elsaeed; Ayatallah Elgohary; Amena S. El-Feky; Yasmina M. Ebrahim; Alaa Sakraan; Hossam A. Ismail; Yasser A. Khadrawy; Heba S. Aboul Ezz; Neveen A. Noor; et al. (Metabolic Brain Disease, 2023)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease worldwide and represents a challenge for clinicians. The present study aims to investigate the effects of cerebrolysin and/or lithium on the behavioral, neurochemical and histopathological alterations induced by reserpine as a model of PD. The rats were divided into control and reserpine-induced PD model groups. The model animals were further divided into four subgroups: rat PD model, rat PD model treated with cerebrolysin, rat PD model treated with lithium and rat PD model treated with a combination of cerebrolysin and lithium. Treatment with cerebrolysin and/or lithium ameliorated most of the alterations in oxidative stress parameters, acetylcholinesterase and monoamines in the striatum and midbrain of reserpine-induced PD model. It also ameliorated the changes in nuclear factor-kappa and improved the histopathological picture induced by reserpine. It could be suggested that cerebrolysin and/or lithium showed promising therapeutic potential against the variations induced in the reserpine model of PD. However, the ameliorating effects of lithium on the neurochemical, histopathological and behavioral alterations induced by reserpine were more prominent than those of cerebrolysin alone or combined with lithium. It can be concluded that the antioxidant and anti-inflammatory effects of both drugs played a significant role in their therapeutic potency.

Rutin protects against gamma-irradiation and malathion-induced oxidative stress and inflammation through regulation of mir-129-3p, mir-200C-3p, and mir-210 gene expressions in rats’ kidney - Amel F. M. Ismail; Asmaa A. Salem; Mamdouh M. T. Eassawy (Environmental Science and Pollution Research, 2023)
Kidney injury represents a global concern, leading to chronic kidney disease. The organophosphate insecticide malathion (MT) demonstrates environmental disturbance and impairment of different mammalian organs, including kidneys. Likewise, gamma-irradiation (IRR) provokes destructive effects in the kidneys. Rutin is a flavonoid glycoside that exhibits nephro-protective and radio-protective properties. This manuscript focused on investigating the protective response of rutin on MT- and IRR-triggered kidney injury in rats. Rats were randomly divided into eight groups of twelve: G1 (C), control; G2 (Rutin), rutin-treated rats; G3 (IRR), gamma-irradiated rats; G4 (MT), malathion-treated rats; G5 (IRR/MT), gamma-irradiated rats treated with malathion; G6 (IRR/Rutin), gamma-irradiated rats treated with rutin; G7 (MT/Rutin), rats treated with malathion and rutin; and G8 (IRR/MT/Rutin), gamma-irradiated rats treated with malathion and rutin, every day for 30 days. The results demonstrated that rutin treatment regulated the biochemical parameters, the oxidative stress, the antioxidant status, and the inflammatory responses due to the down-regulation of the renal NF-κB p65 protein expression. Moreover, it amended the activity of acetylcholinesterase (AchE), angiotensin ACE I, and ACE II-converting enzymes. Besides, it regulated the iNOS, eNOS, miR-129-3p, miR-200c, and miR-210 gene expressions and bradykinin receptor (B1R and B2R) protein expressions. Histopathological examinations of the kidney tissue confirmed these investigated results. It could be concluded that rutin demonstrated nephro/radioprotection and counteracted the toxicological effects triggered in the kidney tissues of IRR, MT, and IRR/MT intoxicated rats, via regulating miR-129-3p, miR-200c-3p, and miR-210-3p gene expressions, which consequently regulated B2R protein expressions, ACE II activity, and HIF-1α production, respectively.

Human health risk assessment due to consumption of dried fish in Chennai, Tamil Nadu, India: a baseline report - Marckasagayam Priyadharshini; Munawar Suhail Ahmed; Kumara Perumal Pradhoshini; Bharathi Santhanabharathi; Mohammed Fazal Shakeel Ahmed; Lubna Alam; Ismail M. M. Rahman; Van‑Hao Duong; Mohamed Saiyad Musthafa (Environmental Science and Pollution Research, 2023)

Cyanobacteria as a Valuable Natural Resource for Improved Agriculture, Environment, and Plant Protection - Atef M. Abo-Shady; Mohamed El-Anwar H. Osman; Reda M. Gaafar; Gehan A. Ismail; Maysa M. F. El-Nagar (Water, Air, & Soil Pollution, 2023)
Taking into consideration, the challenges faced by the environment and agro-ecosystem make increased for suggestions more reliable methods to help increase food security and deal with difficult environmental problems. Environmental factors play a critical role in the growth, development, and productivity of crop plants. Unfavorable changes in these factors, such as abiotic stresses, can result in plant growth deficiencies, yield reductions, long-lasting damage, and even death of the plants. In reflection of this, cyanobacteria are now considered important microorganisms that can improve the fertility of soils and the productivity of crop plants due to their different features like photosynthesis, great biomass yield, ability to fix the atmospheric N 2, capability to grow on non-arable lands, and varied water sources. Furthermore, numerous cyanobacteria consist of biologically active substances like pigments, amino acids, polysaccharides, phytohormones, and vitamins that support plant growth enhancement. Many studies have exposed the probable role of these compounds in the alleviation of abiotic stress in crop plants and have concluded with evidence of physiological, biochemical, and molecular mechanisms that confirm that cyanobacteria can decrease the stress and induce plant growth. This review discussed the promising effects of cyanobacteria and their possible mode of action to control the growth and development of crop plants as an effective method to overcome different stresses. Graphical Abstract

Response surface optimisation for highly efficient removal of 17α-ethinylestradiol by novel kenaf core modification in aqueous solution - H. M. Nasir; A. Z. Aris; L. C. Abdullah; I. Ismail (International Journal of Environmental Science and Technology, 2023)

Exergoeconomic and enviroeconomic evaluations of conventional solar still using PCM and electric heater powered by solar energy: an experimental study - Eslam Ahmed Abdel-Aziz; Tamer M. Mansour; Mohamed M. Khairat Dawood; Tamer M. Ismail; Khaled Ramzy (Environmental Science and Pollution Research, 2023)
Solar stills are used in distant and arid areas to convert brackish or salty water into potable water fit for human use in a simple, affordable, and effective manner. Even when PCM materials are used, typical solar systems still have minimal production per day. In this study, experimental tests were carried out in order to increase the performance of a single-slope solar still combined with PCM material (paraffin wax) and a solar-powered electric heater. Two identical single-slope solar stills were designed, fabricated, and tested under the same climatic conditions during the summer and spring seasons of 2021 in Al-Arish, Egypt. The first is a conventional solar still (CVSS), and the other is also a conventional still but with PCM and an electric heater (CVSSWPCM). Several parameters were measured during the experiments, including sun intensity, meteorological aspects, cumulative freshwater production, average glass, and water temperatures and PCM temperature. The improved solar still was evaluated at different operating temperatures and was compared to the conventional traditional one. There were four cases studied: one case without a heater (paraffin wax only) and three other cases with a heater operating at 58 °C, 60 °C, and 65 °C, respectively. The experimental results revealed that activating the heater inside the paraffin wax increased daily production (i) in the spring by 2.38, 2.66, and 3.1 times and (ii) and in the summer by 2.2, 2.39, and 2.67 times at the three above-mentioned temperatures respectively (when compared to the traditional still). In addition, the maximum rate of daily freshwater production was achieved at paraffin wax temperature of 65 °C in both spring and summer (Case 5). Finally, the economic evaluation of the modified solar still was carried out according to cost per litre. The modified solar still with a heater operating at 65 °C has a higher exergoeconomic value than the traditional one. The maximum CO 2 mitigation in cases 1 and 5 was approximately 28 tons and 160 tons, respectively.

Biotechnological potential of Ulva ohnoi epiphytic bacteria: enzyme production and antimicrobial activities - I. Hmani; L. Ktari; A. Ismail; M. EL Bour (Frontiers in Marine Science, 2023)
Seaweed surfaces harbor diverse epibiotic bacterial communities with functions related to morphogenesis, host health, and defense. Among seaweed holobionts, culturable strains can represent innovative sources of bioactive compounds and enzymes. The global industrial demand for microbial enzymes is continually growing in order to improve certain manufacturing processes with new perspectives of industrial exploitation. In this regard, the present study focuses on the enzymatic production and the antimicrobial activities of culturable epibiotic bacteria of Ulva from the Tunisian coast. Culturable associated bacteria were isolated and molecular identification was realized by 16S rRNA gene sequencing. For each strain, eight enzymatic activities were investigated: amylase, hemolysis, DNase, cellulase, lecithinase, lipase, gelatinase, and chitinase. The antimicrobial activity of Ulva -associated bacteria was evaluated against seven pathogenic bacteria, Escherichia coli, Vibrio anguillarum, Vibrio alginoliticus, Pseudomonas aeruginosa, Aeromonas hydrophila, Salmonella typhymurium , and Staphylococcus aureus , and one yeast, Candida albicans . The antibiotic resistance of isolated strains was determined for 15 commonly used antibiotics. The phylogenetic analysis revealed that the isolates belonged to Alphaproteobacteria (3), Gammaproteobacteria (5), Actinobacteria (3), and Firmicutes (4) phyllum. The majority of the isolates (66%) produced simultaneously more than one enzyme. Hemolysis was produced by 46.6% of isolates, while DNase was produced by 33% of strains. On the other hand, 13% of strains produced lecithinase, gelatinase, cellulase, and lipase. No chitinase was produced by the isolated bacteria. In addition, 60% of isolates displayed antimicrobial activity against at least one pathogenic strain. All Ulva ohnoi -associated bacteria were resistant to at least seven commonly used antibiotics. These results highlighted the occurrence of several enzymatic activities within Ulva -associated bacteria that can have potential uses in the industrial sector.

Impact of Streptococcus agalactiae Challenge on Immune Response, Antioxidant Status and Hepatorenal Indices of Nile Tilapia: The Palliative Role of Chitosan White Poplar Nanocapsule - Afaf N. Abdel Rahman; Sameh H. Ismail; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Samah S. Khalil; Mahmoud M. El-Saber; Ahmed E. Abdelhamid; Simon J. Davies; Rowida E. Ibrahim (Fishes, 2023)
A new insight into the synthesis of the herbal plant (White poplar, Poplus alba) leave extract using chitosan nanocapsule was studied. The in vitro antibacterial activity of chitosan white poplar nanocapsule (CWPNC) against Streptococcus agalactiae (S. agalactiae) was determined. About 120 fish were categorized for 7 days into four groups. The first and second (CWPNC) groups were treated with 0 mg/L and 3 mg/L CWPNC in the water, respectively, without being challenged; the first group was a control. The third (S. agalactiae) and fourth (CWPNC + S. agalactiae) groups were treated with 0 and 3 mg/L CWPNC, respectively, and challenged with S. agalactiae (0.5 × 107 CFU/mL). The obtained results revealed that CWPNC had an in vitro antibacterial activity against S. agalactiae. Moreover, S. agalactiae infection caused a significant elevation (p

Fabrication of BiVO4 nanosheets decorating by V2O5 nanoparticles for the enhanced photocatalytic desulfurization of thiophene - Adel A. Ismail; Soha M. Albukhari; Latifa A. Al-Hajji (Journal of Environmental Chemical Engineering, 2023)

Performance, energy and economic investigation of airgap membrane distillation system: An experimental and numerical investigation - G. Gopi; M. Vasanthkumar; G. Arthanareeswaran; A.F. Ismail; Y. Lukka Thuyavan; P.S. Goh; T. Matsuura (Desalination, 2023)

Theoretical and molecular mechanistic investigations of novel (3-(furan-2-yl)pyrazol-4-yl) chalcones against lung carcinoma cell line (A549) - Magda F. Mohamed; Nada S. Ibrahim; Amna A. Saddiq; Omar A. Almaghrabi; Maha E. Al-Hazemi; Hamdi M. Hassaneen; Ismail A. Abdelhamid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
A new chalcone series has been developed that may be useful in the treatment of lung cancer. The new series was confirmed by the different spectral tools. MTT assay was used to detect the cytotoxic effect of the novel chalcones against lung cancer cell line (A549). Molecular docking studies were performed on the most two effective chalcones 7b and 7c . Different molecular techniques were utilized to study the activity and the effect of two chalcones 7b and 7c on apoptosis of A549 cell line.

Design and analysis of water quality monitoring and filtration system for different types of water in Malaysia - N. A. Razman; W. Z. Wan Ismail; M. H. Abd Razak; I. Ismail; J. Jamaludin (International Journal of Environmental Science and Technology, 2023)

Variation in Anti-inflammatory, Anti-arthritic, and Antimicrobial Activities of Different Extracts of Common Egyptian Seaweeds with an Emphasis on Their Phytochemical and Heavy Metal Contents - Aida H. Shobier; Mona M. Ismail; Sahar W. M. Hassan (Biological Trace Element Research, 2023)
The anti-inflammatory, anti-arthritic, and antimicrobial activities of some common Egyptian seaweeds in addition to their phytochemical and heavy metal contents were investigated. Phytochemical screening of the seaweed extracts showed the presence of different primary and secondary metabolites with different concentrations according to their species and the used solvent. The ethanolic extract of Colpmenia sinuosa (CSBE2) exhibited the maximum anti-inflammatory and anti-arthritic activity at 1000 μg/ml concentration compared to other seaweed extracts. The dichloromethane extract of Corallina officinalis (CORM) exerted the highest antimicrobial activity with an average inhibition zone diameter (AV) = 15.29 mm and activity index (AI) = 1.53 and with the highest antagonistic activity against Escherichia coli (28 mm). It is followed by Ulva linza ethanolic extract (ULGE2) which recorded (AV) of 14.71 mm and (AI) of 1.30 with the highest antifungal activity against Candida albicans (30 mm). The collected seaweeds would therefore be a very promising source for treating inflammatory, arthritic, and microbial diseases. Moreover, the investigated seaweeds showed variable concentrations of heavy metals among various species. The mean concentrations of the heavy metals took the following order: Fe > Zn > Mn > Ba > Cu > As > Cr > Ni > Pb > V > Cd > Se > Co > Mo. Based on the permissible limits set by the WHO and CEVA, Pb and Ni in the studied seaweeds were found to be within the permissible limits, whereas Cd and Zn contents were at the borderline. Significant correlations were observed between studied parameters. The estimated daily intakes for most heavy metals were lower than the recommended daily intakes.

Geochemistry and petrogenesis of the Paleoproterozoic ortho-gneisses and granitoids of the Banded Gneissic Complex, central Rajasthan, NW India: Implications for crustal reworking processes - Iftikhar Ahmad; T. P. Abdul Latheef; M. E. A. Mondal; Ismail S. Hamidullah; Kamaal Parvez (Acta Geochimica, 2023)

Physiological responses of wild grass Holcus lanatus L. to potentially toxic elements in soils: a review - Ismail M.M. Rahman; Bayezid M. Khan (Environmental Science and Pollution Research, 2023)

Evaluating how occupational exposure to organophosphates and pyrethroids impacts ADHD severity in Egyptian male adolescents - Hana-May Eadeh; Jonathan Davis; Ahmed A. Ismail; Gaafar M. Abdel Rasoul; Olfat M. Hendy; James R. Olson; Matthew R. Bonner; Diane S. Rohlman (NeuroToxicology, 2023)

Impact of Modern Irrigation Methods on Groundwater Storage and Land Subsidence in High-water Stress Regions - Ismail Abd-Elaty; Ismail Fathy; Alban Kuriqi; Am Pris John; Salvatore Straface; Elsayed M. Ramadan (Water Resources Management, 2023)
Water resources management in high-stress regions is a large-scale problem affecting food and water security. Therefore, modern irrigation systems such as sprinklers, subsurface, and drip irrigations are applied to manage the water shortage in regions of the Nile delta. Because of the increase in population rate and climate change, freshwater supplies are significantly limited and must be efficiently managed. Consequently, Egypt plans to implement MIS in the old land of the Nile delta. The current study aims to investigate and model the recharge from the excess irrigation system that affects groundwater storage and land subsidence unexpectedly. The visual modflow was applied to investigate the groundwater heads and drawdown. At the same time, the analytical solution based on Terzaghi theory, and the surfer software was used to estimate and map the land subsidence. For this reason, we investigated the groundwater drawdown in the high-water shortage of Egypt’s Nile delta. Three scenarios were considered by changing irrigation methods and their Impact on land subsidence in the Nile Delta Aquifer (NDA). Therefore, the results of this study demonstrated that the groundwater drawdown reached 2.60 m, 4.20 m, and 6.50 m, respectively. In contrast, the land subsidence outstretched 26 m, 44 m, and 65 cm for the sprinkle sub-surface. Future design infrastructures such as pipelines, roads, irrigation networks, canals, and water structures should consider land subsidence due to modern irrigation systems (MIS).

Development of visibility equation based on fog microphysical observations and its verification using the WRF model - Sandeep Wagh; Rachana Kulkarni; Prasanna Lonkar; Avinash N. Parde; Narendra G. Dhangar; Gaurav Govardhan; Veeresh Sajjan; Sreyashi Debnath; Ismail Gultepe; M. Rajeevan; Sachin D. Ghude (Modeling Earth Systems and Environment, 2023)

Therapeutic Potency of Ginger, Garlic, and Pomegranate Extracts Against Cryptosporidium parvum-Mediated Gastro-Splenic Damage in Mice - Dina M. M. EL-Shewehy; Gehad E. Elshopakey; Amira Ismail; Shimaa S. Hassan; Amany M. Ramez (Acta Parasitologica, 2023)
Purpose Cryptosporidium parvum is a protozoan parasite infecting most mammalian hosts and causing major health issues. The present study investigated the efficacy of ginger ( Zingiber officinale ), garlic ( Allium sativum), and pomegranate ( Punica granatum ) peel extracts on the development and progression of experimental cryptosporidiosis in mice. Methods Eighty-two mice were assigned to 6 groups: control, infected non-treated, metronidazole (MTZ), ginger, garlic, and pomegranate. The control group topically received no treatments. The infected non-treated group was experimentally infected by 10 4 C. parvum oocysts per mouse using a stomach tube. The MTZ group was infected with C. parvum oocysts combined with MTZ (50 mg/kg b.w./day). The ginger, garlic, and pomegranate groups daily received different plant extracts at doses of 100 mg/kg BW, 50 mg/kg BW, and 3 gm/kg BW, respectively, followed by infection with C. parvum oocysts. All treatments were applied orally one day after the infection for continuous 30 days. Results Histopathological and immunohistochemical examinations for P53 and caspase-3 expressions in stomach and spleen tissues showed that MTZ and garlic-treated mice had a more significant effect on infected mice. Conclusion The garlic extract was found to exert a more pronounced effect on infected mice compared with the other treatments as well as to improve health. Garlic extracts, therefore, represent an effective and natural therapeutic alternative for the treatment of cryptosporidiosis with low side effects and without drug resistance.

Litoarbolide A: an undescribed sesquiterpenoid from the Red Sea soft coral Litophyton arboreum with an in vitro anti-malarial activity evaluation - Mohammed M. A. Ahmed; Ehab A. Ragab; Ahmed Zayed; Elsayed M. El-Ghaly; Said K. Ismail; Shabana I. Khan; Zulfiqar Ali; Amar G. Chittiboyina; Ikhlas A. Khan (Natural Product Research, 2023)

The Efficacy of Intra-articular Umbilical Cord-Mesenchymal Stem Cell Injection for Knee Osteoarthritis: a Systematic Review - Ismail Hadisoebroto Dilogo; Andri M. T. Lubis; Natasena Galar Perwida; Safinah Aulia Sani; Rufiah Aulia Rasyidah; Bernadus Riyan Hartanto (Current Stem Cell Reports, 2023)

Development and evaluation of an integrated waste to energy system based on polyethylene plastic wastes pyrolysis for production of hydrogen fuel and other useful commodities - Mohamed M. Ismail; Ibrahim Dincer (Fuel, 2023)

Arsenic may be a carcinogenic determinant of a subset of gallbladder cancer: A pilot study - Giuseppe De Palma; Gonzalo Carrasco-Avino; Enrica Gilberti; Moris Cadei; Tatiana Pedrazzi; Ivan M. Gallegos Mendez; Alejandra Roman; Nicolas Demartines; Paolo Boffetta; Ismail Labgaa (Environmental Research, 2023)

Synthesis of silver decorated magnetic Fe3O4/alginate polymeric surfactant with controllable catalytic activity toward p-NP removal and enzymatic-mimic activity for solid-colorimetric H2O2 detection - Shymaa M. Ismail; Ali A. Abd-Elaal; Fatma H. Abd El-salam; Fatma A. Taher; I. Aiad; Samy M. Shaban (Chemical Engineering Journal, 2023)

Methotrexate conjugated gold nanoparticles improve rheumatoid vascular dysfunction in rat adjuvant-induced arthritis: gold revival - Salma T. Rafik; Teshreen M. Zeitoun; Thanaa I. Shalaby; Mervat K. Barakat; Cherine A. Ismail (Inflammopharmacology, 2023)
Endothelial vasomotor dysfunction and accelerated atherosclerosis encompass the features of rheumatoid vascular dysfunction (RVD), increasing cardiovascular morbidity and mortality among rheumatoid arthritis (RA) patients. Methotrexate, among DMARDs, effectively reduces cardiovascular events, but its non-selectivity together with its pharmacokinetic variability often limit drug adherence and contribute to its potential toxicity. Thus, methotrexate was conjugated to gold nanoparticles (MTX/AuNPs) and its effect on RVD in rats’ adjuvant-induced arthritis was evaluated. A comparative study between MTX/AuNPs, free MTX, and AuNPs treatments on joint inflammation, vascular reactivity and architecture, smooth muscle phenotype, systemic inflammation, and atherogenic profile was done. Since MTX/AuNPs effect was superior, it appears that conjugation of MTX to AuNPs demonstrated a synergistic action. MTX immunomodulatory action combined with AuNPs anti-atherogenic potential yielded prompt control of whole features of RVD. These findings highlight the usefulness of nanoparticles-targeted drug-delivery system in refining rheumatoid-induced vascular dysfunction treatment and reviving gold use in RA.

Novel eco-friendly [1,2,4]triazolo[3,4-a]isoquinoline chalcone derivatives efficiency against fungal deterioration of ancient Egyptian mummy cartonnage, Egypt - Neveen S. Geweely; Mona M. Soliman; Rania A. Ali; Hamdi M. Hassaneen; Ismail A. Abdelhamid (Archives of Microbiology, 2023)
Fungal deterioration is one of the major factors that significantly contribute to mummy cartonnage damage. Isolation and molecular identification of thirteen fungal species contributing to the deterioration of ancient Egyptian mummy cartonnage located in El-Lahun regions, Fayoum government, Egypt was performed. The most dominant deteriorated fungal species are Aspergillus flavus (25.70%), Aspergillus terreus (16.76%), followed by A. niger (13.97%). A newly synthesized series of tetrahydro-[1,2,4]triazolo[3,4-a]isoquinoline chalcone derivatives were synthesized and evaluated for their antifungal activities in vitro against the isolated deteriorated fungal species ( Aspergillus flavus, A. niger, A. terreus , Athelia bombacina , Aureobasidium iranianum , Byssochlamys spectabilis , Cladosporium cladosporioides , C. ramotenellum , Penicillium crustosum , P. polonicum , Talaromyces atroroseus , T. minioluteus and T. purpureogenus ). The most efficient chalcone derivatives are new chalcone derivative numbers 9 with minimum inhibitory concentration (MIC) ranging from 1 to 3 mg/mL followed by chalcone derivatives number 5 with MIC ranging from 1 to 4 mg/mL.

Phenolic content of Terminalia catappa L. leaf and toxicity evaluation on red hybrid tilapia ( Oreochromis sp.) - Yahaya Yakubu; Muhammad T. Ahmad; Chou M. Chong; Intan S. Ismail; Khozirah Shaari (Journal of Fish Biology, 2023)
Despite the use of Terminalia catappa (TC) leaf by traditional fish farmers around the world to improve the health status of cultured fish, there is a paucity of information on comprehensive metabolite profile and the maximum safe dose of the plant. This study aims at profiling the methanol leaf extract of T. catappa, quantifying total phenolic content (TPC) as well as the total flavonoid content (TFC) and evaluating its acute toxicity on blood, plasma biochemical parameters and histopathology of some vital organs in red hybrid tilapia ( Oreochromis sp.). The experimental fish were acclimatised for 2 weeks and divided into six groups. Group (1) served as a control group and was administered 0.2 ml,g −1 of phosphate buffer saline (PBS). Groups 2–6 were orally administered T. catappa leaf extracts (0.2 ml.50 g −1 ) in the following sequence; 31.25, 62.5, 125, 250 and 500 mg.kg −1 body weight. The metabolites identified in T. catappa using liquid chromatography‐tandem mass electrospray ionisation spectrometry (LC‐ESI‐MS/MS) revealed the presence of organic acids, hydrolysable tannins, phenolic acids and flavonoids. Phenolic quantification revealed reasonable quantity of phenolic compounds (217.48 μg GAEmg −1 for TPC and 91.90 μg. QCEmg −1 for TFC). Furthermore, there was no significant difference in all the tested doses in terms of blood parameters and plasma biochemical analysis except for the packed cell volume (PCV) at 500 mg.kg −1 when compared to the control. Significant histopathological changes were observed in groups administered with the extract at 125, 250 and 500 mg.kg −1 doses. To a very large extent it is therefore safe to administer the extract at 31.25 and 62.5 mg.kg −1 in tilapia.

Synthesis of mesoporous Ag/α-Fe2O3/TiO2 heterostructures with enhanced and accelerated photo/-catalytic reduction of 4-nitrophenol - Atif Mossad Ali; Hamza El-hosainy; Iman Y. Alhassan; Latifa A. Al-Hajji; Adel A. Ismail; Hamed Algarni; Haitham M. El-Bery (Environmental Science and Pollution Research, 2023)

Acute toxic effects of new synthetic cannabinoid on brain: Neurobehavioral and Histological: Preclinical studies - Shrouk Mohamed Ali; Eman Kolieb; Samar Imbaby; Abeer M. Hagras; Horeya Erfan Korayem Arafat; Eman Mohamed Kamel; Mohamed A. Abdelshakour; Maha Ismail Mohammed Ali (Chemico-Biological Interactions, 2023)

Chalcones: Promising therapeutic agents targeting key players and signaling pathways regulating the hallmarks of cancer - Amr Ahmed WalyEldeen; Salwa Sabet; Haidan M. El-Shorbagy; Ismail A. Abdelhamid; Sherif Abdelaziz Ibrahim (Chemico-Biological Interactions, 2023)

Effect of platelet-rich plasma (PRP) on post-thaw quality, kinematics and in vivo fertility of fertile and subfertile buffalo (Bubalus bubalis) spermatozoa - Essam A. Almadaly; Ibrahim M. Ibrahim; Maha S. Salama; Mohey A. Ashour; Ferial M. Sahwan; Ismail I. El-Kon; Tarek K. Abouzed; Wael B. El-Domany (Veterinary Research Communications, 2023)

Hydrogeochemical characterization of the groundwater of Lahore region using supervised machine learning technique - Sadia Ismail; M. Farooq Ahmed (Environmental Monitoring and Assessment, 2023)

Accuracy of Rapid Emergency Medicine Score and Sequential Organ Failure Assessment Score in predicting acute paraphenylenediamine poisoning adverse outcomes - Ghada N. El-Sarnagawy; Mona M. Ghonem; Marwa A. Abdelhameid; Omaima M. Ali; Asmaa M. Ismail; Doaa M. El Shehaby (Environmental Science and Pollution Research, 2022)
Paraphenylenediamine (PPD) is a commonly used xenobiotic in hair dying, causing deleterious outcomes in acute poisoning. Although many epidemiological studies and case reports explained their clinical presentations and fatal consequences, no studies have evaluated the early determinants of adverse outcomes. Therefore, the present study aimed to assess the initial predictors of acute PPD poisoning adverse outcomes, focusing on the discriminatory accuracy of the Rapid Emergency Medicine Score (REMS) and Sequential Organ Failure Assessment (SOFA) score. A retrospective cohort study included all acute PPD-poisoned patients admitted to three Egyptian emergency hospitals from January 2020 to January 2022. Data was gathered on admission, including demographics, toxicological, clinical, scoring systems, and laboratory investigations. Patients were categorized according to their outcomes (mortality and complications). Ninety-seven patients with acute PPD poisoning were included, with a median age of 23 years, female predominance (60.8%), and suicidal intention (95.9%). Out of all patients, 25.77% died, and 43.29% had complicated outcomes. Respiratory failure was the primary cause of fatalities (10.30%), while acute renal failure (38.14%) was a chief cause of complications. The delay time till hospitalization, abnormal electrocardiogram, initial creatine phosphokinase, bicarbonate level, REMS, and SOFA scores were the significant determinants for adverse outcomes. The REMS exhibited the highest odds ratio (OR = 1.91 [95% confidence interval (CI): 1.41–2.60], p < 0.001) and had the best discriminatory power with the area under the curve (AUC) = 0.918 and overall accuracy of 91.8% in predicting mortality. However, the SOFA score had the highest odds ratio (OR = 4.97 [95% CI: 1.16–21.21], p = 0.001) and only yielded a significant prediction for complicated sequels with AUC = 0.913 and overall accuracy of 84.7%. The REMS is a simple clinical score that accurately predicts mortality, whereas the SOFA score is more practicable for anticipating complications in acute PPD-poisoned patients.

Chemical characterization and biological activities of ulvan extracted from Ulva fasciata (Chlorophyta) - Khouloud M. Barakat; Mona M. Ismail; Hala E. Abou El Hassayeb; Nermeen A. El Sersy; Mostafa E. Elshobary (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)
Ulvan is a sulfated heteropolysaccharide present in the cell wall of Ulva species with a unique structure and biological potential used in various fields. Chemical characterization was carried out to determine the structure of ulvan from Ulva fasciata Delile collected from Eastern Harbor, Alexandria coast, Egypt. Ulva contains 31.5% carbohydrate with a total ulvan content of 43.66% of total carbohydrate (13.75 g/100 g DW) and sulfate content of 20.45% of ulvan. FTIR spectrum presented signals of the sulfate ester (C–O–S) and sulfate groups (S=O), typical for ulvan. GC–MS revealed that ulvan was mainly composed of rhamnose and fucose. 1 H-NMR spectra of ulvan showed identical behavior of monosaccharides nature with peaks characteristic of sulfated polysaccharides at 3.2–5.3 ppm region. Scanning electron micrographs (SEM) demonstrated amorphous architecture, and the sulfated nature of polysaccharides was emphasized by EDX analysis. The extracted ulvan showed significant antimicrobial activity against human and fish pathogens as well as antifouling bacteria with minimum inhibitory concentrations (MIC) of 8 µg/mL. The extracted ulvan exhibited potent antioxidant activity with a scavenging effect of 84.93% for 2,2-diphenyl-1-picrylhydrazy free radical (DPPH). Moreover, it showed anti-arthritic properties for the first time with a maximum inhibition of 86.04% with IC 50 of 43.21%, indicating their potential value for the health and food industry.

Biological potential of the alien red alga Asparagopsis taxiformis and characterization of its culturable associated bacteria - L. Ktari; A. Ismail; H. Selmi; I. Hmani; M. El Bour (Journal of Applied Phycology, 2022)

Effect of Dietary Moringa oleifera Leaves Nanoparticles on Growth Performance, Physiological, Immunological Responses, and Liver Antioxidant Biomarkers in Nile tilapia (Oreochromis niloticus) against Zinc Oxide Nanoparticles Toxicity - Heba S. Hamed; Rehab M. Amen; Azza H Elelemi; Heba H. Mahboub; Hiam Elabd; Abdelfattah M. Abdelfattah; Hebatallah Abdel Moniem; Marwa A. El-Beltagy; Mohamed Alkafafy; Engy Mohamed Mohamed Yassin; Ayman K. Ismail (Fishes, 2022)
The current study addresses the influence of Moringa oleifera leaves nanoparticles (MO-NPs) on growth, biochemical, immunological, and hepatic antioxidant alterations induced by zinc oxide nanoparticles toxicity in Nile tilapia (O. niloticus). Fish (N = 180) were divided into four groups with replicates. The first one was set as a control group and the second group was fed an MO-NPs-enriched diet (2.5 g/kg diet). The third group was exposed to 8 mg/L ZnO-NPs, while the forth group was exposed to 8 mg/L ZnO-NPs and fed on MO-NPs (2.5 g/kg diet) for 2 months. Exposure of O. niloticus to 8 mg/L ZnO-NPs induced the following consequences: a sharp decrease in the growth parameters; a marked increment in the biochemical biomarkers (glucose, cortisol, and liver enzymes (ALT, AST, ALP); a significant increase in serum renal products, urea and creatinine, cholesterol, and LDH levels. Nonetheless, the dietary MO-NPs supplementation for 2 months significantly alleviated the ZnO-NPs toxicity and significantly enhanced the growth indices, plus normalizing the physio-biochemical levels in the exposed group to ZnO-NPs toxicity to reach the levels of the control group. The MO-NPs markedly improved hepatic antioxidant biomarkers, MDA, and TAC, while, decreasing SOD, CAT, and GSH levels to be near the control values. Moreover, supplemented fish in MO-NPs (2.5 g/kg diet) and exposed to ZnO-NPs provided a remarkable increase in the immune profile (respiratory burst (RB) activity, lysozyme, and total immunoglobulins (IgM)) compared to the ZnO-NPs-intoxicated group. Based on the findings of the study, the exposed O. niloticus to ZnO-NPs were immune-antioxidant-depressed, besides showing growth retardation, and physio-biochemical alterations. On the other hand, a supplemented diet with MO-NPs is a novel approach to ameliorate ZnO-NPs toxicity for sustaining aquaculture and correspondingly protecting human health.

Mesoporous BiVO4/TiO2 heterojunction: enhanced photoabsorption and photocatalytic ability through promoted charge transfer - Nada Y. Tashkandi; Soha M. Albukhari; Adel A. Ismail (Environmental Science and Pollution Research, 2022)

Co-expression of candidate genes regulating growth performance and carcass traits of Barki lambs in Egypt - Nasser Ghanem; Mohamed Zayed; Ismail Mohamed; Mona Mohammady; M. F. Shehata (Tropical Animal Health and Production, 2022)
Sheep are considered one of the main sources of animal protein in Egypt and the producers of sheep mutton eagers to find biological criteria for selecting fast-growing lambs that reach market weight early. Therefore, the present study aimed to find a link between the expression profile of selected candidate genes with growth performance and carcass traits of Barki lambs. Thirty-eight Barki lambs were kept and fed individually after weaning till 12 months of age and were divided into 3 groups according to growth performance (fast, intermediate, and slow-growing). Three samples were taken from different body tissues (eye muscle, liver, and fat tail) of each group, directly during slaughtering and stored at − 80 °C until RNA isolation. Real-time PCR was used to profile selected candidate genes (RPL7, CTP1, FABP4, ADIPOQ, and CAPN3) and GAPDH was used as a housekeeping gene. The results indicated that the final body weight was significantly ( P ≤ 0.05) greater in the fast (49.9 kg) and intermediate (40.7 kg) compared to slow-growing animals (30.8 kg). The hot carcass weight was heavier ( P ≤ 0.05) in the fast and intermediate-growing (24.57 and 19.07 kg) than slow-growing lambs (15.10 kg). The blood profiles of T3 and T4 hormones in addition to other parameters such as total protein, total lipids, and calcium level showed no clear variations among different experimental groups. At the molecular level, our data demonstrated upregulation of genes involved in protein biosynthesis (RPL7), fatty acid oxidation (CPT1), and lipolysis (FABP4) in the fast and intermediate-growing lambs in all studied tissues which facilitate protein accretion, energy expenditure, and fatty acid partitioning required for muscle building up. Moreover, the expression profile of the gene involved in muscle development (CAPN3) was increased in fast and intermediate-growing compared to slow-growing lambs in order to support muscle proper development. On the other hand, a candidate gene involved in lipogenesis (ADIPOQ) was expressed similarly in fat and liver tissues; however, its expression was increased in muscles of fast and intermediate-growing lambs compared to slow-growing animals. In conclusion, the current study indicated that the expression profile of genes involved in metabolic activities of liver, muscle, and adipose tissue is linked with the growth performance of lambs although no variations were detected in blood parameters. This provides an evidence for the importance of co-expression of these genes in body tissues to determine the final body weight and carcass characteristics of Barki sheep.

[1,2,4] Triazolo [3,4-a]isoquinoline chalcone derivative exhibits anticancer activity via induction of oxidative stress, DNA damage, and apoptosis in Ehrlich solid carcinoma-bearing mice - Amr Ahmed WalyEldeen; Haidan M. El-Shorbagy; Hamdi M. Hassaneen; Ismail A. Abdelhamid; Salwa Sabet; Sherif Abdelaziz Ibrahim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Despite the advances made in cancer therapeutics, their adverse effects remain a major concern, putting safer therapeutic options in high demand. Since chalcones, a group of flavonoids and isoflavonoids, act as promising anticancer agents, we aimed to evaluate the in vivo anticancer activity of a synthetic isoquinoline chalcone (CHE) in a mice model with Ehrlich solid carcinoma. Our in vivo pilot experiments revealed that the maximum tolerated body weight-adjusted CHE dose was 428 mg/kg. Female BALB/c mice were inoculated with Ehrlich ascites carcinoma cells and randomly assigned to three different CHE doses administered intraperitoneally (IP; 107, 214, and 321 mg/kg) twice a week for two consecutive weeks. A group injected with doxorubicin (DOX; 4 mg/kg IP) was used as a positive control. We found that in CHE-treated groups: (1) tumor weight was significantly decreased; (2) the total antioxidant concentration was substantially depleted in tumor tissues, resulting in elevated oxidative stress and DNA damage evidenced through DNA fragmentation and comet assays; (3) pro-apoptotic genes p53 and Bax , assessed via qPCR, were significantly upregulated. Interestingly, CHE treatment reduced immunohistochemical staining of the proliferative marker ki67, whereas BAX was increased. Notably, histopathological examination indicated that unlike DOX, CHE treatment had minimal toxicity on the liver and kidney. In conclusion, CHE exerts antitumor activity via induction of oxidative stress and DNA damage that lead to apoptosis, making CHE a promising candidate for solid tumor therapy.

Hydrophobic deep eutectic solvent-based dispersive liquid–liquid microextraction for the zinc determination in aqueous samples: multivariate study - B. Al Sayeda; F. Shah; N. Ullah; R. A. Khan; B. Ismail; A. M. Khan; J. Nisar (International Journal of Environmental Science and Technology, 2022)

Utilization of white-cement kiln dust in presence of raw/waste materials for production of alkali-activated products - M. F. Zawrah; N. Shehata; A. B. Saddek; A. R. G. Ismail (International Journal of Environmental Science and Technology, 2022)

Correction: QTL mapping under salt stress in rice using a Kalarata–Azucena population - Marjorie P. de Ocampo; Viet The Ho; Michael J. Thomson; Shiro Mitsuya; Akira Yamauchi; Abdelbagi M. Ismail (Euphytica, 2022)

3E enhancement of freshwater productivity of solar still with heater, vibration, and cover cooling - Mohamed M. Khairat Dawood; Abubakr Helmy Omar; Ali Ismail Shehata; Ahmed Samir Shehata; Ahmed Abd-Elsalam Taha; Mohamed Nabil El-Shaib; Madeha Kamel Mohamed (Environmental Science and Pollution Research, 2022)
This study focused on experimentally increasing the productivity of freshwater from solar stills. The performance of a single solar still system could be augmented with the combination of an electric heater, vibration motion, and thermoelectric cooling. The study investigated the effects of combining two of these components and finally combining all of them on freshwater productivity. The electric heater and vibration motion are used to enrich the evaporation rate, while thermoelectric coolers are used to enhance the condensation rate, leading to high freshwater productivity. The proposal, construction, and testing of two identical solar stills were performed under the local climate conditions of the city of Alexandria in northwestern Egypt during the summer and winter times. The two solar stills had a 1-m 2 base area. An electric heater of 450 W was placed inside the modified solar still. The modified solar still was fixed on four coiled springs. A 1-hp power DC motor, an inverter, a control unit, and two 330-W photovoltaic solar panels were attached to the modified solar still. Eccentric masses were mounted on the rotating disk attached to the DC motor to generate the vibration. Under the same climate conditions, the daily output of freshwater was measured experimentally for the modified case and the conventional solar. The daily rates of freshwater productivity in summer were investigated for four cases and the conventional one. Results showed that the peak daily freshwater productivity achieved with the solar heater, thermoelectric coolers, and vibration motion was 12.82 kg/day, with a maximum estimated cost of 0.01786 $/L/m 2 .The exergoeconomic of the modified solar still with heater, vibration, and thermoelectric cooler was greater than that of conventional ones. The highest CO 2 mitigation of the case (5) and that of the conventional solar desalination were about 160 tons and 28 tons, respectively.

Spatial–temporal prediction model for land cover of the rural–urban continuum axis between Ar-Riyadh and Al-Kharj cities in KSA in the year of 2030 using the integration of CA–Markov model, GIS-MCA, and AHP - Ashraf Abdelkarim; Haya M. Alogayell; Ibtesam I. Alkadi; Ismail Youssef (Applied Geomatics, 2022)
The spatiotemporal analysis of land use/land cover change and monitoring, modeling, and forecasting the future of land uses are considered challenges facing planners and decision-makers in developing countries. These challenges are increased in neighborhood areas surrounding large cities, which are known as the “rural–urban continuum”. These areas have become the preferred areas for resettlement for most urban residents. The objectives of the present study were to (1) monitor the land cover change in the rural–urban continuum axis between the Ar-Riyadh and Al-Kharj cities during the period 1988–2020, (2) simulate the future growth of land cover up to the year 2030 using the Cellular Automated Markov Model (CA-Markov), and (3) improve the ability of CA-Markov to predict the future by integrating multi-criteria analysis based on geographic information systems (GIS-MCA) and analytic hierarchy process (AHP) method. The results of the study revealed large changes in the land cover in the rural–urban continuum axis between the Ar-Riyadh and Al-Kharj cities. About 60 km 2 of agricultural land has been lost, with an average annual decrease of 2 km 2 . The industrial and urban areas were increased with growth rate of 4%. There were five categories of spatial suitability, ranging between 32 and 86%, and 70% or higher is the recommended percentage for future land uses. The industrial use was the most likely land use in 2030, as it recorded an increase of 27.1 km 2 over the year 2020.

Anti-quorum sensing, antibiofilm, and antibacterial activities of extracts of Centella asiatica L. leaves, and in vitro derived leaves-calli through tissue culture: a potential for biofouling-prevention - Mo Ahamad Khan; Haris M. Khan; Irfan Bashir Ganie; Sachin Kumar; Anwar Shahzad; Ismail Celik; Mohammad Shahid (Biofouling, 2022)

Synthesis and design of spinel ZnAl2O4 nanowires with PtO nanoparticles decoration for enhanced induced visible light Hg(II) reduction - S. M. Albukhari; A. A. Ismail; S. Z. Alsheheri; M. H. H. Mahmoud (International Journal of Environmental Science and Technology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Biodegradable Chelator-Assisted Washing and Stabilization of Arsenic-Contaminated Excavated Soils - Shafiqur Rahman; Naoyuki Jii; Shengbin Ni; Yasuhiro Harada; Asami S. Mashio; Zinnat Ara Begum; Ismail M. M. Rahman; Hiroshi Hasegawa (Water, Air, & Soil Pollution, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

QTL mapping under salt stress in rice using a Kalarata–Azucena population - Marjorie P. de Ocampo; Viet The Ho; Michael J. Thomson; Shiro Mitsuya; Akira Yamauchi; Abdelbagi M. Ismail (Euphytica, 2022)
Salt stress is a major constraint across large rice production areas in Asia, because of the high sensitivity of modern rice varieties. To identify quantitative trait loci (QTL) associated with salt tolerance in rice, we developed an F 2 population from a cross between the salt-tolerant landrace, Kalarata, and the salt-sensitive parent, Azucena. F3 families from this population were screened and scored for salt tolerance using IRRI’s Standard evaluation system (SES). Growth, biomass, Na + and K + concentrations in leaf tissues, and chlorophyll concentration were determined. A genetic linkage map was constructed with 151 SSRs and InDel markers, which cover 1463 cM with an average distance of 9.69 cM between loci. A total of 13 QTL were identified using Composite Interval Mapping for 16 traits. Several novel QTL were identified in this study, the largest is for root sodium concentration (LOD = 11.0, R 2 = 25.0) on chromosome 3, which also co-localize with a QTL for SES. Several QTL on the short arm of chromosome 1 coincide with the Saltol locus identified before. The novel QTL identified in this study constitute future targets for molecular breeding, to combine them with other QTL identified before, for higher tolerance and stable performance of rice varieties in salt affected soils.

A holistic approach to the air quality of Konya City, Turkey - Mete TAYANÇ; İsmail SEZEN; Alper ÜNAL; Rosa M. FLORES; Salih KARANFİL (Air Quality, Atmosphere & Health, 2022)

An Association Between Blastocystis Subtypes and Colorectal Cancer Patients: A Significant Different Profile from Non-cancer Individuals - Shaimaa H. Ali; Mousa A. M. Ismail; Ayman A. El-Badry; Enas Y. Abu-Sarea; Ahmad M. Dewidar; Doaa A. Hamdy (Acta Parasitologica, 2022)

Temporal compositional shifts in an activated sludge microbiome during estrone biodegradation - Sarah AlDhafiri; Yin-Ru Chiang; Ashraf M. EL Nayal; Raeid M. M. Abed; Nasser Abotalib; Wael Ismail (Environmental Science and Pollution Research, 2022)

Controlling of Xanthomonas axonopodis pv. phaseoli by induction of phenolic compounds in bean plants using salicylic and benzoic acids - Kamal A. M. Abo-Elyousr; Muhammad Imran; Najeeb M. Almasoudi; Esmat F. Ali; Sabry Hassan; Nashwa M A. Sallam; Khamis Youssef; Ismail R. Abdel-Rahim; Hadeel M.M. Khalil Bagy (Journal of Plant Pathology, 2022)

Microneedle-Based Vaccine Delivery: Review of an Emerging Technology - Ihab Mansoor; Heba A. Eassa; Kamilia H. A. Mohammed; Marwa A. Abd El-Fattah; Marwa H. Abdo; Eman Rashad; Hadeer A. Eassa; Asmaa Saleh; Omnya M. Amin; Mohamed Ismail Nounou; Ola Ghoneim (AAPS PharmSciTech, 2022)

Sarcoroseolides A-D, four undescribed cembranoids from the Red Sea soft coral Sarcophyton roseum - Mohammed M. A. Ahmed; Mohamed A. Albadry; Ehab A. Ragab; Elsayed M. El-Ghaly; Said K. Ismail; Zulfiqar Ali; Shabana I. Khan; Amar G. Chittiboyina; Ikhlas A. Khan (Natural Product Research, 2022)

Histopathological, Immunohistochemical, And Molecular Alterations In Brain Tissue And Submandibular Salivary Gland Of Atrazine-Induced Toxicity In Male Rats - Yasmine H. Ahmed; Huda O. AbuBakr; Ismail M. Ahmad; Zainab Sabry Othman Ahmed (Environmental Science and Pollution Research, 2022)

Development and adaptation of relative sunshine hours models for the equatorial latitudes: a case study - Stephen N. Nnamchi; Mustafa M. Mundu; Kelechi J. Ukagwu; Ismail A. Oyagbola (Modeling Earth Systems and Environment, 2022)

Spatiotemporal trends of temperature extremes in Bangladesh under changing climate using multi-statistical techniques - Javed Mallick; Abu Reza Md. Towfiqul Islam; Bonosri Ghose; H. M. Touhidul Islam; Yousuf Rana; Zhenghua Hu; Shakeel Ahmed Bhat; Subodh Chandra Pal; Zulhilmi Bin Ismail (Theoretical and Applied Climatology, 2022)

Investigating the Use of Stainless Steel Electrodes with the IP Method: A Metallic Ore Deposit Example - N. Yıldırım Gündoğdu; İsmail Demirci; Özcan Özyildirim; Hasan Aktarakçi; M. Emin Candansayar (Pure and Applied Geophysics, 2022)

Evaluation of the androgenic competence of 66 wild Turkish Vaccaria hispanica (Mill.) Rauschert genotypes through microspore culture - Esin Ari; Hilal Bedir; Ismail Gokhan Deniz; Ilker Genc; Jose M. Seguí-Simarro (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Adsorption performance and Kinetics study of Pb(II) by RuO2–ZnO nanocomposite: Construction and Recyclability - B. Mustafa; A. Modwi; M. Ismail; S. Makawi; T. Hussein; Z. Abaker; L. Khezami (International Journal of Environmental Science and Technology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Hypercholesterolemia and 27-Hydroxycholesterol Increase S100A8 and RAGE Expression in the Brain: a Link Between Cholesterol, Alarmins, and Neurodegeneration - Raúl Loera-Valencia; Muhammad-Al-Mustafa Ismail; Julen Goikolea; Maria Lodeiro; Laura Mateos; Ingemar Björkhem; Elena Puerta; Mariana A. Romão; Cláudio M. Gomes; Paula Merino-Serrais; Silvia Maioli; Angel Cedazo-Minguez (Molecular Neurobiology, 2021)
Alterations in cholesterol metabolism in the brain have a major role in the physiology of Alzheimer’s disease (AD). Oxysterols are cholesterol metabolites with multiple implications in memory functions and in neurodegeneration. Previous studies have shown detrimental effects of cholesterol metabolites in neurons, but its effect in glial cells is unknown. We used a high-fat/high-cholesterol diet in mice to study the effects of hypercholesterolemia over the alarmin S100A8 cascade in the hippocampus. Using CYP27Tg, a transgenic mouse model, we show that the hypercholesterolemia influence on the brain is mediated by the excess of 27-hydroxycholesterol (27-OH), a cholesterol metabolite. We also employed an acute model of 27-OH intraventricular injection in the brain to study RAGE and S100A8 response. We used primary cultures of neurons and astrocytes to study the effect of high levels of 27-OH over the S100A8 alarmin cascade. We report that a high-fat/high-cholesterol diet leads to an increase in S100A8 production in the brain. In CYP27Tg, we report an increase of S100A8 and its receptor RAGE in the hippocampus under elevated 27-OH in the brain. Using siRNA, we found that 27-OH upregulation of RAGE in astrocytes and neurons is mediated by the nuclear receptor RXRγ. Silencing RXRγ in neurons prevented 27-OH-mediated upregulation of RAGE. These results show that S100A8 alarmin and RAGE respond to high levels of 27-OH in the brain in both neurons and astrocytes through RXRγ. Our study supports the notion that 27-OH mediates detrimental effects of hypercholesterolemia to the brain via alarmin signaling.

Reduced root mycorrhizal colonization as affected by phosphorus fertilization is responsible for high cadmium accumulation in wheat - M. Atilla Yazici; Muhammad Asif; Yusuf Tutus; Ibrahim Ortas; Levent Ozturk; Hans Lambers; Ismail Cakmak (Plant and Soil, 2021)

Physiology and whole-plant carbon partitioning during stem sugar accumulation in sweet dwarf sorghum - Benjamin A. Babst; Abhijit Karve; Anthony Sementilli; Ismail Dweikat; David M. Braun (Planta, 2021)

Hydraulik und betriebliche Aspekte von Horizontalrechen-Bypass-Systemen - Julian Meister; Claudia Beck; Ismail Albayrak; Robert M. Boes (WASSERWIRTSCHAFT, 2021)

Bemessungsempfehlungen für den Fischschutz mit Horizontalrechen-Bypass-Systemen - Julian Meister; Claudia Beck; Ismail Albayrak; Robert M. Boes; Oliver M. Selz; Armin Peter (WASSERWIRTSCHAFT, 2021)

Non-coding Single Nucleotide Variants of Renin and the (Pro)renin Receptor are Associated with Polygenic Diseases in a Bangladeshi Population - Jobaida Akther; Ashish Das; Md Arifur Rahman; Sajoy Kanti Saha; Md Ismail Hosen; Akio Ebihara; Tsutomu Nakagawa; Fumiaki Suzuki; A. H. M. Nurun Nabi (Biochemical Genetics, 2021)

Acetylcholinesterase and α-glucosidase inhibitory compounds from Callicarpa maingayi - Muhammad A. Ado; M. Maulidiani; Intan Safinar Ismail; Hasanah M. Ghazali; Khozirah Shaari; Faridah Abas (Natural Product Research, 2021)

Electroflotation treatment of stabilized landfill leachate using titanium-based electrode - A. M. H. Shadi; M. A. Kamaruddin; N. M. Niza; M. I. Emmanuel; Md. S. Hossain; N. Ismail (International Journal of Environmental Science and Technology, 2021)

Post-harvest fish loss in the fish value chain and the determinants: empirical evidence from Bangladesh - Debasish Chandra Acharjee; Mohammad Ismail Hossain; G M Monirul Alam (Aquaculture International, 2021)

Experimental investigation of a new sustainable approach for recycling waste styrofoam food containers in lightweight concrete - Zainab Z. Ismail; Ali J. Jaeel; Abeer M. Alwared; Anita Závodská (Innovative Infrastructure Solutions, 2021)

Optimal routing of household waste collection using ArcGIS application: a case study of El Bousten district, Sfax city, Tunisia - Rim Sallem; Mohamed Moncef Serbaji; Abdullah M. Alamri; Amjad Kallel; Ismail Trabelsi (Arabian Journal of Geosciences, 2021)

Identification of a Cyclospora cayetanensis Oocyst Antigens and Their Validity in the Detection of Immunogenic Patterns of Cyclosporiasis Patients - Eman M. Hussein; Eman K. El-Gayar; Ola A. Ismail; Amira B. Mokhtar; Maha M. Al-Abbassy (Acta Parasitologica, 2021)

Factual approach for tropical forest parameters measurement and monitoring: future option with a focus on synergetic use of airborne and terrestrial LiDAR technologies - Muluken N. Bazezew; Yousif A. Hussin; Evert H. Kloosterman; Ismail M. Hasmadi; Teshome Soromessa; Marian S. Adan (International Journal of Remote Sensing, 2021)

Correction to: Effect of design and operational parameters on nutrients and heavy metal removal in pilot floating treatment wetlands with Eichhornia crassipes treating polluted lake water - Mohamed S. Gaballah; Khiary Ismail; Dominic Aboagye; Mona M. Ismail; Mostafa Sobhi; Alexandros I. Stefanakis (Environmental Science and Pollution Research, 2021)

Effect of design and operational parameters on nutrients and heavy metal removal in pilot floating treatment wetlands with Eichhornia Crassipes treating polluted lake water - Mohamed S. Gaballah; Khiary Ismail; Dominic Aboagye; Mona M. Ismail; Mostafa Sobhi; Alexandros I. Stefanakis (Environmental Science and Pollution Research, 2021)

Gum arabic-encapsulated gold nanoparticles modulate hypoxamiRs expression in tongue squamous cell carcinoma - Amira M. Gamal-Eldeen; Houry M. Baghdadi; Nermeen S. Afifi; Ebtehal M. Ismail; Walaa F. Alsanie; Fayez Althobaiti; Bassem M. Raafat (Molecular & Cellular Toxicology, 2021)

Surface water quality status and prediction during movement control operation order under COVID-19 pandemic: Case studies in Malaysia - A. Najah; F. Y. Teo; M. F. Chow; Y. F. Huang; S. D. Latif; S. Abdullah; M. Ismail; A. El-Shafie (International Journal of Environmental Science and Technology, 2021)

Assessment of the antioxidant and antibacterial properties of red algae (Rhodophyta) from the north coast of Tunisia - Imen Hmani; Leila Ktari; Amel Ismail; Cheima M’dallel; Monia El Bour (Euro-Mediterranean Journal for Environmental Integration, 2021)

Atmospheric and anthropogenic deterioration of the İvriz rock monument: Ereğli-Konya, Central Anatolia, Turkey - Mustafa Korkanç; İsmail İnce; M. Ergün Hatır; M. Bahadır Tosunlar (Bulletin of Engineering Geology and the Environment, 2021)

Mineralogical and geochemical characteristics of gold-hosted alteration zones in the Neoproterozoic arc metavolcanics at the Jabal Umm Watirah area, southwestern Saudi Arabia - Adel A. Surour; Hesham M. Harbi; Ismail Al-Sulbi (Arabian Journal of Geosciences, 2021)

Halogen content relative to the chemical and biochemical composition of fifteen marine macro and micro algae: nutritional value, energy supply, antioxidant potency, and health risk assessment - Gehan M. El Zokm; Mona M. Ismail; Ghada F. El-Said (Environmental Science and Pollution Research, 2021)

Impact of polluted open-drain geometry on groundwater contaminant in unconfined aquifers - Hany F. Abd-Elhamid; Abdelrahman M. Said; Gamal M. Abdelaal; Ismail Abd-Elaty (Arabian Journal of Geosciences, 2021)

Additive main effects and multiplicative interaction analyses of yield performance in rice genotypes for general and specific adaptation to salt stress in locations in India - S. L. Krishnamurthy; P. C. Sharma; D. K. Sharma; Y. P. Singh; V. K. Mishra; D. Burman; B. Maji; S. Mandal; S. K. Sarangi; R. K. Gautam; P. K. Singh; K. K. Manohara; et al. (Euphytica, 2021)
The aim of this study was to identify stable rice genotypes tolerant to a salt stress environment and to identify ideal mega-environments using AMMI (additive main effects and multiplicative interaction) stability model analysis. A total of 13 rice genotypes and three salt tolerance checks were evaluated across 13 salt stress locations (alkaline and saline) for the two kharif seasons of 2014 and 2015. Genotype CSR 36 (CHK3) was found to be the most ideal of those tested. Genotypes CHK2 (CST 27) and IR 87952-1-1-1-2-3-B (G05) were found to be the most stable, with above average yields. The check CSR 36 (CHK3) genotype was the best performer in the majority of the environments studied, followed by CSR 27 (CHK2) and IR 87952-1-1-1-2-3-B (G05) which were the best genotypes in the mega-environment consisting of 21 environments evaluated across stress locations and year combinations. Overall, the most promising genotype (IR 87952-1-1-1-2-3-B) had high mean yield and stability and could be used for commercial cultivation or used as donor for breeding programs across salt-affected soils. The genotypes GN13 (IR 87938-1-1-2-1-3-B) and GN11 (IR 87938-1-2-2-1-3-B) showed 60–80% yield advantage at specific salt stress locations, showing that these genotypes could be used for specific environments of salt-affected soils in India.

In silico analysis of phytoconstituents from Tinospora cordifolia with targets related to diabetes and obesity - Bijendra K. Mandar; Pukar Khanal; B. M. Patil; Yadu Nandan Dey; Ismail Pasha (In Silico Pharmacology, 2021)

Association study of leukocyte telomere length and genetic polymorphism within hTERT promoter with type 2 diabetes in Bangladeshi population - Atoll Goswami; Nafiul Huda; Tahirah Yasmin; Md. Ismail Hosen; A. K. M. Mahbub Hasan; A. H. M. Nurun Nabi (Molecular Biology Reports, 2021)

Human locomotion with reinforcement learning using bioinspired reward reshaping strategies - Katharine Nowakowski; Philippe Carvalho; Jean-Baptiste Six; Yann Maillet; Anh Tu Nguyen; Ismail Seghiri; Loick M’Pemba; Theo Marcille; Sy Toan Ngo; Tien-Tuan Dao (Medical & Biological Engineering & Computing, 2021)

Determination and Evaluation of Saltwater Intrusion on Bafra Plain: Joint Interpretation of Geophysical, Hydrogeological and Hydrochemical Data - İsmail Demirci; N. Yıldırım Gündoğdu; M. Emin Candansayar; Pantelis Soupios; Antonis Vafidis; Hakan Arslan (Pure and Applied Geophysics, 2020)

Silver Nanoparticles from Cow’s Milk to Combat Multidrug-Resistant Gram-Negative Bacteria from Clinical Isolates - Akshata G. Athreya; M. Ismail Shareef; S. M. Gopinath (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Estimation of Petrophysical Parameters from Seismic Inversion by Combining Particle Swarm Optimization and Multilayer Linear Calculator - Qamar Yasin; Ghulam M. Sohail; Yan Ding; Atif Ismail; Qizhen Du (Natural Resources Research, 2020)

A highly sensitive colorimetric assessment of hexavalent chromium using a digital camera - Ashraf A. Mohamed; Ethar M. Ismail; Samah Ali (Environmental Monitoring and Assessment, 2020)

Monitoring insecticide resistance and endosymbiont composition in greenhouse populations of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) from Mersin, Turkey - Mohammed A. Mohammed; M. Mete Karaca; İsmail Döker; Kamil Karut (Phytoparasitica, 2020)

Ozone and Ammonium Hydroxide Modification of Biochar Prepared from Pisum sativum Peels Improves the Adsorption of Copper (II) from an Aqueous Medium - Mohamed A. El-Nemr; Nabil M. Abdelmonem; Ibrahim M. A. Ismail; Safaa Ragab; Ahmed El Nemr (Environmental Processes, 2020)

Disruption of biofilm formation by fractions from book gills and carapace of horseshoe crab Tachypleus gigas - MuhdSyukeri Ahmad; Noraznawati Ismail; Ibrahim M. S. Eldeen (Marine Biology Research, 2020)

Seismic Hazard Analysis for Southern Slope of the Greater Caucasus (Azerbaijan) - G. Babayev; L. Telesca; S. Agayeva; T. Ismail-zade; I. Muradi; Y. Aliyev; M. Aliyev (Pure and Applied Geophysics, 2020)

Leveling-index based variable rate seeding technique for paddy - B. Abu Bakar; M. T. Ahmad; M. S. S. Ghazali; M. N. F. Abd Rani; M. A. Mhd Bookeri; M. S. Abdul Rahman; M. Z. K. Abdullah; R. Ismail (Precision Agriculture, 2020)

Farnesol attenuates oxidative stress and liver injury and modulates fatty acid synthase and acetyl-CoA carboxylase in high cholesterol-fed rats - Mohammad H. Abukhalil; Omnia E. Hussein; May Bin-Jumah; Sultan A. M. Saghir; Mousa O. Germoush; Hassan A. Elgebaly; Nermeen M. Mosa; Ismail Hamad; Moath M. Qarmush; Emad M. Hassanein; Emadeldin M. Kamel; Rene Hernandez-Bautista; et al. (Environmental Science and Pollution Research, 2020)

Carbapenem-resistant Enterobacteriaceae in patients with bacteraemia at tertiary hospitals in South Africa, 2015 to 2018 - O. Perovic; H. Ismail; V. Quan; C. Bamford; T. Nana; V. Chibabhai; P. Bhola; P. Ramjathan; K. Swe Swe-Han; J. Wadula; A. Whitelaw; M. Smith; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Laboratory air quality and microbiological contamination in a university building - Siti Amira ‘Ainaa’ Idris; Marlia M. Hanafiah; Marzuki Ismail; Samsuri Abdullah; Md Firoz Khan (Arabian Journal of Geosciences, 2020)

Thermodynamic study of the acid-induced decontamination of waste green sand generated in a brass foundry - Hikaru Sawai; Ismail M. M. Rahman; Naoyuki Jii; Yuji Egawa; Satoshi Mizutani; Hiroshi Hasegawa (Environmental Science and Pollution Research, 2020)

Evolution of petroleum generation and expulsion of the oil-source rock in the north-western Say’un-Masilah Basin as inferred from 1D basin models of a single well (Al-Qarn-01) - Mohammed Hail Hakimi; Abdulwahab S. Alaug; Aref A. Lashin; Madyan M. A. Yahya; Ismail M. Ismail; Ekhlas A. Al-Maghrabi; Shrook A. Mogram (Arabian Journal of Geosciences, 2020)

Improved separation of dyes and proteins using membranes made of polyphenylsulfone/cellulose acetate or acetate phthalate - Mithun Kumar; Arun M. Isloor; Somasekhara Rao Todeti; G. P. Syed Ibrahim; Inamuddin; Ahmed Fauzi Ismail; Abdullah M. Asiri (Environmental Chemistry Letters, 2020)

An assessment of deterioration in cultural heritage: the unique case of Eflatunpınar Hittite Water Monument in Konya, Turkey - Ali Bozdağ; İsmail İnce; Ayla Bozdağ; M. Ergün Hatır; M. Bahadır Tosunlar; Mustafa Korkanç (Bulletin of Engineering Geology and the Environment, 2020)

Emerging chitosan and cellulose green materials for ion exchange membrane fuel cell: a review - S. A. Muhmed; Nor Azureen Mohamad Nor; Juhana Jaafar; A. F. Ismail; M. H. D. Othman; Mukhlis A. Rahman; F. Aziz; N. Yusof (Energy, Ecology and Environment, 2020)

Treatment of emulsion oil using tannic acid/tetraethylenepentamine-supported polymeric membrane - F. Senusi; M. Shahadat; S. Ismail (International Journal of Environmental Science and Technology, 2019)

Recovery of uranium from the Um Samra-Um Bakra shear zone, central Eastern Desert, Egypt - M. S. Kamar; M. A. Hassanin; A. M. Ismail (Euro-Mediterranean Journal for Environmental Integration, 2019)

Numerical analysis of physical barriers systems efficiency in controlling saltwater intrusion in coastal aquifers - Ismail Abd-Elaty; Hany F. Abd-Elhamid; Mohaddeseh M. Nezhad (Environmental Science and Pollution Research, 2019)

Factors affecting the technical efficiency of turmeric farmers in the slash and burn areas of Bangladesh - Mst. Esmat Ara Begum; M. A. Monayem Miah; M. A. Rashid; Mohammad Ismail Hossain (Agroforestry Systems, 2019)

Synthesis, α-amylase inhibition and molecular docking study of bisindolylmethane sulfonamide derivatives - Muhammad Taha; Tayyaba Noreen; Syahrul Imran; Fasial Nawaz; Sridevi Chigurupati; Manikandan Selvaraj; Fazal Rahim; Nor Hadiani Ismail; Ashok Kumar; Ashik Mosaddik; Abdullah M. Alghamdi; Yousif Abdulrahman nasser alqahtani; et al. (Medicinal Chemistry Research, 2019)

Understanding the potential benefits of thyme and its derived products for food industry and consumer health: From extraction of value-added compounds to the evaluation of bioaccessibility, bioavailability, anti-inflammatory, and antimicrobial activities - Jose M. Lorenzo; Amin Mousavi Khaneghah; Mohsen Gavahian; Krystian Marszałek; Ismail Eş; Paulo E. S. Munekata; Isabel C. F. R. Ferreira; Francisco J. Barba (Critical Reviews in Food Science and Nutrition, 2019)

Bioaccumulation and biotransformation of arsenic by the brown macroalga Sargassum patens C. Agardh in seawater: effects of phosphate and iron ions - M. Abdullah Al Mamun; Yoshiki Omori; Rimana Islam Papry; Chika Kosugi; Osamu Miki; Ismail M. M. Rahman; Asami S. Mashio; Teruya Maki; Hiroshi Hasegawa (Journal of Applied Phycology, 2019)

Assessment of health risks associated with potentially toxic element contamination of soil by end-of-life ship dismantling in Bangladesh - Iftakharul Alam; Suman Barua; Kento Ishii; Satoshi Mizutani; Mohammad Mosharraf Hossain; Ismail M. M. Rahman; Hiroshi Hasegawa (Environmental Science and Pollution Research, 2019)

Microencapsulated Lactobacillus plantarum LAB12 Showed No Sign of Acute or Sub-chronic Toxicity In Vivo - Ismail M. Fareez; Siong Meng Lim; Kalavathy Ramasamy (Probiotics and Antimicrobial Proteins, 2019)

Hydrochemistry of Groundwater and its Suitability for Drinking and Irrigation in Baghdad, Iraq - Alhassan H. Ismail; Muntasir A. Shareef; Farid M. Alatar (Environmental Processes, 2019)

Geochemistry of subsurface Late Quaternary ironstones in Rajshahi and Bogra Districts, Bangladesh: implications for genetic and depositional conditions - Md. Sazzadur Rahman; Ismail Hossain; Pradip Kumar Biswas; Md. Abdur Rahim; A. S. M. Mehedi Hasan; Md. Ibrahim Adham (Acta Geochimica, 2019)

A Review of High Impact Weather for Aviation Meteorology - Ismail Gultepe; R. Sharman; Paul D. Williams; Binbin Zhou; G. Ellrod; P. Minnis; S. Trier; S. Griffin; Seong. S. Yum; B. Gharabaghi; W. Feltz; M. Temimi; et al. (Pure and Applied Geophysics, 2019)

A Meteorological Supersite for Aviation and Cold Weather Applications - Ismail Gultepe; M. Agelin-Chaab; J. Komar; G. Elfstrom; F. Boudala; B. Zhou (Pure and Applied Geophysics, 2019)

WRF Model Prediction of a Dense Fog Event Occurred During the Winter Fog Experiment (WIFEX) - Prakash Pithani; Sachin D. Ghude; V Naidu Chennu; Rachana G. Kulkarni; Gert-Jan Steeneveld; Ashish Sharma; Thara Prabhakaran; D. M. Chate; Ismail Gultepe; R. K. Jenamani; Rajeevan Madhavan (Pure and Applied Geophysics, 2019)

Biosynthesis of silver nanoparticles by cell-free extracts from some bacteria species for dye removal from wastewater - Nanis G. Allam; Gehan A. Ismail; Walaa M. El-Gemizy; Mohamed A. Salem (Biotechnology Letters, 2019)

Identification of candidate biomarkers in converting and non-converting clinically isolated syndrome by proteomics analysis of cerebrospinal fluid - O. Timirci-Kahraman; Z. Karaaslan; E. Tuzun; M. Kurtuncu; A. T. Baykal; T. Gunduz; M. B. Tuzuner; E. Akgun; B. Gurel; M. Eraksoy; Cem Ismail Kucukali (Acta Neurologica Belgica, 2019)

Bacterial leaf blight resistance in rice: a review of conventional breeding to molecular approach - S. C. Chukwu; M. Y. Rafii; S. I. Ramlee; S. I. Ismail; M. M. Hasan; Y. A. Oladosu; U. G. Magaji; Ibrahim Akos; K. K. Olalekan (Molecular Biology Reports, 2019)

Screening of electrocoagulation process parameters for treated palm oil mill effluent using minimum-runs resolution IV design - M. Mujeli; S. A. Hussain; M. H. S. Ismail; D. R. A. Biak; M. S. Jami (International Journal of Environmental Science and Technology, 2019)

Correction to: Functional Polymorphism Located in the microRNA Binding Site of the Insulin Receptor (INSR) Gene Confers Risk for Type 2 Diabetes Mellitus in the Bangladeshi Population - Mahrima Parvin; Farhana Jahan; Pankaj Kumar Sarkar; Zakir Hossain Howlader; A. H. M. Nurun Nabi; Md. Ismail Hosen (Biochemical Genetics, 2019)

Functional Polymorphism Located in the microRNA Binding Site of the Insulin Receptor (INSR) Gene Confers Risk for Type 2 Diabetes Mellitus in the Bangladeshi Population - Mahrima Parvin; Farhana Jahan; Pankaj Kumar Sarkar; Zakir Hossain Howlader; A. H. M. Nurun Nabi; Md. Ismail Hosen (Biochemical Genetics, 2019)

X-ray, structural assignment and molecular docking study of dihydrogeodin from Aspergillus Terreus TM8 - Abdelaaty Hamed; Mohamed Ismail; Mohammad M. El-Metwally; Marcel Frese; Hans Georg Stammler; Norbert Sewald; Mohamed Shaaban (Natural Product Research, 2019)

The Utilization of Electric Arc Furance Slag in Soil Improvement - A. I. M. Ismail; S. A. Awad; M. A. G. Mwafy (Geotechnical and Geological Engineering, 2019)

Hepatoprotective activity of Uncaria tomentosa extract against sub-chronic exposure to fipronil in male rats - Rania Abdelrahman Elgawish; Heba M. A. Abdelrazek; Shimaa A. A. Ismail; Naglaa M. Loutfy; Mohamed T. A. Soliman (Environmental Science and Pollution Research, 2019)

Environmental hazards associated with open-beach breaking of end-of-life ships: a review - Suman Barua; Ismail M. M. Rahman; Mohammad Mosharraf Hossain; Zinnat A. Begum; Iftakharul Alam; Hikaru Sawai; Teruya Maki; Hiroshi Hasegawa (Environmental Science and Pollution Research, 2018)

Landslide susceptibility mapping of Blue Nile and Tekeze River Basins using oblique rainfall-aspect rasters - Elamin H. Ismail; J. David Rogers; M. Farooq Ahmed; E. Lynn Usery; Mohamed G. Abdelsalam (Bulletin of Engineering Geology and the Environment, 2018)

Heterotrophic bacteria associated with the green alga Ulva rigida: identification and antimicrobial potential - A. Ismail; L. Ktari; M. Ahmed; H. Bolhuis; Balkiss Bouhaouala-Zahar; L. J. Stal; A. Boudabbous; M. El Bour (Journal of Applied Phycology, 2018)

Changes in nutritional values induced by butachlor in juvenile diploid and triploid Clarias gariepinus - A. Karami; S. Karbalaei; M. Ebrahimi; A. Ismail; M. F. Jahromi; S. L. Simpson; P. Eghtesadi Araghi; R. P. Lim; J. B. Liang (International Journal of Environmental Science and Technology, 2018)

Delineation of contamination zone using geophysical and hydrogeochemical methods around the El Moheet drain in the El Minia district, Upper Egypt - M Abou Heleika; E Ismail; M. Ahmed (Arabian Journal of Geosciences, 2018)

Prime-boost vaccination strategy against avian influenza and Newcastle disease viruses reduces shedding of the challenge viruses - Nermeen M. Ismail; Ayman H. El-Deeb; Mohamed M. Emara; Hoda I. Tawfik; Nabil Abdel Wanis; Hussein A. Hussein (VirusDisease, 2018)

Cellulose Derivatives Enhanced Stability of Alginate-Based Beads Loaded with Lactobacillus plantarum LAB12 against Low pH, High Temperature and Prolonged Storage - Ismail M. Fareez; Siong Meng Lim; Nurul Aida Ashyqin Zulkefli; Rakesh K. Mishra; Kalavathy Ramasamy (Probiotics and Antimicrobial Proteins, 2018)

Finite element modelling and validation for breast cancer detection using digital image elasto-tomography - Hina M. Ismail; Chris G. Pretty; Matthew K. Signal; Marcus Haggers; J. Geoffrey Chase (Medical & Biological Engineering & Computing, 2018)

Genetic variants in components of the NALCN–UNC80–UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies) - Nuria C. Bramswig; Aida M. Bertoli-Avella; Beate Albrecht; Aida I. Al Aqeel; Amal Alhashem; Nouriya Al-Sannaa; Maissa Bah; Katharina Bröhl; Christel Depienne; Nathalie Dorison; Diane Doummar; Nadja Ehmke; et al. (Human Genetics, 2018)

Saponin-adjuvanted vaccine protects chickens against velogenic Newcastle disease virus - Wahid H. El-Dabae; Hussein Aly Hussein; Mohammed A. Rohaim; Munir M. El-Safty; Nagwa S. Ata; Ismail M. Reda (Archives of Virology, 2018)

FEG-EPMA mapping and Fe-Ti oxide mineral chemistry of Brahmaputra River sediments in Bangladesh: provenance and petrogenetic implications - A. S. M. Mehedi Hasan; Ismail Hossain; Md. Aminur Rahman; Md. Sazzadur Rahman; Mohammad Nazim Zaman; Pradip Kumar Biswas (Arabian Journal of Geosciences, 2018)

Wind-Induced Air-Flow Patterns in an Urban Setting: Observations and Numerical Modeling - Ahmed M. A. Sattar; Mohamed Elhakeem; Bishoy N. Gerges; Bahram Gharabaghi; Ismail Gultepe (Pure and Applied Geophysics, 2018)

Metabolomic analysis and biochemical changes in the urine and serum of streptozotocin-induced normal- and obese-diabetic rats - Ahmed Mediani; Faridah Abas; M. Maulidiani; Azliana Abu Bakar Sajak; Alfi Khatib; Chin Ping Tan; Intan Safinar Ismail; Khozirah Shaari; Amin Ismail; N. H. Lajis (Journal of Physiology and Biochemistry, 2018)

Dual protective effect of ginger and rosemary extracts against CCl4-induced hepatotoxicity in rats - Amina E. Essawy; Wessam M. Abdel-Wahab; Ismail A. Sadek; Omnia M. Khamis (Environmental Science and Pollution Research, 2018)

Measuring Crop Water Requirement and Crop Coefficient for Blue Panic Crop Under Arid Conditions Using Draining Lysimeters - Saleh M. Ismail; Fathy S. El‐Nakhlawy (Irrigation and Drainage, 2018)
Previous research results of Blue Panic ( Panicum antidotale Retz) in arid conditions under different irrigation methods proved an increase in forage yield and water productivity (WP) under full and water stress conditions. However, a thorough search in the literature revealed that its water requirement has not yet been determined. Therefore the objective of this research was to measure evapotranspiration (ET c ) and crop coefficient ( K c ) for a Blue Panic crop under arid conditions. Four draining lysimeters constructed in Jeddah (21° 48′ 3′′ N, 39° 43′ 25′′ E) were used to measure its ET c and K c under a plentiful water supply. Results revealed that ET c varied from 141 mm in the first harvest to 292 mm in the sixth, with an average of 225 mm per harvest. The K c value was different from one harvest to another. The average K c over all harvests was 0.7, 1.2, 1.3 and 1.0 for the initial, development, midseason and late stages, respectively. Average fresh and dry forage yields per harvest were 30.5 and 12.6 t ha −1 , respectively. Average WP was 55 kg ha −1 mm −1 . The predicted ET c based on the measured crop coefficient value and ET 0 show a good fit between measured and calculated ET c . Copyright © 2018 John Wiley & Sons, Ltd.

Petrography, diagenesis and isotope geochemistry of dolostones and dolocretes in the Eocene Dammam Formation, Kuwait, Arabian Gulf - Fikry I. Khalaf; Fowzia A. Abdullah; Ismail M. Gharib (Carbonates and Evaporites, 2018)

Mitochondrial signatures revealed panmixia in Lutjanus argentimaculatus (Forsskål 1775) - A. Gopalakrishnan; N. Vineesh; Shihab Ismail; Muktha Menon; K. V. Akhilesh; N. S. Jeena; M. P. Paulton; P. Vijayagopal (Journal of Genetics, 2018)

Production of Lightweight Concretes from Pumice/Bentonite Mix - A. I. M. Ismail; E. R. Souaya; M. Fathy; A. Abd El-Hakeem (Geotechnical and Geological Engineering, 2018)

Best available science still supports an ancient common origin of Devils Hole and Devils Hole pupfish - İsmail K. Sağlam; Jason Baumsteiger; Matt J. Smith; Javier Linares‐Casenave; Andrew L. Nichols; Sean M. O'Rourke; Michael R. Miller (Molecular Ecology, 2018)
The age of DHP and how pupfish colonized Devils Hole have always been a topic of interest. Recently, two different publications (Martin, Crawford, Turner, & Simons, & Sağlam et al., ) tackled this issue using genomic data sets and demographic models but came to widely different conclusions. In their comment, Martin and Höhne ( ) argue that our results (Sağlam et al., ) were misleading because we used inappropriate calibration information and biased a priori assumptions. They then re‐analysed our data using a “biologically informed” mutation rate prior and concluded that our data support a much younger age of DHP (12.6 kya) as opposed to 60 kya reported in our study. Below we will summarize why their arguments do not hold up and explore some of the inconsistencies between their claims and what was actually presented in our study. Furthermore, we will demonstrate their re‐analyses provide no new information compared to what was presented in our original manuscript and reinforce our estimate of a 60 kya divergence of DHP as outweighing competing hypotheses.

Synthesis, structural characterization and anticancer evaluation of pyrazole derivatives - Mohamed S. A. El-Gaby; Mustafa M. Ghorab; Zainb H. Ismail; Soad. M. Abdel-Gawad; Hala. M. Aly (Medicinal Chemistry Research, 2018)

A review on mechanism and future perspectives of cadmium-resistant bacteria - S. Z. Abbas; M. Rafatullah; K. Hossain; N. Ismail; H. A. Tajarudin; H. P. S. Abdul Khalil (International Journal of Environmental Science and Technology, 2018)

Mining the global diversity of barley for Fusarium resistance using leaf and spike inoculations - Ismail M. A. Bedawy; Heinz-Wilhelm Dehne; Jens Léon; Ali Ahmad Naz (Euphytica, 2018)

Molecular and phenotypic characterization of transgenic wheat and sorghum events expressing the barley alanine aminotransferase - Pamela A. Peña; Truyen Quach; Shirley Sato; Zhengxiang Ge; Natalya Nersesian; Ismail M. Dweikat; Madhavan Soundararajan; Tom Clemente (Planta, 2017)

Suppression of PGE2 production via disruption of MAPK phosphorylation by unsymmetrical dicarbonyl curcumin derivatives - Mohd Fadhlizil Fasihi Mohd Aluwi; Kamal Rullah; Md. Areeful Haque; Bohari M. Yamin; Waqas Ahmad; Muhammad Wahab Amjad; Sze Wei Leong; Nurul Amira Fahmizar; Juriyati Jalil; Faridah Abas; Nor Hadiani Ismail; Ibrahim Jantan; et al. (Medicinal Chemistry Research, 2017)

Variation in biochemical constituents and master elements in common seaweeds from Alexandria Coast, Egypt, with special reference to their antioxidant activity and potential food uses: prospective equations - Mona M. Ismail; Gehan M. El Zokm; Abeer A. M. El-Sayed (Environmental Monitoring and Assessment, 2017)

Biochemical indicators of root damage in rice (Oryza sativa) genotypes under zinc deficiency stress - Jae-Sung Lee; Matthias Wissuwa; Oscar B. Zamora; Abdelbagi M. Ismail (Journal of Plant Research, 2017)

Late Cretaceous spore-pollen zonation of the Central African Rift System (CARS), Kaikang Trough, Muglad Basin, South Sudan: angiosperm spread and links to the Elaterates Province - James M. Cole; Omer Babiker Abdelrahim; Aaron W. Hunter; Eckart Schrank; Mohd Suhaili Bin Ismail (Palynology, 2017)

Critical success factors for public housing projects in developing countries: a case study of Nigeria - Musa M. Mukhtar; Roslan Bin Amirudin; Trevor Sofield; Ismail Bin Mohamad (Environment, Development and Sustainability, 2017)

Impact of organic contents and brittleness indices to differentiate the brittle-ductile transitional zone in shale gas reservoir - Qamar Yasin; Qizhen Du; Ghulam M. Sohail; Atif Ismail (Geosciences Journal, 2017)

Anti-proliferative study and isolation of Ochnaflavone from the ethyl acetate-soluble fraction of Ochna kibbiensis Hutch & Dalziel - Abdullahi M. Ismail; Aliyu M. Musa; Tajuddeen Nasir; Mohammed G. Magaji; Yusuf A. Jega; Iliya Ibrahim (Natural Product Research, 2017)

Discrimination of Ipomoea aquatica cultivars and bioactivity correlations using NMR-based metabolomics approach - U. Lawal; M. Maulidiani; K. Shaari; I. S. Ismail; A. Khatib; F. Abas (Plant Biosystems, 2017)

Genetic dissection for zinc deficiency tolerance in rice using bi-parental mapping and association analysis - Jae-Sung Lee; Andres Godwin C. Sajise; Glenn B. Gregorio; Tobias Kretzschmar; Abdelbagi M. Ismail; Matthias Wissuwa (Theoretical and Applied Genetics, 2017)

Transforming rice cultivation in flood prone coastal Odisha to ensure food and economic security - Manzoor H. Dar; Ritadhi Chakravorty; Showkat A. Waza; Mayank Sharma; Najam W. Zaidi; Amrendra N. Singh; Umesh S. Singh; Abdelbagi M. Ismail (Food Security, 2017)

Aeromagnetic signature analysis of Gasus area and its surrounding, central eastern desert, Egypt - O. A. Zaki; S. H. AbdAlnabi; S E. Abd El Wahab; A. A. Ismail; N. M. Soliman (Arabian Journal of Geosciences, 2017)

Case Series Study of Invasive Pulmonary Aspergillosis - Ana I. Aller-García; Carmen Castro-Méndez; Ana Alastruey-Izquierdo; Elena M. Marín-Martínez; Ismail Zakariya-Yousef Breval; Carmen Couto-Caro; Juan C. López-Marín; Nicolás Peña-Griñán; Maite Ruiz de Pipaon; Ana M. Romero-Mejías; Estrella Martín-Mazuelos (Mycopathologia, 2017)

Virtual water trade in industrial products: evidence from Malaysia - A. Hassan; M. Y. Saari; T. H. Tengku Ismail (Environment, Development and Sustainability, 2017)

Electrical and electromagnetic surveys to locate possible causes of water seepage to ground surface at a quarry open pit near Helwan city, Egypt - Hany S. Mesbah; Ahmed Ismail; Ayman I. Taha; Usama Massoud; Mamdouh M. Soilman (Arabian Journal of Geosciences, 2017)

Onion purple blotch symptoms, at Assiut Governorate (Egypt), caused by synergistic association between Alternaria porri and Stemphylium vesicarium - Ismail R. Abdel-Rahim; Sobhy I. I. Abdel-Hafez; Kamal A. M. Abo-Elyousr (Journal of Plant Diseases and Protection, 2017)

Laboratory culture experiments to study the effect of lignite humic acid fractions on iron solubility and iron uptake rates in phytoplankton - Hiroshi Hasegawa; Yousuke Tate; Masashi Ogino; Teruya Maki; Zinnat A. Begum; Toshiharu Ichijo; Ismail M. M. Rahman (Journal of Applied Phycology, 2017)

Occurrence of jarosite within Quaternary coastal sabkha sediments in Kuwait, Arabian Gulf - Abdullah Al Zamel; Fikry I. Khalaf; Ismail M. Gharib (Arabian Journal of Geosciences, 2017)

Emergence of new virulent rabbit hemorrhagic disease virus strains in Saudi Arabia - Mahmoud M. Ismail; Mahmoud H. A. Mohamed; Ibrahim M. El-Sabagh; Mohamed A. Al-Hammadi (Tropical Animal Health and Production, 2017)

Ameliorative effect of kolaviron, a biflavonoid complex from Garcinia kola seeds against scopolamine-induced memory impairment in rats: role of antioxidant defense system - Ismail O. Ishola; Folasade M. Adamson; Olufunmilayo O. Adeyemi (Metabolic Brain Disease, 2017)

Variation in oxidative stress indices of two green seaweeds growing under different heavy metal stresses - Gehan A. Ismail; Mona M. Ismail (Environmental Monitoring and Assessment, 2017)

Molecular markers: a potential resource for ginger genetic diversity studies - Nor Asiah Ismail; M. Y. Rafii; T. M. M. Mahmud; M. M. Hanafi; Gous Miah (Molecular Biology Reports, 2016)

Development of salt tolerant IR64 near isogenic lines through marker-assisted breeding - Viet The Ho; Michael J. Thomson; Abdelbagi M. Ismail (Journal of Crop Science and Biotechnology, 2016)

Facies analysis and sequence stratigraphy of Kometan Formation (Upper Cretaceous) in the imbricated zone, northeastern Iraq - Sardar M. Balaky; Irfan Sh. Asaad; Ali Ismail Al-Juboury (Arabian Journal of Geosciences, 2016)

Evaluation of exposure of pemphigus vulgaris patients to Mycobacterium tuberculosis and Aspergillus fumigatus - R. A. Ali; R. H. Elsherif; M. A. Saleh; M. H. Ismail (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Megalencephalic leukoencephalopathy with cysts in twelve Egyptian patients: novel mutations in MLC1 and HEPACAM and a founder effect - Ghada M. H. Abdel-Salam; Mohamed S. Abdel-Hamid; Samira I. Ismail; Heba Hosny; Tarek Omar; Laila Effat; Mona S. Aglan; Samia A. Temtamy; Maha S. Zaki (Metabolic Brain Disease, 2016)

The use of multiplex PCR for the diagnosis of viral severe acute respiratory infection in children: a high rate of co-detection during the winter season - A. A. El Kholy; N. A. Mostafa; A. A. Ali; M. M. S. Soliman; S. A. El-Sherbini; R. I. Ismail; N. El Basha; R. I. Magdy; N. El Rifai; D. H. Hamed (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Effect of Water Regimes and Palm Coefficient on Growth Parameters, Date Yield and Irrigation Water Use of Tissue Culture‐Regenerated ‘Barhee’ Date Palms Grown in a Newly Established Orchard - Adel D. Al‐Qurashi; Saleh M. Ismail; Mohamed A. Awad (Irrigation and Drainage, 2016)
A field experiment was carried out at the Agriculture Experimental Station of King Abdulaziz University during the 2013 and 2014 seasons to study the effect of water regimes and palm coefficient on growth parameters, yield and irrigation water use (IWU) of tissue culture‐derived ‘Barhee’ date palm cultivars in a newly established orchard. Four water regimes T1, T2, T3 and T4 representing 70, 85, 100 and 115% of water requirement were studied to select the best water regime that maximizes yield and IWU. Water requirement in 2013 was calculated based on the FAO palm coefficient ( K p ) but based on measured K p during 2014. Results revealed that using measured K p reduces water requirements in the summer season and increases date yield. It saves about 12% of irrigation water compared to FAO K p . Increasing the water regime increased yield per palm, where the highest yield was obtained from T4 (16.5 kg per tree), and the least from T1(12.4 kg per tree). IWU is increased by decreasing the water regime. However, the differences between T4 and T3 were not significant, indicating that giving the highest water regime produces the highest yield. It is concluded that increasing water supply maximizes yield production of young tissue culture‐derived ‘Barhee’ date palms in a newly established orchard. Copyright © 2016 John Wiley & Sons, Ltd.

Monitoring Snow Using Geostationary Satellite Retrievals During the SAAWSO Project - Robert M. Rabin; Ismail Gultepe; Robert J. Kuligowski; Andrew K. Heidinger (Pure and Applied Geophysics, 2016)

Biodegradation of ketoprofen using a microalgal–bacterial consortium - Maha M. Ismail; Tamer M. Essam; Yasser M. Ragab; Fathia E. Mourad (Biotechnology Letters, 2016)

In vitro and in vivo comparison of the biological activities of two traditionally and widely used Arum species from Jordan: Arum dioscoridis Sibth & Sm. and Arum palaestinum Boiss. - Fatma U. Afifi; Violet Kasabri; Simona C. Litescu; Ismail M. Abaza (Natural Product Research, 2016)

Fischschutz und Fischabstieg mittels vertikaler Leitrechen-Bypass-Systeme: Rechenverluste und Leiteffizienz - Robert M. Boes; Ismail Albayrak; Carl Robert Kriewitz; Armin Peter (WASSERWIRTSCHAFT, 2016)

Phylogenetics support an ancient common origin of two scientific icons: Devils Hole and Devils Hole pupfish - İsmaİl K. Sağlam; Jason Baumsteiger; Matt J. Smith; Javier Linares‐Casenave; Andrew L. Nichols; Sean M. O'Rourke; Michael R. Miller (Molecular Ecology, 2016)
The Devils Hole pupfish ( Cyprinodon diabolis ; DHP ) is an icon of conservation biology. Isolated in a 50 m 2 pool (Devils Hole), DHP is one of the rarest vertebrate species known and an evolutionary anomaly, having survived in complete isolation for thousands of years. However, recent findings suggest DHP might be younger than commonly thought, potentially introduced to Devils Hole by humans in the past thousand years. As a result, the significance of DHP from an evolutionary and conservation perspective has been questioned. Here we present a high‐resolution genomic analysis of DHP and two closely related species, with the goal of thoroughly examining the temporal divergence of DHP . To this end, we inferred the evolutionary history of DHP from multiple random genomic subsets and evaluated four historical scenarios using the multispecies coalescent. Our results provide substantial information regarding the evolutionary history of DHP . Genomic patterns of secondary contact present strong evidence that DHP were isolated in Devils Hole prior to 20–10 ka and the model best supported by geological history and known mutation rates predicts DHP diverged around 60 ka, approximately the same time Devils Hole opened to the surface. We make the novel prediction that DHP colonized and have survived in Devils Hole since the cavern opened, and the two events (colonization and collapse of the cavern's roof) were caused by a common geologic event. Our results emphasize the power of evolutionary theory as a predictive framework and reaffirm DHP as an important evolutionary novelty, worthy of continued conservation and exploration.

Maximizing Production and Irrigation Water Productivity of Canola Crop ( Brassica Napus L.) Under Arid Land Conditions - Saleh M. Ismail (Irrigation and Drainage, 2016)
A field experiment was carried out at the Agricultural Experimental Research Station of King Abdulaziz University to study the effect of irrigation level, row spacing and inter‐row spacing on productivity and irrigation water productivity (IWP) of Canola. Two irrigation levels, I Full (100% of field capacity) and I min (65% of I Full ), were investigated. Three row spacing, S1, S2 and S3, represented by 20, 40 and 60 cm between rows were studied under each irrigation level. Three inter‐row spacing, IRS1, IRS2 and IRS3, represented by 5, 10 and 20 cm between plants, were investigated for each row spacing. Results indicated that I min reduced seed yield per plant, total seed yield and oil percentage but increased IWP. Decreasing row and inter‐row spacing decreased seed yield per plant but increased total seed yield and IWP. The highest oil percentage (36.1%) was obtained from S2 during both growing seasons. The triple interaction optimized total seed yield, IWP and oil production. The best combination was I Full– S1–IRS2 with average production of 8430 kg ha −1 seed yield which is expected to produce 2990 kg of oil, followed by I min– S1–IRS1 which produced 6750 kg ha −1 seed yield with about 2270 kg ha −1 of oil. Application of this combination saves 35% of water but reduces oil production by 24%. Copyright © 2016 John Wiley & Sons, Ltd.

Variation in bioactive compounds in some seaweeds from Abo Qir bay, Alexandria, Egypt - Mona M. Ismail; Saly F. Gheda; Leonel Pereira (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Molecular-Level Characterization of Normal, Benign, and Malignant Breast Tissues Using FTIR Spectroscopy - Wael M. Elshemey; Alaa M. Ismail; Nihal S. Elbialy (Journal of Medical and Biological Engineering, 2016)

Assessing ambient ozone injury in olive (Olea europaea L.) plants by using the antioxidant ethylenediurea (EDU) in Saudi Arabia - J. M. Basahi; I. M. Ismail; N. S. Haiba; I. A. Hassan; G. Lorenzini (Environmental Monitoring and Assessment, 2016)

Local community acceptance of the rare earth industry: the case of the Lynas Advanced Materials Plant (LAMP) in Malaysia - T. H. Tengku Ismail; H. Juahir; A. Z. Aris; Sharifuddin M. Zain; Armi Abu Samah (Environment, Development and Sustainability, 2016)

Analysis of Stability and G × E Interaction of Rice Genotypes across Saline and Alkaline Environments in India - S. L. Krishnamurthy; S. K. Sharma; D. K. Sharma; P. C. Sharma; Y. P. Singh; V. K. Mishra; D. Burman; B. Maji; B. K. Bandyopadhyay; S. Mandal; S. K. Sarangi; R. K. Gautam; et al. (Cereal Research Communications, 2016)

Formulation and In Vitro and In Vivo Evaluation of Lipid-Based Terbutaline Sulphate Bi-layer Tablets for Once-Daily Administration - Fahima M. Hashem; Mohamed Nasr; Gihan Fathy; Aliaa Ismail (AAPS PharmSciTech, 2016)

A novel antimicrobial flavonoid from the stem bark of Commiphora pedunculata (Kotschy & Peyr.) Engl. - Nasir Tajuddeen; Muhammad S. Sallau; Aliyu M. Musa; Sani M. Yahaya; James D. Habila; Abdullahi Musa Ismail (Natural Product Research, 2016)

Middle Miocene ostracods from Wadi Sudr, westcentral Sinai, Egypt: systematic, biostratigraphy and palaeobiogeographic affinity with the Mediterranean realm - Ibrahim M. Ied; Abdelmoneim S. A. Ismail (Arabian Journal of Geosciences, 2016)

Variation of slant path Ka/V-band rain attenuation over seven tropical locations in Nigeria using synthetic storm techniques - J. S. Ojo; A. T. Adediji; J. S. Mandeep; M. Ismail (Theoretical and Applied Climatology, 2016)

Use of Cement Kiln Dust on the Engineering Modification of Soil Materials, Nile Delta, Egypt - A. I. M. Ismail; Z. L. Belal (Geotechnical and Geological Engineering, 2016)

Chemical composition and bioactivities of the essential oil from different organs of Ferula communis L. growing in Tunisia - Asma Nguir; Hajer Mabrouk; Wahiba Douki; Manel Ben Ismail; Hichem Ben Jannet; Guido Flamini; M’hamed Ali Hamza (Medicinal Chemistry Research, 2016)

Evaluation of pesticide residues of organochlorine in vegetables and fruits in Qatar: statistical analysis - Noora M. Al-Shamary; Mohammad A. Al-Ghouti; Ismail Al-Shaikh; Saeed H. Al-Meer; Talaat A. Ahmad (Environmental Monitoring and Assessment, 2016)

Sublethal imidacloprid effects on honey bee flower choices when foraging - Ahmed Karahan; Ibrahim Çakmak; John M. Hranitz; Ismail Karaca; Harrington Wells (Ecotoxicology, 2015)

Curcumin Ameliorates Lead (Pb2+)-Induced Hemato-Biochemical Alterations and Renal Oxidative Damage in a Rat Model - Ashraf M. Abdel-Moneim; Mona Y. El-Toweissy; Awatef M. Ali; Abd Allah M. Awad Allah; Hanaa S. Darwish; Ismail A. Sadek (Biological Trace Element Research, 2015)

Determining the site effects of 23 October 2011 earthquake (Van province, Turkey) on the rural areas using HVSR microtremor method - İsmail Akkaya; Ali Özvan; Mücip Tapan; M Alper Şengül (Journal of Earth System Science, 2015)

Synthesis, Spectral Characteristics and DFT Studies of the New Dye 2,7-diacetyl-9-((dimethylamino)methylene)-9H-fluorene (DMMF) in Different Solvents - Abdullah M. Asiri; Saleh A. Ahmed; Samy A. El-Daly; Mahmoud A. Hussein; Amerah M. Al-Soliemy; Osman I. Osman; Mohamed R. Shaaban; Ismail I. Althagafi (Journal of Fluorescence, 2015)

Predicting Eucalyptus spp. stand volume in Zululand, South Africa: an analysis using a stochastic gradient boosting regression ensemble with multi-source data sets - Timothy Dube; Onisimo Mutanga; Elfatih M. Abdel-Rahman; Riyad Ismail; Rob Slotow (International Journal of Remote Sensing, 2015)

Contamination of rice field water with sulfonylurea and phenoxy herbicides in the Muda Irrigation Scheme, Kedah, Malaysia - B. S. Ismail; S. Prayitno; M. A. Tayeb (Environmental Monitoring and Assessment, 2015)

Poly-3-hydroxybutyrate (PHB) production by Bacillus flexus ME-77 using some industrial wastes - Mostafa M. El-Sheekh; Mostafa A. El-Abd; Ahmed I. El-Diwany; Abdel-mohsen S. Ismail; Thanaa H. Omar (Rendiconti Lincei. Scienze Fisiche e Naturali, 2015)

Molecular modeling design, synthesis, and anti-hyprglycemic evaluation of certain 5-(aryl-alkoxy-benzylidine)-imidazolidine-2,4-dione derivatives as potential PPARγ agonists - Mohamed A. H. Ismail; Dalal A. Abou El Ella; Khaled A. M. Abouzid; Nermin Samir Abdou; Antoon Lahham (Medicinal Chemistry Research, 2015)

How the Dyes Are Degraded/Mineralized in a Photocatalytic System? The Possible Role of Auxochromes - M. Aslam; Iqbal M. I. Ismail; S. Chandrasekaran; Huda A. Qari; A. Hameed (Water, Air, & Soil Pollution, 2015)

Chelant-Assisted Depollution of Metal-Contaminated Fe-Coated Sands and Subsequent Recovery of the Chemicals Using Solid-Phase Extraction Systems - Ismail M. M. Rahman; Zinnat A. Begum; Hikaru Sawai; Masashi Ogino; Yoshiaki Furusho; Satoshi Mizutani; Hiroshi Hasegawa (Water, Air, & Soil Pollution, 2015)

Erratum to: Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid Mohammed Khan; Sammer Yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid M. Khan; Sammer yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Antimicrobial susceptibility profiles, serotype distribution and virulence determinants among invasive, non-invasive and colonizing Streptococcus agalactiae (group B streptococcus) from Malaysian patients - N. Eskandarian; Z. Ismail; V. Neela; A. van Belkum; M. N. M. Desa; S. Amin Nordin (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Accelerating the development of new submergence tolerant rice varieties: the case of Ciherang-Sub1 and PSB Rc18-Sub1 - Endang M. Septiningsih; Nurul Hidayatun; Darlene L. Sanchez; Yudhistira Nugraha; Jerome Carandang; Alvaro M. Pamplona; Bertrand C. Y. Collard; Abdelbagi M. Ismail; David J. Mackill (Euphytica, 2015)

Design, synthesis, and antihypertensive evaluation of 2′-tetrazolyl and 2′-carboxy-biphenylylmethyl-pyrrolidine scaffolds substituted at their N1, C3, and C4 positions as potential angiotensin II AT1 receptor antagonists - Mohamed A. H. Ismail; Mohamed Nabil Aboul-Enein; Aida Abd ElSatar El-Azzouny; Khaled A. M. Abouzid; Nasser S. M. Ismail (Medicinal Chemistry Research, 2015)

Synthesis of indole-2-hydrazones in search of potential leishmanicidal agents - Muhammad Taha; Nor Hadiani Ismail; Muhammad Ali; Khalid M. Khan; Waqas Jamil; Syed Muhammad Kashif; Mohammad Asraf (Medicinal Chemistry Research, 2014)

A novel plasmid pEA68 of Erwinia amylovora and the description of a new family of plasmids - Emadeldeen Ismail; Jochen Blom; Alain Bultreys; Milan Ivanović; Aleksa Obradović; Joop van Doorn; Maria Bergsma-Vlami; Martine Maes; Anne Willems; Brion Duffy; Virginia O. Stockwell; Theo H. M. Smits; et al. (Archives of Microbiology, 2014)

Immobilization of Ni and Cd in Soil by Biochar Derived From Unfertilized Dates - M. Ehsan; M. A. Barakat; Dalal Z. Husein; S. M. Ismail (Water, Air, & Soil Pollution, 2014)

Recovery of the Rare Metals from Various Waste Ashes with the Aid of Temperature and Ultrasound Irradiation Using Chelants - Hiroshi Hasegawa; Ismail M. M. Rahman; Yuji Egawa; Hikaru Sawai; Zinnat A. Begum; Teruya Maki; Satoshi Mizutani (Water, Air, & Soil Pollution, 2014)

The Quality Control of Engineering Properties for Stabilizing Silty Nile Delta Clay Soil, Egypt - A. I. M. Ismail; N. Ryden (Geotechnical and Geological Engineering, 2014)

Investigation of groundwater potentiality in the eastern part of Qena, central Eastern Desert, Egypt, using 2D homogeneous function method - A. E. El-Haddad; A M. El-Akraby; I. S. Ismail; A. M. Abdel Gowad (Arabian Journal of Geosciences, 2014)

Zinc and Homocysteine Levels in Polycystic Ovarian Syndrome Patients with Insulin Resistance - Ismail Guler; Ozdemir Himmetoglu; Ahmet Turp; Ahmet Erdem; Mehmet Erdem; M. Anıl Onan; Cagatay Taskiran; Mine Yavuz Taslipinar; Haldun Guner (Biological Trace Element Research, 2014)

QTL mapping for tolerance of anaerobic germination from IR64 and the aus landrace Nanhi using SNP genotyping - Miriam D. Baltazar; John Carlos I. Ignacio; Michael J. Thomson; Abdelbagi M. Ismail; Merlyn S. Mendioro; Endang M. Septiningsih (Euphytica, 2014)

Effect of Intraoperative Heparin Administration on Some Indices of the Blood Coagulatory-Lytic System in the Ischemic Region of the Small Intestine with Anastomosis - S. A. Markos’yan; N. M. Lysyakov; M. A. Ismail Alawal; K. I. Irkova; I. V. Martyanov (Bulletin of Experimental Biology and Medicine, 2014)

Nickel removal from electroplating waste water using stand-alone and electrically assisted ion exchange processes - I. Ismail; A. Soliman; N. Abdel-Monem; H. Salah Ahmed; M. H. Sorour (International Journal of Environmental Science and Technology, 2014)

OPTIMIZATION OF IRRIGATION WATER USE, YIELD, AND QUALITY OF 'NABBUT‐SAIF' DATE PALM UNDER DRY LAND CONDITIONS - Saleh M. Ismail; Adel D. Al‐Qurashi; Mohamed A. Awad (Irrigation and Drainage, 2014)
A field experiment was conducted in the western part of Saudi Arabia to optimize irrigation water use (IWU), yields and quality of the 'Nabbut‐Saif' date palm grown in sandy loam soil under arid conditions. Four water regimes were investigated. The supplied amounts of irrigation water were 50, 65, 82 and 100% of date palm water requirements to the first (W1), second (W2), third (W3) and fourth (W4) water regimes, respectively. The daily water requirement was calculated using the Penman–Montieth equation for dry climates and applied to the trees three times a week through a drip irrigation system. Results indicated that giving 65% of total date palm water requirement maximized date yield by producing 46.1 kg per tree and resulted in the best IWU (0.8 m 3 kg −1 per tree). Increasing the water regime to 82 and 100% of total water requirement produced only 45.5 and 46 kg per tree respectively and reduced IWU. Generally, fruit quality characteristics were insignificantly affected by the water regimes investigated. The results suggested that supplying 34 m 3 yr −1 per tree for date palms grown under the conditions of the western part of Saudi Arabia is enough to maximize IWU, yield and quality of the 'Nabbut‐Saif' date palm cultivar. Copyright © 2014 John Wiley & Sons, Ltd.

Estimating standing biomass in papyrus ( Cyperus papyrus L.) swamp: exploratory of in situ hyperspectral indices and random forest regression - Elhadi Adam; Onisimo Mutanga; Elfatih M. Abdel-Rahman; Riyad Ismail (International Journal of Remote Sensing, 2014)

The Monitoring Network of the Vancouver 2010 Olympics - Paul Joe; Bill Scott; Chris Doyle; George Isaac; Ismail Gultepe; Douglas Forsyth; Stewart Cober; Edwin Campos; Ivan Heckman; Norman Donaldson; David Hudak; Roy Rasmussen; et al. (Pure and Applied Geophysics, 2014)

Weather observations on Whistler Mountain during five storms - Julie M. Thériault; Kristen L. Rasmussen; Teresa Fisico; Ronald E. Stewart; Paul Joe; Ismail Gultepe; Marilys Clément; George A. Isaac (Pure and Applied Geophysics, 2014)

Synthesis, molecular docking of novel 1,8-naphthyridine derivatives and their cytotoxic activity against HepG2 cell lines - Ahmad F. Eweas; Nagy M. Khalifa; Nisreen S. Ismail; Mohamed A. Al-Omar; Abdel Mohsen M. Soliman (Medicinal Chemistry Research, 2014)

Socio-ecological systems and biodiversity conservation in African city: Insights from Kano Emir’s Palace gardens - Aliyu Salisu Barau; A. N. M. Ludin; Ismail Said (Urban Ecosystems, 2013)

Laboratory investigation on measuring suspended sediment by portable laser diffractometer (LISST) focusing on particle shape - David Felix; Ismail Albayrak; Robert M. Boes (Geo-Marine Letters, 2013)

Synthesis, characterization, bioactivity, and POM analyses of isothiochromeno[3,4-e][1,2]oxazines - Brahim Bennani; Abdelali Kerbal; Bouchra F. Baba; Maria Daoudi; Ismail Warad; Mohamad Aljofan; Ahmed M. Alafeefy; Vijay Masand; Taibi B. Hadda (Medicinal Chemistry Research, 2013)

Engineering Properties, Microstructure and Strength Development of Lightweight Concrete Containing Pumice Aggregates - A. I. M. Ismail; M. S. Elmaghraby; H. S. Mekky (Geotechnical and Geological Engineering, 2013)

Herders’ Perceptions of and Responses to Climate Change in Northern Pakistan - S. Joshi; W. A. Jasra; M. Ismail; R. M. Shrestha; S. L. Yi; N. Wu (Environmental Management, 2013)

Assessing building vulnerability to earthquake and tsunami hazard using remotely sensed data - M. Mück; H. Taubenböck; J. Post; S. Wegscheider; G. Strunz; S. Sumaryono; F. A. Ismail (Natural Hazards, 2013)

First insights into the metagenome of Egyptian mummies using next-generation sequencing - Rabab Khairat; Markus Ball; Chun-Chi Hsieh Chang; Raffaella Bianucci; Andreas G. Nerlich; Martin Trautmann; Somaia Ismail; Gamila M. L. Shanab; Amr M. Karim; Yehia Z. Gad; Carsten M. Pusch (Journal of Applied Genetics, 2013)

Inhibition of In Vitro TNF-α Production by Anisomeles malabarica R.Br. Reinforces Its Anti-Rheumatic and Immunomodulatory Properties - M. Ismail Shareef; S. Leelavathi; Anis Ahmed Shariff (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Selective Separation of Tri- and Pentavalent Arsenic in Aqueous Matrix with a Macrocycle-Immobilized Solid-Phase Extraction System - Ismail M. M. Rahman; Zinnat A. Begum; Yoshiaki Furusho; Satoshi Mizutani; Teruya Maki; Hiroshi Hasegawa (Water, Air, & Soil Pollution, 2013)

QTL mapping and confirmation for tolerance of anaerobic conditions during germination derived from the rice landrace Ma-Zhan Red - Endang M. Septiningsih; John Carlos I. Ignacio; Pamella M. D. Sendon; Darlene L. Sanchez; Abdelbagi M. Ismail; David J. Mackill (Theoretical and Applied Genetics, 2013)

Investigations of storms in the region of Marmara in Turkey - Ali Deniz; E. Tuncay Özdemir; İsmail Sezen; M. Coşkun (Theoretical and Applied Climatology, 2013)

Synthesis of some (E)-6-[2-(furan-2-yl)ethenyl]-1,2,4-triazin-5-ones and their biological evaluation as antitumor agents - Hayam M. Ashour; Marwa H. El-Wakil; Mounir A. Khalil; Khadiga A. Ismail; Ibrahim M. Labouta (Medicinal Chemistry Research, 2013)

Modulatory Effect of Lycopene on Deltamethrin-Induced Testicular Injury in Rats - Manal F. Ismail; Hanaa M. Mohamed (Cell Biochemistry and Biophysics, 2013)

Long-term monitoring programme of the hydrological variability in the Mediterranean Sea: a first overview of the HYDROCHANGES network - K. Schroeder; C. Millot; L. Bengara; S. Ben Ismail; M. Bensi; M. Borghini; G. Budillon; V. Cardin; L. Coppola; C. Curtil; A. Drago; B. El Moumni; et al. (Ocean Science, 2013)
The long-term monitoring of basic hydrological parameters (temperature and salinity), collected as time series with adequate temporal resolution (i.e. with a sampling interval allowing the resolution of all important timescales) in key places of the Mediterranean Sea (straits and channels, zones of dense water formation, deep parts of the basins), constitute a priority in the context of global changes. This led CIESM (The Mediterranean Science Commission) to support, since 2002, the HYDROCHANGES programme (http//www.ciesm.org/marine/programs/hydrochanges.htm), a network of autonomous conductivity, temperature, and depth (CTD) sensors, deployed on mainly short and easily manageable subsurface moorings, within the core of a certain water mass. The HYDROCHANGES strategy is twofold and develops on different scales. To get information about long-term changes of hydrological characteristics, long time series are needed. But before these series are long enough they allow the detection of links between them at shorter timescales that may provide extremely valuable information about the functioning of the Mediterranean Sea. The aim of this paper is to present the history of the programme and the current set-up of the network (monitored sites, involved groups) as well as to provide for the first time an overview of all the time series collected under the HYDROCHANGES umbrella, discussing the results obtained thanks to the programme.

Effect of Extraction Variables on the Biodegradable Chelant-Assisted Removal of Toxic Metals from Artificially Contaminated European Reference Soils - Zinnat A. Begum; Ismail M. M. Rahman; Hikaru Sawai; Satoshi Mizutani; Teruya Maki; Hiroshi Hasegawa (Water, Air, & Soil Pollution, 2013)

Applying Minimum Night Flow to Estimate Water Loss Using Statistical Modeling: A Case Study in Kinta Valley, Malaysia - Jaber M. A. Alkasseh; Mohd Nordin Adlan; Ismail Abustan; Hamidi Abdul Aziz; Abu Bakar Mohamad Hanif (Water Resources Management, 2013)

Blast resistance in rice: a review of conventional breeding to molecular approaches - G. Miah; M. Y. Rafii; M. R. Ismail; A. B. Puteh; H. A. Rahim; R. Asfaliza; M. A. Latif (Molecular Biology Reports, 2013)

Archaeological exploration using magnetic and GPR methods at the first court of Hatshepsut Temple in Luxor, Egypt - Hatem Odah; Ahmed Ismail; Ibrahim Elhemaly; Neil Anderson; Abbas M. Abbas; Fathy Shaaban (Arabian Journal of Geosciences, 2013)

Novel 2-thiopyrimidine derivatives as CDK2 inhibitors: molecular modeling, synthesis, and anti-tumor activity evaluation - Omar Abd El-Fattah M. Fathalla; Mohamed A. H. Ismail; Manal M. Anwar; Khaled A. M. Abouzid; Aisha A. K. Ramadan (Medicinal Chemistry Research, 2013)

MAXIMIZING PRODUCTIVITY AND WATER USE EFFICIENCY OF ALFALFA UNDER PRECISE SUBSURFACE DRIP IRRIGATION IN ARID REGIONS - Saleh M. Ismail; Mohammed H. Almarshadi (Irrigation and Drainage, 2013)
A field experiment studying the effect of water stress on alfalfa ( Medicago sativa ) productivity and water use efficiency was conducted at the Agricultural Experimental Station of King Abdelaziz University. The design of the experiment was randomized complete block design (RCBD) with four replicates. It consisted of three treatments, namely: field capacity treatment (FC) as a control, 85% FC and 70% FC as stress treatments. The irrigation water for all treatments was precisely supplied using recent technology known as the water electronics module (WEM). Results indicated that decreasing water supply decreased fresh and dry yield of alfalfa but increased irrigation water use efficiency (IWUE). As a result, 13 and 27% of irrigation water were saved from 85% FC and 70% FC treatments respectively in each cut compared with the FC treatment. The reduction of water supply resulted in a yield reduction of 12 and 21.7% for 85% FC and 70% FC, respectively. The results also proved that WEM is a practical tool to precisely supply irrigation water and can be used effectively to control deficit irrigation. Copyright © 2013 John Wiley & Sons, Ltd.

Random forest regression and spectral band selection for estimating sugarcane leaf nitrogen concentration using EO-1 Hyperion hyperspectral data - Elfatih M. Abdel-Rahman; Fethi B. Ahmed; Riyad Ismail (International Journal of Remote Sensing, 2013)

Soil fertility management effects on maize productivity and grain zinc content in smallholder farming systems of Zimbabwe - Grace M. Manzeke; Paul Mapfumo; Florence Mtambanengwe; Regis Chikowo; Takesure Tendayi; Ismail Cakmak (Plant and Soil, 2012)

Genetic analysis of the effect of zinc deficiency on Arabidopsis growth and mineral concentrations - Artak Ghandilyan; Umit Baris Kutman; Bahar Yildiz Kutman; Ismail Cakmak; Mark G. M. Aarts (Plant and Soil, 2012)

Synthesis, DNA affinity, and antimicrobial activity of 4-substituted phenyl-2,2′-bichalcophenes and aza-analogues - Magdy M. Youssef; Mohammed A. Al-Omair; Mohamed A. Ismail (Medicinal Chemistry Research, 2012)

Generation of the Sotos syndrome deletion in mice - Anna M. Migdalska; Louise van der Weyden; Ozama Ismail; Alistair G. Rust; Mamunur Rashid; Jacqueline K. White; Gabriela Sánchez-Andrade; James R. Lupski; Darren W. Logan; Mark J. Arends; David J. Adams (Mammalian Genome, 2012)

Lasiodiplodia species associated with dieback disease of mango (Mangifera indica) in Egypt - A. M. Ismail; G. Cirvilleri; G. Polizzi; P. W. Crous; J. Z. Groenewald; L. Lombard (Australasian Plant Pathology, 2012)

Removal of Residual Oils from Palm Oil Mill Effluent by Adsorption on Natural Zeolite - M. A. Shavandi; Z. Haddadian; M. H. S. Ismail; N. Abdullah; Z. Z. Abidin (Water, Air, & Soil Pollution, 2012)

A 3-tier tsunami vulnerability assessment technique for the north-west coast of Peninsular Malaysia - H. Ismail; A. K. Abd Wahab; M. F. Mohd Amin; M. Z. Mohd Yunus; F. Jaffar Sidek; B. Esfandier J. (Natural Hazards, 2012)

16S rRNA gene sequences analysis of Ficus elastica rubber latex degrading thermophilic Bacillus strain ASU7 isolated from Egypt - Abd El-Latif Hesham; Nadia H. Mohamed; Mady A. Ismail; Ahmed A. M. Shoreit (Biodegradation, 2012)

Essential oil composition of the aerial parts of fresh and air-dried Salvia palaestina Benth. (Lamiaceae) growing wild in Jordan - Hala I. Al-Jaber; Mahmoud A. Al-Qudah; Lina M. Barhoumi; Ismail F. Abaza; Fatma U. Afifi (Natural Product Research, 2012)

Protective role of nitric oxide against arsenic-induced damages in germinating mung bean seeds - Ghada Saber M. Ismail (Acta Physiologiae Plantarum, 2012)

Measurement of radionuclides and absorbed dose rates in soil samples of Peshawar, Pakistan, using gamma ray spectrometry - Hasan M. Khan; Muhammad Ismail; Muhammad Abid Zia; Khalid Khan (Isotopes in Environmental and Health Studies, 2012)

Jania rubens-associated bacteria: molecular identification and antimicrobial activity - A. Ismail-Ben Ali; M. El Bour; L. Ktari; H. Bolhuis; M. Ahmed; A. Boudabbous; L. J. Stal (Journal of Applied Phycology, 2012)

Discriminating the papyrus vegetation ( Cyperus papyrus L.) and its co-existent species using random forest and hyperspectral data resampled to HYMAP - E. M. Adam; O. Mutanga; D. Rugege; R. Ismail (International Journal of Remote Sensing, 2012)

Effect of Zinc and Iron Fortification of the Feed on Liver and Thyroid Function in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; M. Riaz; Muhammad Arshad; Abdul Basit; Tariq Ismail (Biological Trace Element Research, 2011)

Impact of Trace Element Changes on Dehydroepiandrosterone Sulfate in Healthy and Diabetic States among Middle-Age and Elderly Egyptians - Noha M. El Husseiny; Elham Sobhy Said; Naglaa El Shahat Mohamed; Azza Ismail Othman (Biological Trace Element Research, 2011)

Effects of implementing satellite observed aerosols into a mesoscale atmosphere model - Emine Bay; Ismail Yucel; Tom Kovacs; M. Patrick Mccormick (International Journal of Remote Sensing, 2011)

Genetic characterization of highly pathogenic H5N1 avian influenza viruses isolated from poultry farms in Egypt - Abd Elfattah H. Eladl; Kamel I. Abou El-Azm; Abd Elshakour N. Ismail; Ahmed Ali; Yehia M. Saif; Chang-Won Lee (Virus Genes, 2011)

Formulation, Characterization, and Clinical Evaluation of Microemulsion Containing Clotrimazole for Topical Delivery - Fahima M. Hashem; Dalia S. Shaker; Mohamed Khalid Ghorab; Mohamed Nasr; Aliaa Ismail (AAPS PharmSciTech, 2011)

Measurement of Radionuclides and Gamma-Ray Dose Rate in Soil and Transfer of Radionuclides from Soil to Vegetation, Vegetable of Some Northern Area of Pakistan Using γ-Ray Spectrometry - Hasan M. Khan; M. Ismail; Khalid Khan; Perveen Akhter (Water, Air, & Soil Pollution, 2011)

Isolation and screening of potential actinobacteria for rapid composting of rice straw - H. Kausar; M. Sariah; H. Mohd Saud; M. Zahangir Alam; M. Razi Ismail (Biodegradation, 2011)

Clinico-pathological findings and cerebrospinal fluid analysis in llamas (Lama glama) experimentally infected with the meningeal worm Parelaphostrongylus tenuis - Zuhair Bani Ismail; M. Levy; T. Qureshi; M. W. Lankester (European Journal of Wildlife Research, 2011)

Stagnant surface water bodies (SSWBs) as an alternative water resource for the Chittagong metropolitan area of Bangladesh: physicochemical characterization in terms of water quality indices - Ismail Md. Mofizur Rahman; M. Monirul Islam; M. Mosharraf Hossain; M. Shahadat Hossain; Zinnat A. Begum; Didarul A. Chowdhury; Milan K. Chakraborty; M. Azizur Rahman; M. Nazimuddin; Hiroshi Hasegawa (Environmental Monitoring and Assessment, 2011)

Assessment of Radionuclides, Trace Metals and Radionuclide Transfer from Soil to Food of Jhangar Valley (Pakistan) Using Gamma-Ray Spectrometry - Hasan M. Khan; Zahid S. Chaudhry; Muhammad Ismail; Khalid Khan (Water, Air, & Soil Pollution, 2010)

Molecular marker survey and expression analyses of the rice submergence-tolerance gene SUB1A - Namrata Singh; Trang T. M. Dang; Georgina V. Vergara; Dev Mani Pandey; Darlene Sanchez; C. N. Neeraja; Endang M. Septiningsih; Merlyn Mendioro; Evelyn Mae Tecson-Mendoza; Abdelbagi M. Ismail; David J. Mackill; Sigrid Heuer (Theoretical and Applied Genetics, 2010)

Distribution and Normalization of some Metals in Surface Sediments from South Caspian Sea - T. Sohrabi; A. Ismail; M. B. Nabavi (Bulletin of Environmental Contamination and Toxicology, 2010)

Levels of ABA, its precursors and dehydrin-like proteins during mangrove leaf development and senescence - FAR Ismail; M Masoud; JWM Derksen; C Mariani (Western Indian Ocean Journal of Marine Science, 2010)

Erratum to: Development and application of gene-based markers for the major rice QTL Phosphorus uptake 1 - Joong Hyoun Chin; Xiaochun Lu; Stephan M. Haefele; Rico Gamuyao; Abdelbagi Ismail; Matthias Wissuwa; Sigrid Heuer (Theoretical and Applied Genetics, 2010)

Development and application of gene-based markers for the major rice QTL Phosphorus uptake 1 - Joong Hyoun Chin; Xiaochun Lu; Stephan M. Haefele; Rico Gamuyao; Abdelbagi Ismail; Matthias Wissuwa; Sigrid Heuer (Theoretical and Applied Genetics, 2010)

Interpopulation Crosses, Inheritance Study, and Genetic Variability in the Brown Planthopper Complex, Nilaparvata lugens (Homoptera: Delphacidae) - M. A. Latif; Mohd. Yosuh Omar; Soon Guan Tan; Siti Shapor Siraj; Abdul Rahim Ismail (Biochemical Genetics, 2010)

QTLs associated with tolerance of flooding during germination in rice (Oryza sativa L.) - S. Abdolhamid Angaji; Endang M. Septiningsih; D. J. Mackill; Abdelbagi M. Ismail (Euphytica, 2010)

Phenotypic correlations, G × E interactions and broad sense heritability analysis of grain and flour quality characteristics in high latitude spring bread wheats from Kazakhstan and Siberia - Hugo Ferney Gómez-Becerra; Aigul Abugalieva; Alexei Morgounov; K. Abdullayev; L. Bekenova; M. Yessimbekova; G. Sereda; S. Shpigun; V. Tsygankov; Yu Zelenskiy; Roberto Javier Peña; Ismail Cakmak (Euphytica, 2010)

Management of palm oil mill effluent through production of cellulases by filamentous fungi - Shah Samiur Rashid; Md. Zahangir Alam; M. Ismail A. Karim; M. Hamzah Salleh (World Journal of Microbiology and Biotechnology, 2009)

Lonazolac analogues: molecular modeling, synthesis, and in vivo anti-inflammatory activity - Mohamed A. H. Ismail; Jochen Lehmann; Dalal A. Abou El Ella; Amgad Albohy; Khaled A. M. Abouzid (Medicinal Chemistry Research, 2009)

Surface circulation in the Eastern Mediterranean using drifters (2005–2007) - R. Gerin; P.-M. Poulain; I. Taupier-Letage; C. Millot; S. Ben Ismail; C. Sammari (Ocean Science, 2009)
Within the framework of the EGITTO/EGYPT programs, the spatial structure and the temporal variability of the surface circulation in the eastern basin of the Mediterranean Sea was studied with satellite-tracked drifters. A total of 97 drifters drogued to 15-m nominal depth were released between September 2005 and March 2007, regularly along ship-of-opportunity routes in the Sicily Channel and within specific structures during dedicated campaigns in the Levantine sub-basin. This study complements previous ones in the former and in the Ionian, but it is the first one in the latter. After editing and low-pass filtering, the drifter trajectories were used to estimate pseudo-Eulerian statistics: mean current, variance ellipses, mean and eddy kinetic energies. A statistical analysis was also performed dividing the dataset in two extended seasons (winter and summer). A branching behaviour of the surface water after passing through the Sicily Channel is evidenced, together with a seasonal variability inducing a reversal of the circulation in the southern part of the Ionian. In the Levantine, the surface circulation describes an eastward flow along the Libyan and Egyptian slopes (the Libyo-Egyptian Current: LEC) that continues in a cyclonic circuit along the Middle East and Turkish slopes. This general alongslope circuit can be perturbed locally and temporally by the numerous anticyclonic eddies that co-exist in the Levantine, mainly created by the instability of the LEC in the south (Libyo-Egyptian Eddies: LEEs), but also by the wind (Ierapetra and Pelops), and by the topography (over the Eratosthenes Seamount and off Latakia). The most frequent perturbation is the entrainment of part of the flow seaward: the LEEs close to the slope can interact with the LEC, which then spreads more or less around them, so that a series of contiguous LEEs (paddle-wheel effect) can possibly result in an eastward offshore transport (the so-called Mid Mediterranean Jet). Additionally, when LEEs are close enough to the slope, most of the surface flow is spread seaward. Along the slope the current is then induced by the LEEs southern side which results in a westward current. Locally and temporally the circulation along the slope can thus be reversed.

Hydrogeophysical study of the El Qaa Plain, Sinai, Egypt - Sultan Awad Sultan; Mahmoud Ismail Mohameden; Fernando M. Santos (Bulletin of Engineering Geology and the Environment, 2009)

Acidic Rocks as Aggregates in Concrete: Engineering Properties, Microstructures and Petrologic Characteristics - A. I. M. Ismail; D. Sadek Ghabrial (Geotechnical and Geological Engineering, 2009)

Cloning of a xylanase gene xyn2A from rumen fungus Neocallimastix sp. GMLF2 in Escherichia coli and its partial characterization - Ismail Akyol; Ugur Comlekcioglu; Bulent Kar; M. Sait Ekinci; Emin Ozkose (Biologia, 2009)

Effect of Host Medium on the Fluorescence Emission Intensity of Rhodamine B in Liquid and Solid Phase - M. Fikry; M. M. Omar; Lotfi Z. Ismail (Journal of Fluorescence, 2009)

Helicobacter pylori cagA gene variants in Malaysians of different ethnicity - Ramelah Mohamed; Alfizah Hanafiah; Isa M. Rose; Mohd Rizal A. Manaf; Shiekh Anwar Abdullah; Ismail Sagap; A. van Belkum; Jasmi A. Yaacob (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Analysis of heavy metal concentrations in sediments of selected estuaries of Malaysia—a statistical assessment - Abbas F. M. Alkarkhi; Norli Ismail; Aness Ahmed; Azhar mat Easa (Environmental Monitoring and Assessment, 2009)

Potential of Water Hyacinth as a Removal Agent for Heavy Metals from Petroleum Refinery Effluents - Z. Ismail; A. M. Beddri (Water, Air, & Soil Pollution, 2009)

Variations in tomato (Lycopersicon esculentum) cultivars grown under heat stress - A. Mansour; H. M. Ismail; Mohamed Fawzy Ramadan; G. Gyulai (Journal of Consumer Protection and Food Safety, 2009)

On the use of gravity and magnetic anomalies for locating probable areas of metallic mineralization in South Sinai, Egypt - El-Arabi H. Shendi; A. M. Ismail; Tamer E. Attia (Arabian Journal of Geosciences, 2008)

Quantitative assessment of total and Gram-positive aerobic bacteria in fresh and ambient-temperature-stored sub-tropical marine fish - Ismail M. Al Bulushi; Susan Poole; Hilton C. Deeth; Gary A. Dykes (World Journal of Microbiology and Biotechnology, 2008)

Multivariate analysis of heavy metals concentrations in river estuary - Abbas F. M. Alkarkhi; Anees Ahmad; Norli Ismail; Azhar Mat Easa (Environmental Monitoring and Assessment, 2008)

A Laser doppler study of the effect of 2-alkylthio-4-ethyl-4-methyl-4,5 dihydro-1H-imidazolin-5-one oxime (oxime) on the ischaemic rat lower limb - R. E. Mostafa; A. A. Sleem; O. M. E. Abdel-Salam; M. Abdel-Hamid Ismail; A. E. Khalifa (Inflammopharmacology, 2008)

Rice grain zinc concentrations as affected by genotype, native soil-zinc availability, and zinc fertilization - Matthias Wissuwa; Abdelbagi M. Ismail; Robin D. Graham (Plant and Soil, 2008)

Development of Enteric Coated Flurbiprofen Tablets using Opadry/acryl-eze System—A Technical Note - Durriya Hashmat; M. Harris Shoaib; Zafar Alam Mehmood; Rabia Bushra; Rabia Ismail Yousuf; Fahim Lakhani (AAPS PharmSciTech, 2008)

Genetic and genomic approaches to develop rice germplasm for problem soils - Abdelbagi M. Ismail; Sigrid Heuer; Michael J. Thomson; Matthias Wissuwa (Plant Molecular Biology, 2007)

Acaricidal activity of spinosad and abamectin against two-spotted spider mites - Manal S. M. Ismail; Maha F. M. Soliman; Moustafa H. El Naggar; Mona M. Ghallab (Experimental and Applied Acarology, 2007)

A marker-assisted backcross approach for developing submergence-tolerant rice cultivars - C. N. Neeraja; R. Maghirang-Rodriguez; A. Pamplona; S. Heuer; B. C. Y. Collard; E. M. Septiningsih; G. Vergara; D. Sanchez; K. Xu; A. M. Ismail; D. J. Mackill (Theoretical and Applied Genetics, 2007)

Influence of a niosomal formulation on the oral bioavailability of acyclovir in rabbits - Ismail A. Attia; Sanaa A. El-Gizawy; Medhat A. Fouda; Ahmed M. Donia (AAPS PharmSciTech, 2007)

Trichoderma harzianum: a biocontrol agent against Bipolaris oryzae - Gamal M. Abdel-Fattah; Yasser M. Shabana; Adel E. Ismail; Younes Mohamed Rashad (Mycopathologia, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Disposition Kinetics of Difloxacin After Intravenous, Intramuscular and Subcutaneous Administration in Calves - M. Ismail (Veterinary Research Communications, 2007)

Iron and zinc grain density in common wheat grown in Central Asia - Alexei Morgounov; Hugo Ferney Gómez-Becerra; Aigul Abugalieva; Mira Dzhunusova; M. Yessimbekova; Hafiz Muminjanov; Yu Zelenskiy; Levent Ozturk; Ismail Cakmak (Euphytica, 2007)

New pyrazolic compounds as cytotoxic agents - Ibrahim Bouabdallah; Lahcen Ait M’barek; Abdelmajid Zyad; Abdelkrim Ramdani; Ismail Zidane; Ahmed Melhaoui (Natural Product Research, 2007)

Genome-wide transcriptional analysis of salinity stressed japonica and indica rice genotypes during panicle initiation stage - Harkamal Walia; Clyde Wilson; Linghe Zeng; Abdelbagi M. Ismail; Pascal Condamine; Timothy J. Close (Plant Molecular Biology, 2007)

Approximate Methods for the Estimation of Muskingum Flood Routing Parameters - Jasem M. Al-Humoud; Ismail I. Esen (Water Resources Management, 2006)

Xanthones from Garcinia mangostana (Guttiferae) - G. C. L. Ee; S. Daud; Y. H. Taufiq-Yap; N. H. Ismail; M. Rahmani (Natural Product Research, 2006)

Anticancer effect of three pyrazole derivatives - Ibrahim Bouabdallah; Lahcen Ait M’Barek; Abdelmajid Zyad; Abdelkrim Ramdani; Ismail Zidane; Ahmed Melhaoui (Natural Product Research, 2006)

Synthesis and evaluation of 2,6-piperidinedione derivatives as potentially novel compounds with analgesic and other CNS activities - S. A. El Batran; A. E. N. Osman; M. M. Ismail; A. M. El Sayed (Inflammopharmacology, 2006)

A new coumarin and triterpenes from Malaysian Micromelum minutum - Ratna Asmah Susidarti; Mawardi Rahmani; Hazar B. M. Ismail; M. Aspollah Sukari; Taufiq-Yap Yun Hin; Gwendoline Ee Cheng Lian; Abdul Manaf Ali; Julius Kulip; Peter G. Waterman (Natural Product Research, 2006)

Biochemical study of the anti-diabetic action of the Egyptian plants Fenugreek and Balanites - Mohamed Z. Gad; Maha M. El-Sawalhi; Manal F. Ismail; Nibal D. El-Tanbouly (Molecular and Cellular Biochemistry, 2006)

Tissue-Specific Expression and Drought Responsiveness of Cell-Wall Invertase Genes of Rice at Flowering - X. M. Ji; M. Raveendran; R. Oane; A. Ismail; R. Lafitte; R. Bruskiewich; S. H. Cheng; J. Bennett (Plant Molecular Biology, 2005)

Endocytosis and vesicle trafficking during tip growth of root hairs - M. Ovečka; I. Lang; F. Baluška; A. Ismail; P. Illeš; I. K. Lichtscheidl (Protoplasma, 2005)

Novel Pirfenidone Analogs as Antifibrotic Agents: Synthesis and Antifibrotic Evaluation of 2-Pyridones and Fused Pyridones - Magda M. F. Ismail; Eman Noaman (Medicinal Chemistry Research, 2005)

Study on Organochlorine Compounds in Cockles, Anadara granosa and Mussels, Perna viridis from Aquaculture Sites in Peninsular Malaysia - C. W. Ang; N. M. Mazlin; L. Y. Heng; B. S. Ismail; S. Salmijah (Bulletin of Environmental Contamination and Toxicology, 2005)

Disposition Kinetics of Difloxacin in Rabbit after Intravenous and Intramuscular Injection of Dicural - A.M. Abd El-Aty; A. Goudah; M. Ismail; M. Shimoda (Veterinary Research Communications, 2005)

Evaluating the quality and storage stability of fish burgers during frozen storage - Ismail M. AL-BULUSHI; Stefan KASAPIS; Hamed AL-OUFI; Sultan AL-MAMARI (Fisheries Science, 2005)

Simulation of continuous and surge flow irrigation under short field conditions - Saleh M. Ismail; Herman Depeweg (Irrigation and Drainage, 2005)

Water productivity and crop production simulation under surge flow irrigation in short furrows in Egypt - Saleh M. Ismail; Herman Depeweg (Irrigation and Drainage, 2005)

Surge flow irrigation under short field conditions in Egypt - Saleh M. Ismail; Herman Depeweg; Bart Schultz (Irrigation and Drainage, 2004)
Several studies carried out in long furrows have shown that surge flow irrigation offers the potential of increasing the efficiency of irrigation. The effects of surge flow in short fields, such as in Egypt, are still not well known, however. To investigate the effect of surge flow irrigation in short fields a series of experiments have been carried out at two different locations in Egypt. The first location with a clay soil was situated at the Agriculture Experimental Station, Assiut University, Assiut. The second location with a sandy soil was situated at the Assiut University Experimental Station for Desert Land, El‐Wadi El‐Assuity, Assiut. The blocked end furrow lengths and widths were 70 and 0.70 m respectively. Three discharges were selected for each soil type, namely 0.46, 0.74 and 0.90 l s −1 for clay soil and 0.73, 1.0 and 1.4 l s −1 for sandy soil. For each discharge two cycle times were investigated, namely 16 and 24 minutes. For each cycle time three cycle ratios were chosen, 1/4, 1/2 and 3/4 for the 16‐minute and 1/3, 1/2, and 2/3 for the 24‐minute cycle time. The water content was measured at three locations, namely at the beginning, middle and end of the furrow. In each location three points were measured in a vertical line at a depth of 0–0.1, 0.1–0.3 and 0.3–0.7 m. The results show that surge flow irrigation leads to a more uniform water distribution along the furrows than continuous flow. This uniformity is more pronounced in clay soil than in sandy soil. Surge flow irrigation decreases the advance time in comparison to continuous flow. The reduction in advance time was more pronounced with the discharges of 0.74 and 1.0 l s −1 in clay and sandy soil respectively. The 24‐minute cycle time is better than the 16‐minute cycle time. The reduction in advance time with a cycle time of 24 minutes is due to the effect of the off‐time. Different cycle ratios can be used but the 1/3 cycle ratio may be the best. In conclusion, surge flow irrigation under the short field conditions as prevailing in Egypt decreases the advance time, increases uniformity and efficiency by decreasing deep percolation and reduces applied water volume by 15–35%. Copyright © 2004 John Wiley & Sons, Ltd.

Genotypic variation in common bean in response to zinc deficiency in calcareous soil - Gökhan Hacisalihoglu; Levent Ozturk; Ismail Cakmak; Ross M. Welch; Leon Kochian (Plant and Soil, 2004)

A study on the effect of genotypes, plant growth regulators and sugars in promoting plant regeneration via organogenesis from soybean cotyledonary nodal callus - R.V. Sairam; G. Franklin; R. Hassel; B. Smith; K. Meeker; N. Kashikar; M. Parani; D. Al. Abed; S. Ismail; K. Berry; S.L. Goldman (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Analysis of sedimentary facies and depositional environments of the Permian Gondwana sequence in borehole GDH-45, Khalaspir Basin, Bangladesh - H. M. Zakir Hossain; M. Sultan-Ul-Islam; Syed Samsuddin Ahmed; Ismail Hossain (Geosciences Journal, 2002)

Diversity and distribution of Odonata (dragonflies and damselflies) in the fresh water swamp lake Tasek Bera, Malaysia - Y. Norma-Rashid; A. Mohd-Sofian; M. Zakaria-Ismail (Hydrobiologia, 2001)

A Case of Non-O:1 Vibrio cholerae Septicemia with Meningitis, Cerebral Abscess and Unilateral Hydrocephalus in a Preterm Baby - E. Ismail; M. Shafik; G. Al-Mutairi (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

FTIR-monitored thermal titration reveals different mechanisms for the alkaline isomerization of tuna compared to horse and bovine cytochromes c - Angelo Filosa; A. A. Ismail; A. M. English (JBIC Journal of Biological Inorganic Chemistry, 1999)

Preliminary surveys of outdoor and indoor aeromycobiota in Uganda - M. A. Ismail; S. K. Chebon; Rebecca Nakamya (Mycopathologia, 1999)

Evaluation of the mycological status of luncheon meat with special reference to aflatoxigenic moulds and aflatoxin residues - M. A. Ismail; Z. M. Zaky (Mycopathologia, 1999)

Microbial populations, ammonification and nitrification in soil treated with urea and inorganic salts - S. A. Omar; M. A. Ismail (Folia Microbiologica, 1999)

Stimulation of the bronchus-associated lymphoid tissue of goats and its effect on in vitro colonization by Pasteurella haemolytica - A.W.M. Effendy; M. Zamri-Saad; M.A. Maswati; M.S. Ismail; S.M. Jamil (Veterinary Research Communications, 1998)

Expression of glyoxylate cycle genes in cucumber roots responds to sugar supply and can be activated by shading or defoliation of the shoot - Ismanizan Ismail; Luigi De Bellis; Amedeo Alpi; Steven M. Smith (Plant Molecular Biology, 1997)

A study of losses from field channels under arid region conditions - H. E. M. Moghazi; E.-S. Ismail (Irrigation Science, 1997)

Effect of the nematodeHeterorhabditis bacteriophora and the bacteriumBacillus thuringiensis as integrated biocontrol agents of the black cutworm - M. M. M. Shamseldean; A. A. Ismail (Journal of Pest Science, 1997)

Infleence of some organic manures as soil amendments on development and reproduction ofRotylenchulus reniformis infecting eggplant andHirschmanniella oryzae infecting rice - A. E. Ismail; M. M. A. Youssef (Journal of Pest Science, 1997)

Biochemical composition of benign thyroid cyst fluid - Metin Ozata; Ismail Kurt; Muhittin A. Serdar; M. Emin Onde; Ahmet Aydin; Ahmet Corakci; M. Ali Gundogan (Biological Trace Element Research, 1997)

Loss of residual activity of abamectin on foliage against adult hymenopteran parasitoids - M. Iqbal; F. Ismail; D. J. Wright (BioControl, 1996)

Agrotis segetum granulosis virus as a control agent against field populations ofAgrotis ipsilon andA. Segetum [Lep.: Noctuidae] on tobacco, okra, potato and sugar beet in northern pakistan - O. Zethner; Bashir M. Khan; M. Ismail Chaudhry; B. Bolet; Sharfuddin Khan; Habibullah Khan; Hanif Gul; L. Øgaard; M. Zaman; Gul Nawaz (BioControl, 1987)